Preclinical evidence of chrysin in metabolic disorder via mitochondrial signaling: a mechanistic review - Monika Bansal; Soumarshi Das; Manish Kumar; Teenu Sharma; Sushma Devi (Molecular Biology Reports, 2026)

Transient heat stress irreversibly disrupts molecular signals, cellular and developmental competence of riverine buffaloes (Bubalus bubalis) oocytes and early embryos in a stage-specific manner - Devender Singh; Parul Sarwalia; Manish Kumar; Moloya Gohain; Asit Jain; Tripti Jain; Rakesh Kumar; Tirtha Kumar Datta (Molecular Biology Reports, 2026)

Fusion protein based strategies for developing insect-resistant crops - Marri Keerthana; Morthala Shankara Sai Reddy; Yogesh Dashrath Naik; Arindam Pal; Anil Namdev Kale; Satish Kumar Singh; Sudha Nandni; K. Premalatha; Murukarthick Jayakodi; Venugopal Mendu; Manish K. Pandey; Somashekhar Punnuri; et al. (Functional & Integrative Genomics, 2026)
Insect pest control in crop production incurs substantial economic costs annually on a global scale. Although broad-spectrum chemical pesticides were once considered the most effective solution, their overreliance has led to adverse effects on beneficial insects, human health, and the environment, as well as the development of pesticide-resistant insect populations. Consequently, there is an urgent need for alternative pest management strategies that minimize pesticide use and reduce unintended impacts on natural enemies, thereby maintaining ecological balance. Host plant resistance plays a pivotal role in integrated pest management (IPM). However, developing pest-resistant varieties through conventional breeding methods can be time-consuming and challenging due to the involvement of multiple quantitative traits controlled by various genetic loci. One promising biotechnological approach is the development of fusion proteins, engineered molecules that combine the functional properties of two or more distinct proteins. These fusion proteins effectively target specific insect pests while minimizing environmental impact. Importantly, they overcome key limitations of single-gene constructs, including narrow target range and rapid resistance development. Numerous fusion proteins have been successfully developed and deployed in various crop plants, demonstrating their versatility and broad-spectrum activity against major insect pests. This review discusses fusion protein technologies and their application in developing transgenic crops with enhanced resistance to insect pests.

Integrated genome-wide association study (GWAS) and metabolomics identify genetic and metabolic drivers of stripe rust resistance in wheat from the Western Himalayas - Farkhandah Jan; M. Parthiban; Sofora Jan; Anjan Kumar Pradhan; Sundeep Kumar; Safoora Shafi; Mahpara Bashir; Divya Sharma; Naeela Qureshi; Manish Kumar Vishwakarma; Sarabjit Kaur; Jaspal Kaur; et al. (Functional & Integrative Genomics, 2026)

Comparative phenotypic analysis of primary aortic VSMCs versus TGF - β/PDGF - BB differentiated MSCs in rat - Pulkit Soni; Diksha Rani; Manish Kumar; Vaibhav Kushwaha; Anurag Thapliyal; Satyavir Yadav; Shashank Kumar Maurya; Sanjay Kumar Dey (Tissue and Cell, 2026)

Endohyphal bacterial symbiosis is associated with altered metabolite profiles and stress adaptation in Trichoderma atrobrunneum PEI1: Integrative metagenomic and metabolomic insights - Pramod Kumar Sahu; Krishna Nanda Dhal; Deepak Singla; Niharika Rai; Aditya Kumar Gautam; Nidhi Rai; Astha Pandey; Amrita Gupta; Madhu Yadav; Pankaj Kumar Maurya; Manish Roy; Vivek Kumar; et al. (Physiological and Molecular Plant Pathology, 2026)

Flood risk in India's arid Ramsar wetlands: Integrating extreme rainfall, fuzzy risk assessment, and CMIP6 projections - Shivukumar Rakkasagi; Kushal Jagdish Patil; Manish Kumar Goyal; Shimrit Maman (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Artificial intelligence–driven air quality mapping and forecasting for extreme PM2.5 events - Kuldeep Singh Rautela; Mayank Upadhyay; Manish Kumar Goyal; Sitaram Taigor (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Variability and ozone formation potential of ambient non-methane hydrocarbons in a tropical semi-arid atmosphere of northwest India - Soniya Yadav; Mahendar Chand Rajwar; Chinmay Mallik; Rajesh Kumar; Manish Naja (Journal of Environmental Sciences, 2026)

Structure–function relationships of plant-derived antioxidants in ghee: oxidative stability, thermal behaviour, and simulated intestinal digestion - Aditya Kumar Jain; Tanmay Hazra; Ankit Bihola; Kunal Kumar Ahuja; Rohit Sindhav; Subhash Prasad; Manish Parmar (Food Chemistry, 2026)

The evolution of inverse optimization: A cross-disciplinary review of algorithmic approaches and application framework in building life cycle assessment - Manish Kumar Dixit; Sejal Sanjay Shanbhag (Energy and Buildings, 2026)

Nickel-olivine catalyst action and supercritical water gasification processing of municipal waste for hydrogen extraction - Madaminov Sanjarbek Maxmudjon Ugli; Pradeep Kumar Singh; G. Tejasri Devi; Himanshu Makhija; P.S. Ranjit; Manish Nagpal; Ponmurugan Panneerselvam; Ramya Maranan; Anand Rajendran; M. Murali (Biomass and Bioenergy, 2026)

Phytochemical profiling, enzyme inhibition and computational analysis of the anti-diabetic and anti-obesity potential of Spirogyra sp. - Vishal Kumar; Deepika Kaushik; Fatih Oz; Charalampos Proestos; Manish Chaudhary; Mukul Kumar (Algal Research, 2026)

Phytogenic synthesis of cobalt oxide nanoparticles with Mallotus philippensis and their photocatalytic–antimicrobial efficiency - Sandeep Kumar; Pooja Kumari; Manish Kumar; Deepika Kaushal (Next Research, 2026)

Occupational exposure to respirable crystalline silica and its association with pulmonary function impairment among coal mine workers: A retrospective assessment - Manish Yadav; Nitin Kumar Singh; Tanveer Rehman; Sanghamitra Pati; Vinita Arora; Sumit Saha (Environmental Research, 2026)

Genome wide association studies and expression analyses identify candidate genes for spot blotch resistance in bread wheat - G. Mahendra Singh; Uttam Kumar; Bhagya Shree Acharya; Pradeep Bhati; Manish Vishwakarma; Dinesh Kumar Saini; Sundeep Kumar; Vinod K. Mishra; Arun K. Joshi; Sandeep Sharma (Theoretical and Applied Genetics, 2026)

Cross incompatibility restricting genome exchange and diversification of primary gene pool in plants: challenges and opportunities - Mahendar Thudi; Yogesh Dashrath Naik; Uday Chand Jha; M. S. Sai Reddy; Manish Kumar Pandey; Reyazul Rouf Mir; Muraleedhar S. Aski; Murukarthick Jayakodi; Venugopal Mendu; Naveen Puppala; P. V. Vara Prasad; Somashekhar M. Punnuri; et al. (Theoretical and Applied Genetics, 2026)
Key message Crop wild relatives provide essential genetic diversity for improving crop resilience; however, pre- and post-zygotic barriers often restrict interspecific hybridization. Recent approaches enable their effective use in crop improvement programs. Abstract Crop wild relatives (CWR), closely related wild taxa of cultivated crops, offer a wealth of genetic diversity essential for developing traits to help crops adapt to the challenges of biotic and abiotic stresses. This diversity is critical to meet the increasing global demand for food, especially under the looming threat of climate change. However, crossing between individuals from different species often results in maladapted or inviable offspring due to pre- and post-zygotic barriers. Pre-zygotic barriers prevent successful pollen–stigma interactions and pollen tube growth, while post-zygotic barriers include hybrid embryo or endosperm failure and chromosome pairing issues, contributing to cross incompatibility (CI). These barriers restrict genome exchange and hinder the diversification of the primary gene pool in plants. Overcoming these barriers is a significant challenge. This review explores the diverse pre- and post-zygotic barriers in interspecific hybridization, emphasizing genetic factors related to CI. Additionally, this review highlights biotechnological approaches such as somatic hybridization and embryo rescue techniques, which are used to overcome these barriers. Through continued research and innovation, these barriers can be overcome, unlocking the full potential of CWR to address the evolving demands of global agriculture. Recent advances in synthetic biology now offer the possibility to reprogram reproductive barriers, turning CI into a controllable trait for hybrid development.

Indian monsoon climate records from the Palaeogene-Early Miocene soil repositories in the Kangra sub-basin of the NW Himalaya - Seema Singh; Rajan Bhandari; Asifa Kamboj; Manish Kumar; Sudhir Kumar (Journal of Sedimentary Environments, 2026)

Heat stress responses and thermoregulatory dynamics in Murrah buffalo calves assessed by infrared thermography - Reetu Kumari; Priyambada Kumari; Brijesh Yadav; Shanker Kumar Singh; Vansh Sharma; Manish Tiwari; Saeeda Khanam; Pooja Dawar; Krishna Verma; Arun Kumar Madan (International Journal of Biometeorology, 2026)

Interpretable machine learning for reliability-oriented prediction of the reduction factor of eccentrically loaded strip footings using MARS and XGBoost - Manish Kumar (Innovative Infrastructure Solutions, 2026)

Pyramiding of Multiple QTL for Drought and Submergence Tolerance for Infusing Climate-Resilience in Rice Variety Samba Mahsuri - Priyanka Jain; Riti Thapar Kapoor; Manish Kumar; Neera Yadav; Mukta Rani; Rekha Joshi; Vandana Rai; Deepak Singh Bisht; Kishor Gaikwad; Nagendra Kumar Singh (Indian Journal of Genetics and Plant Breeding, 2026)

Compound Climate Extremes: Interactions, Emerging Urban Stressors, and Impacts on Water Quality - Aanchal Kumari; Durga Prasad Panday; Kanchan Deoli Bahukhandi; Aldo I. Ramirez; Manish Kumar (Current Pollution Reports, 2026)

Introducing Relationship Matrix of Combined USLE and Morphometric Analyses for Prioritization of Soil Erosion Susceptibility Zones - Manish Kumar Sinha; Amit Prakash Multaniya; Raju Choudhary; Sharad Patel (Journal of the Indian Society of Remote Sensing, 2026)

Correction to: Effects of anthropogenic stress on river water quality during Mahakumbh (2025) at Sangam, Prayagraj, India: a multivariate approach and water quality index - Rakesh Kumar Parida; Santosh Kumar Rai; Manish Pant (Environmental Science and Pollution Research, 2026)

Targeting methyl-accepting chemotaxis transmembrane sensory protein inhibits Helicobacter pylori autoinducer-2 quorum sensing system - Thejaswi Bhat; Manish Kumar; Tamizh Selvan Gnanasekaran; Pavan Gollapalli (Biologia, 2026)

Topographic and Land Use Driven Land Surface Temperature Dynamics in a Fragile Lesser Himalayan Catchment - Pravin Rangrao Patil; Harsh Upadhyay; Disha Yadav; Manish Kumar Nema; A. R. Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2026)

Comparative toxicity of nickel titanate and calcium manganite perovskite nanomaterials in human and bacterial systems: Implications for environmental and health risks - Prashant Sharma; Indranil De; Nikita Chaudhary; Gurvinder Singh; Dinesh Kumar; Kaushik Ghosh; Manish Singh (Chemosphere, 2026)

Escalating heat waves and human thermal stress over semi-arid Bundelkhand region, India - Yogeshwar Singh; Rahul Kumar; Soumyajeet Sahu; Shobhit Pipil; Shiv Vendra Singh; Pavan Kumar; Manish Srivastav; A.K. Singh (Urban Climate, 2026)

Retraction notice to “Rice straw derived graphene-silica based nanocomposite and its application in improved co-fermentative microbial enzyme production and functional stability” [Sci. Total Environ. 876 (2023) 162765] - Mohammed Asiri; Neha Srivastava; Rajeev Singh; Amer Al Ali; Subhash C. Tripathi; Abdulaziz Alqahtani; Mohd Saeed; Manish Srivastava; Ashutosh Kumar Rai; Vijai Kumar Gupta (Science of The Total Environment, 2026)

Retraction notice to “Mobilization of contaminants: Potential for soil remediation and unintended consequences” [Sci. Total Environ. 839 (2022) 156373] - Manish Kumar; Nanthi Bolan; Tahereh Jasemizad; Lokesh P. Padhye; Srinidhi Sridharan; Lal Singh; Shiv Bolan; James O'Connor; Haochen Zhao; Sabry M. Shaheen; Hocheol Song; Kadambot H.M. Siddique; et al. (Science of The Total Environment, 2026)

Retraction notice to “Biotechnological potential of rumen microbiota for sustainable bioconversion of lignocellulosic waste to biofuels and value-added products” [Sci. Total Environ. 814 (2022) 152773] - Sachin Krushna Bhujbal; Pooja Ghosh; Virendra Kumar Vijay; Rashmi Rathour; Manish Kumar; Lal Singh; Atya Kapley (Science of The Total Environment, 2026)

Retraction notice to “Biochar modulating soil biological health: A review” [Sci. Total Environ. 914 (2024) 169585] - Shiv Bolan; Shailja Sharma; Santanu Mukherjee; Manish Kumar; Ch. Srinivasa Rao; K.C. Nataraj; Gurwinder Singh; Ajayan Vinu; Arnab Bhowmik; Harmandeep Sharma; Ali El-Naggar; Scott X. Chang; et al. (Science of The Total Environment, 2026)

On the laminar wake of a circular cylinder in an accelerating environment - Manish Manojkumar Menon; Avinash Nair; Kexin Wu; Vignesh Ram Petha Sethuraman; Ajith Kumar S. (Ocean Engineering, 2026)

Building a high-resolution late Miocene benthic foraminiferal δ13C record from the Bay of Bengal with a non-destructive approach using machine learning - Vikash Kumar; Manish Tiwari; Mohd Tarique; Ravi Bhushan; T. Sarathchandraprasad (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Comparative assessment of artificial neural network and response surface methodology for modeling and optimizing phosphate adsorption onto rice straw biochar - Sheetal Kumari; Smriti Agarwal; Jyoti Chowdhry; Pinki Sharma; Manish Kumar; Ajay Kumar; Manoranjan Nayak; Manoj Chandra Garg (Journal of Environmental Management, 2026)

Pilot scale production, structural characterization, and cytotoxicity assessment of insoluble linear β-1,3 glucan from Euglena gracilis - Vijay Kumar; Nirmal Renuka; Manish S. Bhoyar; Chandra Sekhar Mohanty; Puneet Singh Chauhan; Kiran Toppo; Sachitra Kumar Ratha (Carbohydrate Polymers, 2026)

A multipurpose medicinal tree under threat: biology, phytochemistry, propagation and conservation of Dillenia pentagyna Roxb - Manish Kumar Vijay; Neelu Singh (The Science of Nature, 2026)

Market Landscape and In-vitro Assessment of Commercially Available Domperidone Products - Himanshu Saini; Hitesh Kumar; Anushka Chopra; Navneet Sharma; Manish Dhall (Journal of Pharmaceutical Innovation, 2026)

Controversy and consensus: common ground and best practices for life cycle assessment of emerging technologies - Rachel Woods-Robinson; Amila Abeynayaka; Michael Carbajales-Dale; Hao Chen; Anthony Cheng; Gregory Cooney; Abby Kirchofer; Manish Kumar; Heather P. H. Liddell; Lisa Peterson; I. Daniel Posen; Sheikh Moni; et al. (Journal of Industrial Ecology, 2026)
Public and private interest in life cycle assessment (LCA) has grown as environmental disclosure norms tighten, driving demand for decision-relevant assessment early in technological development cycles. Early-stage LCA has the potential to guide design choices, steer innovation, and mitigate lock-in of adverse environmental impacts. However, many aspects of early-stage LCA practice remain unsettled. We convened experts in a series of Faraday Discussion-style workshops to address recurring debates across six key topics for emerging technologies: appropriate use of LCA, uncertainty, comparison with incumbents, standardization, scale-up, and stakeholder engagement. For each issue, we present a declarative resolution, summarize key arguments for and against it, identify points of consensus, and provide recommendations. Across topics, the research network converged on practical priorities including framing studies to the decision context; setting minimum reporting expectations for data and study quality; and explicitly stating limits of transferability for scenario-based uncertainty assessment or analytically scaled-up projections. Disagreements persisted on when to formalize standards and how extensively uncertainty can/should be treated for low-maturity technologies. Supplementing the workshop findings with examples and context from relevant literature, we synthesize outcomes into a set of shared challenges and research priorities to strengthen transparent, evidence-based, and context-informed approaches for early-stage LCA.

Catchment–Wetland Associations Based on Multiscale Landscape Structure and Hydro-Ecological Indicators at Bakhira Ramsar Site, India - Manish Rawat; Ashish Pandey; Basant Yadav; Praveen Kumar Gupta (Environmental Management, 2026)

Hydro-geomorphic amplification of flash flood hazards: transect-based analysis of the 2025 Dharali flood, Himalayan Bhagirathi river, India - Shravankumar S. Masalvad; Manish Pandey; N. V. Umamahesh; Anil Kumar Gupta (Environmental Fluid Mechanics, 2026)

Genome Wide Association Study Reveals Novel Loci Controlling Agronomic Traits in Tomato (Solanum lycopersicum L.) - Jagesh Kumar Tiwari; Nagendra Rai; Manish Kumar Singh; Rajat Singh; Tushar Kant; Suresh Reddy Yerasu; Achuit Kumar Singh; Rajesh Kumar (Biochemical Genetics, 2026)

Scaling Laws Reveal a Unified Species‐Energy Relationship for Mountain Biodiversity - Zihan Jiang; Hongyan Liu; Zhiyao Tang; Jonathan M. Chase; Alexandre Antonelli; Michael Kessler; Maharaj K. Pandit; Kumar Manish; Wei Xu; Jianxiao Zhu; Qinggang Wang; Hang Sun; et al. (Global Ecology and Biogeography, 2026)
Aim Energy availability is often assumed to be a primary driver of variation in biodiversity across large‐scale environmental gradients such as elevation, but support for the role of energetic constraints is far from universal. Here, we assume that these variations in energy–richness relationships might arise from the degree of match between the scale of the response of organisms to energy (response scale) and the scale of the observation made (observation scale). Location 41 mountain ecosystems worldwide, with detailed case studies on Dongling Mountain, China. Time Period Contemporary. Major Taxa Studied Trees, shrubs, herbs, ferns, birds, ants, bees, Lepidoptera, Coleoptera, Orthoptera, soil fauna, litter‐layer fauna, bacteria, fungi. Methods First, we quantify the response scale on the basis of energy requirements, and then, we develop a general scaling model that explicitly describes how the scale matching between response and observation scale influences the predictive power of energy in determining elevational richness patterns; this model holds across taxonomic groups, trophic guilds, and ecosystems across mountains globally. Results Global analyses strongly supported the model's prediction that scale matching determines the detectability of energy‐richness relationships. On Dongling Mountain, energy availability best explained richness patterns at the predicted response scales for trees, herbs, and litter fauna. Main Conclusions Our model advances the understanding of montane biodiversity distributions by demonstrating the critical role of scale matching in energy–richness relationships. Our findings strongly support the existing mechanistic foundation for predicting biodiversity changes across spatial scales in montane ecosystems. The scale‐matching principle we identified is likely to be applicable to a wide range of taxa and other ecosystems where energy availability varies across scales.

Repurposing drugs for treating dengue haemorrhagic fever and associated autoimmune diseases - Govinda Rao Dabburu; Anjali Garg; Anchal Vishnoi; Neelja Singhal; Manish Kumar (In Silico Pharmacology, 2026)

Multi-proxy hydrochemical and microbial fingerprinting of sewage contamination in the Upper Ganga River, Uttarakhand - Rakesh Kumar Parida; Manish Pant; Santosh Kumar Rai (Environmental Monitoring and Assessment, 2026)

Effects of heading back on leaf nutrients, flowering, physiological and fruit-related traits in mango (Mangifera indica L.) cv. Amrapali - Harshit Kumar; Manish Srivastav; Kanhaiya Singh; A. Nagaraja; S. Gopala Krishnan; Pandey Rakesh; Shruti Shethi; V. K. Sharma; Gulshan Kumar; Prabhanjan Rane; Hansraj Meena (Vegetos, 2026)

Effect of Boron on the Growth Performance, Biochemical Indices, Carcass, Intestinal and Bone Characteristics with Economics in Broiler Chickens - Jayant Kumar Kakwani; Dharmesh Tewari; S. Gautam; Pallavi Maurya; S. S. Kashyap; V. K. Singh; Shubham Tripathi; Manish Kumar Singh; Sandeep Kumar Chaudhary (Biological Trace Element Research, 2026)

Effects of anthropogenic stress on river water quality during Mahakumbh (2025) at Sangam, Prayagraj, India: a multivariate approach and water quality index - Rakesh Kumar Parida; Santosh Kumar Rai; Manish Pant (Environmental Science and Pollution Research, 2026)

Optimising CRDI engine performance using waste-derived biodiesel, bioethanol, and ceric oxide nanoparticles: An RSM approach for emission reduction and economic viability - Manish Kumar; Naushad Ahmad Ansari; Raghvendra Gautam (Fuel, 2026)

Influence of different pre-sowing seed treatments on the germination and growth performance of Abutilon indicum Linn. - Varsha Pandey; Samiksha Parihar; Hari Om Saxena; Manish Kumar Vijay; Anil Kumar Yadav (Vegetos, 2026)

Ecological niche modelling of Saussurea obvallata (DC.) Sch.Bip., a culturally and medicinally important threatened species of Indian Himalayan region - Gourav Devtalla; Praveen Gunwant; Anil Kumar Yadava; Manish Tripathi (Journal for Nature Conservation, 2026)

Synergistic interplays of emerging contaminants: Rethinking water security, risk, and resilience in a changing world - Manish Kumar; Kashyap K. Dubey; Keisuke Kuroda; Sanjeeb Mohapatra; Vivek Agarwal; Rakesh Kumar (Current Opinion in Environmental Science & Health, 2026)

Photoperiodic alteration modulates immune responses of freshwater snakehead teleost, Channa punctatus - Sheena Farheen Khan; Swati Shree; Manish Kumar Tripathi (Veterinary Research Communications, 2026)

Nutrient-solution modulation on physiological responses and volatile metabolism in Ocimum basilicum L. - Snehlata Dalal; Pooja Thakur; Shiv Rattan; Manish Kumar; Bhavya Bhargava; Dinesh Kumar; Rakesh Kumar; Ashish R. Warghat (Plant Physiology Reports, 2026)

The role of green chemistry in the transformation of agro-industrial wastes for health and environment: a review - Manoj Chandra Garg; Sheetal Kumari; Minh-Ky Nguyen; Basil Osayin Daudu; Sanskriti Thapa; Juhi Gupta; Manish Kumar; Elif Esra Altuner; Akhilesh Kumar Yadav; Esther Besty Anaiye; Adel Zrelli; Kassian T. T. Amesho (Biodegradation, 2026)

Smart agroforestry interventions for enhancing livelihood and ecological resilience in semi-arid regions - Prabhat Tiwari; Garima Gupta; Pankaj Lavania; Soumyajeet Sahu; Preeti Kumari; Manmohan Dobriyal; S. S. Singh; Manish Srivastav; A. K. Singh; Pavan Kumar (Agroforestry Systems, 2026)

Flavonoids as functional food-derived modulators of the gut microbiota-NF-κB axis in metabolic dysfunction-associated steatotic liver disease - Lunasmrita Saikia; Partha Pratim Dutta; Douglas Law; Saikat Sen; Manish Kumar Gautam; Dhrubajyoti Gogoi (Molecular and Cellular Biochemistry, 2026)

Synthesis, radiolabelling and preliminary evaluation of [68Ga]Ga-DOTA-linked cyanuric chloride–glu-ureido scaffold for PSMA PET imaging - Mohd Faheem; Vaibhav Pandey; Anjali Pal; Pradeep Kumar Sharma; Manisha Prasad; Manish Dixit (Molecular Diversity, 2026)

β-defensin1 antimicrobial peptide protects mitochondrial function, DNA integrity and calcium homeostasis in cryopreserved buck spermatozoa - Manish Kumar; Ravi Ranjan; Alok Bharadwaj; Kumarsen Gururaj; Dilip Kumar Swain (Small Ruminant Research, 2026)

Estimating anisotropy of fracture patterns using gray level Co-occurrence matrix (GLCM) approach: Implication on understanding permeability anisotropy - Raghubeer Rai; Sivaji Lahiri; Ayoti Banerjee; Somnath Santra; Sachin Kumar; Manish A. Mamtani (Journal of Structural Geology, 2026)

Composite Heat Wave Risk (CHWR) framework using Principal Component Analysis (PCA) and machine learning for assessing agro community resilience - Dolgobinda Pal; Saon Banerjee; Nidhi Nagabhatla; Sarath Chandran M. A.; Amitava Panja; Sarathi Saha; Manish Kumar Naskar; Subhadeep Sarkar (Journal of Environmental Management, 2026)

Groundwater pollution and sustainable development goals: A crucial resource for achieving sustainable environment - Rakesh Kumar; Prabhakar Sharma; Jasmeet Lamba; Manish Kumar; Maria Aurora Armienta; Tom van der Voorn; Prosun Bhattacharya (Groundwater for Sustainable Development, 2026)

The impact of climate-induced extreme weather events on soil constraints and ecosystem functioning - Manish Kumar; Shiv Bolan; Anandkumar Naorem; Smirti Shukla; Nitika Chandel; Santanu Mukherjee; Cherukumalli Srinivasa Rao; Patricia Saco; Jose Rodriguez; Karolina Furtak; Renu Dhupper; Sasha Jenkins; et al. (Journal of Soils and Sediments, 2026)

Spatial analysis and hybrid machine learning prediction of forest fire susceptibility: a longitudinal appraisal synergy with physiographic division - Netrananda Sahu; Pritiranjan Das; Prince Gupta; Suraj Kumar Mallick; Rajiv Pandey; Xiaojun Wang; Manish Kumar; Ayush Varun; Ravi Kesharwani; Anil Kumar (Advances in Space Research, 2026)

Exploring the immune‐modulatory role of melatonin in head kidney and spleen cells of freshwater snakehead teleost, Channa punctatus - Sheena Farheen Khan; Swati Shree; Manish Kumar Tripathi (Journal of Fish Biology, 2026)
Melatonin, the ubiquitous hormone marks its presence from plants to animals with remarkable antioxidant and anti‐inflammatory properties. In the teleost, melatonin is secreted from the pineal gland, which functions as a modulator of circadian rhythm, being homologous to the suprachiasmatic nuclei of mammals. The current study revolves around evaluating the role of in vitro melatonin in the immune mechanism of the snakehead fish, Channa punctatus . Reactive oxygen and nitrogen species production was assayed by respiratory burst and nitrite assay. Mitogen‐stimulated lymphocyte proliferation was done using concanavalin A, phytohemagglutinin and lipopolysaccharide. Macrophage phagocytosis was also assessed using yeast cells. Melatonin administration to the cultures of spleen and head kidney cells enhanced phagocytic activity, superoxide and nitric oxide production. Direct action of melatonin was confirmed by using the melatonin receptor antagonist luzindole, which resulted in suppression of melatonin‐mediated elevation of immune responses. Further, the use of adenylate cyclase inhibitor, SQ 22536, caused suppression of immune activity, signifying the involvement of cAMP in the downstream signalling cascade. This study concludes the immuno‐stimulatory role and elucidates the signalling pathway of melatonin. The findings of the present study may help understand the melatonin‐mediated immune modulation, which may result in altered disease resistance and mortality.

Network pharmacology, molecular docking, and In Vitro evaluation of morin against gastric cancer - Nilesh Naskar; Sunil Kumar; Deepanshu Mamgai; Harish Chandra Vishwakarma; Santosh Kumar Guru; Bijo Mathew; Naseer Maliyakkal; Uday R. Kumar; Shweta Shrivastava; Manish Kumar Jeengar (Molecular Diversity, 2026)

Assessment of heavy metal enrichment, ecological risk with in-situ phyco-remediation approach: A regional study from Odisha’s coastal creeks, India - Dharitri Mishra; Suman Patra; Manish Kumar; S. Dinesh Kumar; R. Sathish; Nabin Kumar Dhal (Regional Studies in Marine Science, 2026)

Long-term spatiotemporal assessment of wetland degradation and ecological resilience in Indian Ramsar sites spanning various agroecological zones - Manish Rawat; Basant Yadav; Praveen Kumar Gupta; Ashish Pandey (Remote Sensing Applications: Society and Environment, 2026)

A review on phosphotungstate-based materials for their photocatalytic degradation - Shivani Devi; Divya Thakur; Amit Kumar; Vivek Sheel; Vinay Chauhan; Deepika Kaushal; Manish Kumar (Next Research, 2026)

Hydrochemical redistribution in a stressed aquifer system: Decadal attenuation of salinity extremes and expansion of diffuse agricultural contamination across Mexico - Sachin Tripathi; Durga Prasad Panday; Juan Antonio Torres-Martinez; Saugata Datta; Manish Kumar (Journal of Contaminant Hydrology, 2026)

Intensification of rice-wheat cropping system with summer green gram improves growth, productivity and profitability of rice in the middle Indo-Gangetic Plains of India - Manish Raj; Sushant; Mainak Ghosh; Anil Kumar Singh; Sumit Sow; Sanjay Kumar; Birendra Kumar; Swaraj Kumar Dutta; Nintu Mandal; Pritam Ganguly; Arnab Roy Chowdhury; Shishpal Poonia; et al. (European Journal of Agronomy, 2026)

The future of global Ramsar wetlands under intensifying precipitation extremes: Arid regions as emerging hotspots - Deepak Mishra; Nakka Naveen Kumar; Shekhar Singh; Manish Kumar Goyal (Environmental Impact Assessment Review, 2026)

Fabrication of customizable thin film composite membranes by electrospray assisted interfacial polymerization - Mert Can Hacifazlioglu; Salman Ahmadipouya; Deniz Ipekci; Mayur Ostwal; Edward Wazer; Matthew Coupin; Chenhao Yao; Jamie Warner; Manish Kumar; Ying Li; Yuepeng Zhang; Jeffrey R. McCutcheon (Desalination, 2026)

A systematic review of methods and frameworks integrating environmental sustainability and resilience in building design and construction - Mana Nemati Aghdam; Manish Kumar Dixit (Building and Environment, 2026)

Valorization of paneer waste whey through fermentation with Pediococcus pentosaceus NCDC 273 insights from intracellular metabolomics by GC-MS - Manish Singh Sansi; Daraksha Iram; Kamal Gandhi; Nishi Singh; Shiv Kumar Sood (Biocatalysis and Agricultural Biotechnology, 2026)

Evaluating the Dynamics of Urban and Rural Areas Adjacent to the Coal Mining Region of Eastern India Using Landsat time Series Data - Wilson Kandulna; Manish Kumar Jain (Journal of the Indian Society of Remote Sensing, 2026)

Effect of Tree Age on Leaf Nutrient, Flowering, Physiological and Fruit-Related Traits in ‘Amrapali’ Mango (Mangifera indica L.) Under an Intensive Planting System - Harshit Kumar; Manish Srivastav; Gulshan Kumar; Prabhanjan Rane; Hansraj Meena; Kanhaiya Singh; A. Nagaraja; Gopala Krishnan S.; Rakesh Pandey; Shruti Shethi; V. K. Sharma (Applied Fruit Science, 2026)

Mineralogical profiling of fine particulate matter (PM2.5) over the Megacity Delhi and the Central Himalayan Region Nainital, India - Anjali Rana; Preeti Tiwari; Priyanka Srivastava; Sakshi Gupta; Manish Naja; Surinder P. Singh; Sudhir Kumar Sharma; Sachchidanand Singh (Air Quality, Atmosphere & Health, 2026)

Non-methane hydrocarbon (NMHC) variability in rural Himalayan atmospheres: impacts on ozone, secondary organic aerosols, and human health - Mahendar Chand Rajwar; Manish Naja; Prajjwal Rawat; Vikrant Tomar; Mukesh Kumar; Priyanka Srivastava; Shyam Lal (Environmental Science and Pollution Research, 2026)

Unveiling the Potential of Plant-derived Exosomes: A Comprehensive Review - Srishty Jaiswal; Mitali Sethi; Rafquat Rana; Shourya Tripathi; Arun Kumar Trivedi; Manish K. Chourasia (AAPS PharmSciTech, 2026)

Oroxylum indicum (L.) kurz as a promising Anticancer resource: bridging ethnopharmacology, biotechnology, and conservation perspectives - Mhaiskar Priya Rajendra; Katikala Anish; Milkuri Chiranjeeva Reddy; Manish Kumar; Yerrawada Naveen; Bheemreddyvalla Venkateshwar Reddy; Rohith Ravula; Akkenapally Snehanjali; Sachin Kumar (Natural Product Research, 2026)

Effect of ahfad2 genes on oil profile of advanced breeding lines in groundnut (Arachis hypogaea L.) - Pesaleddula Jashuva Paul; Srividhya Akkareddy; Manish K. Pandey; Spandana Bandila; Sree Vidya Gundrathi; Girish Kumar Killada (The Nucleus, 2026)

Bikaneri Camel Milk-Derived Low-Molecular-Weight Peptides as a Novel Therapeutic Approach for Diabetes - Sunny Kalyan; Rakesh Kumar Raman; Dipanjan Misra; Manish Singh Sansi; Sunita Meena (International Journal of Peptide Research and Therapeutics, 2026)

Deciphering the Genetic Determinants of Bull Fertility through QTL-Linked SNP Analysis - Manish Kumar Sinha; Pradeep Nag; Arumugam Kumaresan; Thirumala Rao Talluri; John Peter Ebenezer Samuel King; Arsha shaji; Shivanagouda Patil; Anand Kumar Yadav; Kishan Kumar Fataniya; V. Aranganathan (Agricultural Research, 2026)

High-throughput Verticillium wilt detection in cotton: A comparative study of faster R-CNN and YOLOv11 - Manish Kumar Patel; Geoff Bull; Lucy M. Egan; Natasha Swain; Vivien Rolland; Warwick N. Stiller; Warren C. Conaty (Biosystems Engineering, 2026)

Antarctic warming affects northern Equatorial Indian Ocean SST via oceanic tunnels - Sharmila Sherin; Manish Tiwari; Vikash Kumar (Global and Planetary Change, 2026)

Multi-Objective Variance-Bias Tradeoff Optimization of ANN by Hybridizing with Multi-Objective GA for Water Discharge Estimation - Arvind Yadav; Ashwini Kumar Pradhan; Manish Kumar; Priyaranjan Sharma; Sunil Kr. Maakar; Shivangi Singh; Umamaheswararao Batta; Devendra Joshi (Water Resources Management, 2026)

Spatiotemporal assessment of extreme rainfall events in the Wainganga river basin using CMIP6 climate models - Gupta Abhishek Rajkumar; Manish Kumar Nema; Deepak Khare (Natural Hazards, 2026)

Machine Learning Driven Urban Flood Susceptibility Analysis of National Capital Territory Delhi: Integrating Remote Sensing and GIS Technique - Monika Dudy; Syed Irtiza Majid; Anant Rajee Bara; Manish Kumar; Rakesh Kumar; Benay Kumar Ray (Journal of the Indian Society of Remote Sensing, 2026)

Cytosine methylation at proximal 3’UTR modulates gene expression of leaf rust responsive microRNA targeted allene oxide cyclase (TaAOC) in wheat - Uzma Afreen; Shailendra Kumar Jha; Kunal Mukhopadhyay; Manish Kumar (Cereal Research Communications, 2026)

Comprehensive Proteomic Profiling and Functional Network Analyses of Indigenous Zebu (Bos indicus) Cattle Spermatozoa - Apoorva Verma; Arumugam Kumaresan; Shivanagouda Patil; Manish Kumar Sinha; John Peter Ebenezer Samuel King; Pradeep Nag; Gowdar Veerappa Vedamurthy; Sakthivel Jeyakumar; Ayyasamy Manimaran; Kerekoppa Ramesha (Agricultural Research, 2026)

Impact Assessment of Climate Change on Soybean Crop Using CROPGRO-Soybean Model in Central India - Manish Bhan; Deshraj Patel; Santanu K. Bal; Puppala V. Kumar (Agricultural Research, 2026)

Fungi as Therapeutics: Bridging Traditional Wisdom and Modern Medicine - Bidhan Mahajon; Rupashri Nath; Santosh Kumar Thakur; Manish Kumar Gautam; Sandip Mondal; Nur Shaid Mondal; Arup Dey; Partha Pratim Dutta (New Zealand Journal of Botany, 2026)
Fungi have been recognized for their medicinal properties for centuries, playing critical roles in both traditional and modern medical systems. Ancient practices, such as Ayurveda and Traditional Chinese Medicine (TCM), have utilized fungi for their therapeutic properties, while modern pharmacology has harnessed fungal metabolites to develop groundbreaking drugs. This study aims to provide a comprehensive overview of the medicinal applications of fungi, emphasizing their role in traditional medicine systems, modern drug development, and potential mechanisms of action. It also addresses the challenges and prospects of integrating fungal‐based therapies into the healthcare system. A comprehensive analysis of classical medicinal texts and contemporary scientific literature identified key fungal species, their bioactive compounds, and the underlying mechanisms of their therapeutic effects. Fungal species such as Ganoderma lucidum , Cordyceps sinensis , and Trametes versicolor have a long‐standing tradition in traditional medicine for enhancing the immune system and promoting health restoration. Modern pharmacology has leveraged fungal metabolites, such as penicillin and cyclosporine, revolutionizing the development of antibiotics and immunosuppressants. Fungi play a crucial role in addressing global health challenges through their diverse mechanisms of action, including immune modulation, anti‐inflammatory pathways, and direct antimicrobial effects. Their bioactive compounds exhibit unique therapeutic properties, making them valuable in combating diseases and infections. As a bridge between traditional wisdom and modern science, fungi encapsulate centuries of indigenous knowledge about their medicinal uses. Integrating this traditional understanding with advanced biotechnological tools enables the discovery of novel applications for fungal metabolites. This synergy offers sustainable and innovative solutions for pressing health issues, paving the way for breakthroughs in pharmaceuticals, therapeutics, and global healthcare systems.

Mass Spectrometry-Guided Library Preparation of Peptides as Metabolic Enzyme Natural Inhibitors for the Management of Obesity and Diabetes - Manish Singh Sansi; Daraksha Iram; Sunny Kalyan; Sudarshan Kumar; Suman Kapila; Kamal Gandhi; Sunita Meena (International Journal of Peptide Research and Therapeutics, 2026)

Interrelationship Between Indoor Air Quality and Indoor Dust in Four Schools across Dhanbad City, India - Shravan Kumar; Manish Kumar Jain (Aerosol Science and Engineering, 2026)

Role of urban green space structure and configuration in regulating land surface temperature in NCT Delhi using explainable artificial intelligence - Manish Kumar; Sourav Bhadwal; Netrananda Sahu (Urban Climate, 2026)

Plasmid-borne multidrug resistance genes in environmental isolates from hospital effluent: Implications for resistance dissemination - Prajakti; Manish Kumar Pandey; Kunal Mukhopadhyay (Science of The Total Environment, 2026)

Leveraging machine learning for microplastic detection, global distribution analysis, and management - Sheetal Kumari; Prabhat Kumar Patel; Manish Kumar; Hao Yi Cheng (Journal of Hazardous Materials, 2026)

Understanding radon behaviour in traditional Indian dwellings: Insights from a validated CFD study of a representative mud test house - Rajat Parkash; Sandeep D. Kanse; Tarun Kumar Agarwal; Rosaline Mishra; Manish Joshi; R.P. Chauhan (Environmental Pollution, 2026)

Harnessing microplastic contaminant hydro(bio)logy: Proxies for flood impact, surface-groundwater connectivity, and urbanisation - Manish Kumar; Aseem Saxena; Sachin Tripathi; Durga Prasad Panday; Juan Antonio Torres-Martínez (Current Opinion in Environmental Science & Health, 2026)

Bio-transforming maize husk residue into a multi-omics-validated biostimulant: Agro-waste bioformulation sustaining micronutrient delivery in millets - Shubham Anil Durgude; Raj Kumar Jat; Vijay Singh Meena; Manish Kumar Vishwakarma; Shiv Vendra Singh; Suneel Kumar; Pazhanisamy Selvaganesan; Mohammed Hassnain; Arun Kumar Joshi (Biomass and Bioenergy, 2026)

Carbon dioxide (CO2) variations across India: Synthesis of observations and model simulations - Ravi Kumar Kunchala; Imran Girach; Chiranjit Das; Chaithanya Jain; Pramit Kumar Deb Burman; Mahesh Pathakoti; Prabir K. Patra; Yogesh K. Tiwari; M. Venkat Ratnam; Vinayak Sinha; Vinu Valsala; Manish Naja; et al. (Atmospheric Environment, 2026)

Comparative metabolomics-based screening of fruit extracts of less-known melon ( Cucumis melo var . agrestis) accessions collected from dry terrain of North India by using HPLC–DAD - Chanchal Sharma; Jyoti Rani; Manish Kapoor; Navneet Kaur; Sandeep Gawdiya; Saroj Kumar Pradhan (Natural Product Research, 2026)

Spatio-Temporal Analysis of Drought Characteristics and Trend in Mahanadi River Basin Over the Last 121 years (1902–2022) - Preeti Rajput; Manish Kumar Sinha; Ajay Kumar Garg; Mukesh Kumar Verma (Pure and Applied Geophysics, 2026)

Pangenome-based network analysis of Acinetobacter baumannii reveals the landscape of conserved therapeutic targets - Thejaswi Bhat; Manish Kumar; Krishna Kumar Ballamoole; Vijaya Kumar Deekshit; Pavan Gollapalli (Molecular Diversity, 2026)

Heavy Metal Accumulation on the Roadside Plant Species with Ethnobotanical Significance and Human Health Risk Assessment: A Case Study of a Major Highway Near the Coal Capital of India - Jitin Rahul; Manish Kumar Jain; Beenu Raj; Mansi Sharma; Shiv Shankar; Aliya Naz; Abhiroop Chowdhury (International Journal of Environmental Research, 2026)

Exposure assessment of respirable free silica in coal mining areas - Manish Yadav; Nitin Kumar Singh; Sumit Saha (Environmental Geochemistry and Health, 2026)

Exploring a Case of Unconjugated Hyperbilirubinaemia Resulting from the Rare Coexistence of Inherited Disorders- A Case Report - Sumita Sharma; Kapil Sharma; Onjal K. Taywade; Manish Kumar; Anurag Sankhyan (Indian Journal of Clinical Biochemistry, 2026)

Evolving Approaches in Groundwater-Surface Water Interaction Studies: From Numerical Models to Machine Learning - Lolali Nanda; Durga Prasad Panday; Pankaj Kumar Srivastava; Durga Madhab Mahapatra; Uday Bhan; Manish Kumar (Current Pollution Reports, 2026)

Comparative HPTLC analysis of shatavarin IV, sarsasapogenin, caffeic acid, β-sitosterol and lupeol in roots and cladodes of ten Asparagus L. ssp. from North India - Pooja Mawal; Manish Kapoor; Saroj Kumar Pradhan; Jyoti Rani; Raghbir Chand Gupta (Natural Product Research, 2026)

Climate-resilient agri-food systems: analyzing yield trends and overcoming adoption barriers - Shubham Durgude; Raj Kumar Jat; Vijay Singh Meena; RK Sohane; RK Jha; Abhay Kumar; Ujjwal Kumar; Anjani Kumar; RN Singh; Dinesh Chand Meena; Suneel Kumar; Illathur R. Reddy; et al. (Environment, Development and Sustainability, 2026)

Retraction notice to “Almond shell-derived biochar decreased toxic metals bioavailability and uptake by tomato and enhanced the antioxidant system and microbial community” [Sci. Total Environ. 929 (2024) 172632] - Muhammad Imran Ghani; Mohammad Abass Ahanger; Tanveer Ali Sial; Sajjad Haider; Junaid Ali Siddique; Ruidong Fan; Yanjiang Liu; Esmat F. Ali; Manish Kumar; Xing Yang; Jörg Rinklebe; Xiaoyulong Chen; et al. (Science of The Total Environment, 2026)

Urban dimension of microplastics in municipal solid waste compost within an emerging eastern Indian city - Sibadutta Mohanty; Manish Kumar; Kushalindu Biswas; Arati Ray; Akshyurna Pattnaik; Chandrama Dipa; Sumit Saha (Water, Air, & Soil Pollution, 2026)

Proximity analysis of the impact of coal fire on surface urban heat Island in Jharia coal mining region of Eastern India - Wilson Kandulna; Manish Kumar Jain (Theoretical and Applied Climatology, 2026)

Beyond nutrition: a two-decade systematic review of the ethnopharmacological potential and therapeutic promise of Amaranthus sp. - Suman Dutta; Rohan Sarkar; Nabanita Saha; Manish Kumar Suthar; Sandeep Gawdiya; Malini Roy Choudhury; Sourav Garai; Debashis Paul; Sumanta Das (Phytochemistry Reviews, 2026)

Characteristic dissimilarities in the cloud base height over Indo-Gangetic plain airports during withdrawal phase of southwest monsoon - Krishna Kumar Shukla; Gajendra Kumar; Anoop Kumar Mishra; Sourav Adhikary; Neeti Singh; Manish R. Ranalkar; Radheshyam Sharma; Manish Rai; Anand Shankar (Meteorology and Atmospheric Physics, 2026)

Seasonal variability and temperature-driven temporal dynamics of air pollutants in a mega coal mining zone of the talcher coalfield - Artatrana Mishra; Sarat Chandra Sahu; Manish Yadav; Nitin Kumar Singh; Charu Jhamaria; Amit Karmakar; Sumit Saha (Environmental Geochemistry and Health, 2026)

A novel automated technique based on ensemble learning for prediction of soil moisture using satellite images - Aryan Singh; Rohit Kumar Tiwari; Manish Pratap Singh; Sunil Jha (Advances in Space Research, 2026)

Life cycle assessment and carbon balance of eucalyptus and bamboo plantations in Semi-Arid, India - Manish Kumar; Rohith Ravula; G. Chandrashekar Reddy; Sreedhar Bodiga; Milkuri Chiranjeeva Reddy; Mhaiskar Priya Rajendra (Environmental Monitoring and Assessment, 2025)

Identification of long non-coding RNA from transcriptome data of leaf rust infected wheat (Triticum aestivum L.) and revealing their interaction with microRNAs and mRNAs - Moumita Roy Chowdhury; Dhananjay Kumar; Manish Kumar Pandey; Shailendra Kumar Jha; Manish Kumar; Kunal Mukhopadhyay (South African Journal of Botany, 2025)

Opportunities and perspectives for molecular composition-based utilization of edible rhizomes of the genus Curcuma L - Devi Datt Joshi; Lokesh Deb; Bharat G. Somkuwar; Virendra Singh Rana; Manish Kant Pant; Basant Kumar Singh; Ramesh C. Uniyal (South African Journal of Botany, 2025)

Current generation in microbial electrolysis cells based on an abiotic anode and planktonic Geobacter sulfurreducens in the presence of suspended reduced graphene oxide and activated carbon - Abhishiktha Chiliveru; Manish Kumar Yadav; James Ebenezer; Avinash Jukanti; Ester Bar Hanun; Arie Borenstein; Alex Schechter; Rivka Cahan (Journal of Environmental Chemical Engineering, 2025)

Production metrics of lemongrass essential oil under the combined influence of organics and silicon nanoparticles - Soumik Samanta; Kaushik Maity; Sangam Subba; Sujit Kumar Bhunia; Manish Kumar Naskar; Nilanjan Biswas; Apurba Bandyopadhyay; Amit Baran Sharangi (Biocatalysis and Agricultural Biotechnology, 2025)

High-throughput proteomic profiling reveals dysregulated serum proteins in low fertility bulls linked to nutrient-autophagy-inflammation-extracellular matrix axis - Anand Kumar Yadav; Arumugam Kumaresan; Kishan Kumar Fataniya; Manish Kumar Sinha; John Peter Ebenezer Samuel King; Ayyasamy Manimaran; Sakthivel Jeyakumar; Muniandy Sivaram; Gowdar Veerappa Vedamurthy; Dayal Nitai Das (Veterinary Research Communications, 2025)

Mulberry Silk Worm Pupae Oil and Prussian Blue Nanoparticle Enriched Multi-Faceted Polyvinyl Alcohol Nanofiber for Infectious Full Thickness Skin Wound Healing - Manish Kumar; Dilip Kumar Arya; Salem Salman Almujri; Kumarappan Chidambaram; Prashant Pandey; Anit Kumar; Giriraj Pandey; Akash Sharma; Mohini Chaurasiya; M. Arockia Babu; R. Venkatesh Kumar; Ravi Kr. Gupta; et al. (Tissue Engineering and Regenerative Medicine, 2025)

Nanoparticles: integrating sustainability for circular economy and eco-UN-SDGs through multidisciplinary synthesis - Manish Kumar Sah; Biraj Shah Thakuri; K. Rama Swami; Farhat Anwar; Khaled Edbey; Ashraf El-Hashani; Rehab Gaber Ismael; Ramesh L. Gardas; Ajaya Bhattarai (Nanotechnology for Environmental Engineering, 2025)

Investigating postbiotics as innovative adjuvants: deciphering the gut-breast connection in breast Cancer therapy, from gut microbiome to personalized medicine - Rashmi Ghosh; Debayan Sil; Rohit Sharma; Dinesh Kumar; Kumari Komal; Sourabh Kumar; Hitendra S Mahajan; Manu Sharma; Manish Kumar (Molecular Biology Reports, 2025)

Therapeutical potential of natural products in treatment of pancreatic cancer: a review - Sanjeev Kumar Sahu; Pranav Kumar Prabhakar; Manish Vyas (Molecular Biology Reports, 2025)

A pentatricopeptide repeat protein restores fertility in Moricandia arvensis based cytoplasmic male sterility system in Brassica juncea - Deepak Singh Bisht; Nitin Kumar; Anshul Watts; Rohit Chamola; Vajinder Kumar; Priyanka Jain; Manish Kumar; Balwant Singh Adhikari; Siddanna Savadi; Shripad Ramachandra Bhat (Molecular Genetics and Genomics, 2025)

Unlocking genetic hotspots: GWAS reveals key nitrogen responsive genomic regions and key genes for root and yield traits in indica rice - Ankur Poudel; Sachin Phogat; Jeet Roy; Manish Ranjan Saini; K. M. Shivaprasad; Jayanthi Madhavan; Viswanathan Chinnusamy; K. K. Vinod; Amitha Mithra Sevanthi; Pranab Kumar Mandal (Molecular Genetics and Genomics, 2025)

Formulation Development, Box-Behnken Design-Based Optimization and Evaluation of Cisplatin-Loaded Chitosan Nanoparticles Embedded in Mucoadhesive Buccal Film for Targeted Oral Cancer Therapy - Md Moidul Islam; Manish Kumar; Md Ali Mujtaba; Gamal Osman Elhassan; Siham Abdoun; Md Misbah; Ameeduzzafar Zafar; Mohammad Khalid (Journal of Pharmaceutical Innovation, 2025)

Comprehensive Image Analysis of Seed and Plant for Classification of Cotton Genotypes Using Deep Learning Methodologies - Anirban Jyoti Hati; Debashis Paul; Yogesh Shejwal; V. Santhy; Jayaraj U. Kidav; Y. G. Prasad; Ashish Kumar Singh; Ramesh Kumar; Manish Singla (Journal of Crop Health, 2025)

ANN–RSM Synergistic Optimization for CRDI Engine Performance and Emissions Using Novel Waste-Based Biodiesel–Ethanol–Diesel Ternary Blends - Manish Kumar; Naushad Ahmad Ansari; Raghvendra Gautam (International Journal of Environmental Research, 2025)

Advancing vegetable genetics with gene editing: a pathway to food security and nutritional resilience in climate-shifted environments - Rajib Roychowdhury; Soumya Prakash Das; Siddhartha Das; Sabarni Biswas; Manish Kumar Patel; Ajay Kumar; Umakanta Sarker; Sikander Pal Choudhary; Ranjan Das; Kalenahalli Yogendra; Sunil S Gangurde (Functional & Integrative Genomics, 2025)

Elucidating circRNA-miRNA-mRNA competing endogenous regulatory RNA network during leaf rust pathogenesis in wheat (Triticum aestivum L.) - Umang Kumar Dhandhanya; Uzma Afreen; Shailendra Kumar Jha; Kunal Mukhopadhyay; Manish Kumar (Functional & Integrative Genomics, 2025)

Analytical study of multi-layer one-dimensional spatially dependent solute transport modeling - Pallawi Bharti; Manish Kumar; Mritunjay Kumar Singh; Manish Chaudhary (Environmental Fluid Mechanics, 2025)

Tissue culture optimization and genome editing for yield improvement of an Indian rice landrace Chittimuthyalu - Faisal Yousuf; Manish Solanki; Surya Satyanarayana Singh; Suvarna Rani Ch; C. N. Neeraja; R. M. Sundaram; Satendra Kumar Mangrauthia (Transgenic Research, 2025)

Emerging approaches on biomass and water-based hydrogen production and downstream recovery pathways: a review on recent challenges and prospects - Ramesh Kumar; Prasenjit Chakraborty; Prashant Kumar Singh; Sankha Chakrabortty; Suraj K. Tripathy; Ganesh Dattatraya Saratale; Manish Kumar; Alak Kumar Ghosh; Byong-Hun Jeon (Reviews in Environmental Science and Bio/Technology, 2025)

Soil Moisture Prediction Using Artificial Neural Networks and Remote Sensing Data - Aryan Singh; Avdhesh Kumar; Ankit Singh; Rohit Kumar Tiwari; Navin Chaurasiya; Adarsh Singh; Shashank Shekhar Singh; Manish Pratap Singh (Remote Sensing in Earth Systems Sciences, 2025)

Postpartum hypernatremic osmotic demyelination syndrome - Farsana Mustafa; Navneeta Menoki; Suraj Patre; Ajay Garg; Divyani Garg; Manish Soneja; Naval K. Vikram; Achal Kumar Srivastava; Ayush Agarwal (Acta Neurologica Belgica, 2025)

Microalgae as an emerging alternative raw material of docosahexaenoic acid and eicosapentaenoic acid – a review - Tanishka Sharma; Nisha Das; Preeti Mehta Kakkar; Ranjan Kumar Mohapatra; Sudheer Pamidimarri; Ravi Kant Singh; Manish Kumar; Abhishek Guldhe; Manoranjan Nayak (Critical Reviews in Food Science and Nutrition, 2025)

A comprehensive safety assessment of algae protein from Picochlorum for human consumption - Manish R. Shukla; Tomal Dattaroy; Ashish Waghmare; Bhaskar Bhadra; Chitranshu Kumar; Debanjan Sanyal; Jayesh Sakariya; Kshipra Gautam; Mahadev S. Gaikwad; Manish Shukla; Meenakshi Chelliah; Meghna Rajvanshi; et al. (Regulatory Toxicology and Pharmacology, 2025)

A dive into plant SNAREs: Gatekeepers of plant immunity and pathogen defence - Payal Gaggar; Umang Kumar Dhandhanya; Manish Kumar; Kunal Mukhopadhyay (Physiological and Molecular Plant Pathology, 2025)

Corrigendum to “Interaction of cesium compounds with abundant inorganic compounds of atmosphere: Effect on cloud formation potential and settling” [J Hazard Mater, 488 (2025) 137248] - Gaurav Mishra; Manish Kumar; S.N. Tripathi; Manish Joshi; Sidyant Kumar; T. Saud; Sudha Chauhan; Arshad Khan; B.K. Sapra (Journal of Hazardous Materials, 2025)

Distribution and ecological risk of iodinated and gadolinium-based contrast agents in an impacted basin of central Mexico - Jaime Dueñas-Moreno; Abrahan Mora; Cristina Moreau; Manish Kumar; Chongqing Wang; Frederic Coulon; Jürgen Mahlknecht (Environmental Research, 2025)

Synergetic catalysis methods for sustainable wastewater treatment - Manish Kumar; Abhishek Shukla; Neha Thakur; Rahul Vaish (Environmental Research, 2025)

Molecular markers for the identification of BNI capacity in chromosome addition lines and their use in marker-assisted breeding - Manish Kumar Vishwakarma; Uttam Kumar; Pradeep Kumar Bhati; Susanne Dreisigacker; Karthikeyan Thiyagarajan; Masahiro Kishii; Arun Kumar Joshi (Euphytica, 2025)

Optimization of performance and emissions of a diesel engine using acetylene-enriched waste cooking biodiesel - Suraj Bhan; Prem Shanker Yadav; Girish Gautam; Ragvendra Gautam; Saket Kumar; Manish Kumar (Clean Technologies and Environmental Policy, 2025)

Cystatin as a Potential Diagnostic Marker in Oral Submucous Fibrosis: A Subtractive Proteomics Approach - Prerna Srivastava; SaiTeja Dubbaka; Priya Shree; Arpita Rai; Manish Kumar (International Journal of Peptide Research and Therapeutics, 2025)

Seaweed extract: a potential modulator of productivity and bulb quality in onion (Allium cepa L.) - S Thirumalesh; Shailesh Kumar Singh; Priyanka Upadhyay; Manish Bakshi (The Nucleus, 2025)

Introducing Normalized Surface-adjusted Precipitation Index (NSPI) for regional drought assessment - Preeti Rajput; Manish Kumar Sinha; Nikhil Ghodichore; Ajay Kumar Garg; Mukesh Kumar Verma (Science of The Total Environment, 2025)

Recent advances in covalent organic framework-based photocatalysts: From molecular design to hydrogen evolution - Umisha Kalia; Pooja Shandilya; Deepika Kaushal; Vinay Chauhan; Tabassum Nike; Manish Kumar (Journal of Environmental Chemical Engineering, 2025)

Ti₃C₂F₂ MXene disrupts microbial pathogenicity via hydrophobic-driven binding: Structural dynamics and energetics against bacterial and fungal targets - Satyam Tripathi; Manish Kumar; Aisha Tufail; Pratima Chauhan; Amit Dubey (Chemical Engineering Journal, 2025)

Freshwater microalgae-mediated engineered nanoparticles: Sustainable approach for heavy metals remediation - Manish Sutradhar; Raju Kumar Sharma; Gobinda Dey; Uttara Sukul; Koyeli Das; Md. Taharia; Pin-Yun Lin; Shafiqa Ali; Chin-Wen Wang; Chien-Yen Chen (Bioresource Technology, 2025)

Accessibility, detection, bioaccumulation, concentration and toxicity studies of antibiotics in fish - Chaitali Mallick; Amatha Sreedevi; Tapan Kumar Mukherjee; Deblina Pal; Rakesh Das; Sandip Mondal; Manish Gautam (Aquatic Toxicology, 2025)

Grain arsenic accumulation is independent of agronomic traits in rice under field conditions - Parminder Singh Saini; Manish Pandey; Samrath Baghel; Suraj Patil; Parmeshwar Kumar Sahu; Vinay Kumar; Bikram Kishore Das; Deepak Sharma; Ashish Kumar Srivastava (Physiology and Molecular Biology of Plants, 2025)
Arsenic (As) is a toxic environmental pollutant and a group-1 carcinogen, posing serious concern for human health. Rice and rice-based food products are considered as one of the major sources for As contamination into the human food-chain. Hence, world-wide concerted research efforts are going on, either to identify and/or develop low-As accumulating rice genotypes. The present study evaluated the natural accessions of rice, comprising of landraces and farmer’s varieties, under the naturally As-contaminated sites of Chhattisgarh, India, which is well-known for its richness in terms of rice production as well as varietal diversity. The wide-range spectrum of grain-As was obtained in 120 selected genotypes, with 90 and 81 accessions having As-accumulation above the WHO permissible limit for white (0.2 mg kg −1 ) and brown (0.3 mg kg −1 ) rice, respectively. The lowest grain-As accumulation among the varieties was seen in cultivated varieties (Badsabhog Sel 1 and Bahadur Sel 1) and landraces (Bastul and Kanaklata), which can be either cultivated or used as suitable donor in breeding programs. Among different agronomic traits, the plant height was identified as most-responsive parameter for assessing As-toxicity. The comparative assessment of agro-morphological traits although showed variations under naturally As-contaminated site; however, no significant correlation was seen in terms of grain-As accumulation, indicating the complexity for on-site field screening of low As-accumulating genotypes. Taken together, the results identified the potential low-As accumulating genotypes and highlighted the grain-As accumulation, as a complex multi-genic trait.

Growing Indica and Aus Type Rice Till Maturity in Hydroponics Under N-Optimum and N-Stressed Condition: A Detailed Account - Ankur Poudel; Manish Ranjan Saini; Sachin Phogat; Jeet Roy; Harsh Chauhan; Jayanthi Madhavan; Amitha Mithra Sevanthi; Pranab Kumar Mandal (Journal of Plant Growth Regulation, 2025)

Evaluation of Agromorphological and Yield Traits in Strawberry (Fragaria X ananassa Duch.) Genotypes Under Hydroponic Cultivation - Pallvi Verma; Shailesh Kumar Singh; Priyanka Upadhyay; Sanjay Singh; Manish Bakshi (Applied Fruit Science, 2025)

Integrated assessment of water quality, health risks, and corrosion potential in Mayurbhanja district of Odisha, India: Implications for sustainable water management - Subrat Swain; Tejaswini Sahoo; Jagannath Panda; Sunil Kumar Sahoo; Manish Maurya; Swasti Padma Panda; Niharika Das; Abinash Sahu; Rojalin Sahu (Total Environment Advances, 2025)

Sustainable no–tillage practices with a disc type novel residue cleaning mechanism: Design, development and field evaluation - Manish Kumar; Kamendra; H.S. Pandey; K.P. Singh; Chetna Verma; Satish Kumar Singh; Dushyant Singh (Soil and Tillage Research, 2025)

Nafithromycin: a potential ketolide antibiotic for combating antimicrobial resistance in community-acquired bacterial pneumonia - Dinesh Kumar; Debayan Sil; Rashmi Ghosh; Kumari Komal; Prachi Pandey; Ghanshyam Das Gupta; Manish Kumar (Next Research, 2025)

Forecasting of the household cooking energy demand pattern and emission scenario in Nepal - Durga Prasad Chapagai; Neeta Dhusia Sharma; Manish Kumar Roy; Amit Kumar Roy (Next Research, 2025)

Dietary ethanolic ashwagandha root extract augments growth performance and insulin growth factor-1 expression of rohu, Labeo rohita fingerlings raised at low-temperature - Naveen S. Krishnamenan; Manish Jayant; Ashutosh D Deo; Tincy Varghese; Naseemashahul Shamna; Atshaya Sundararajan; Vasanthakumaran Kumar; Revathi Annadhurai (Next Research, 2025)

Propensity and repercussion of microplastics in the soil-water-urban continuum - Manish Kumar; Priyansha Gupta; Shiwangi Dogra; Dibyendu Sarkar; Abrahan Mora; Nancy Ornelas-Soto; Jürgen Mahlknecht (Journal of Contaminant Hydrology, 2025)

Weathering in the subsurface environment of the Gondwana deposits intensified by the cumulative impacts of mining and agriculture practices - Bhairo Prasad Ahirvar; Pallavi Das; Ramesh Kumar; Durga Prasad Panday; Nilotpal Das; Pankaj Kumar Srivastva; Manish Kumar (Journal of Contaminant Hydrology, 2025)

Is the River Ganga a gigantic contributor to microplastic contamination in the groundwater ecosystem under the aegis of climatic extremes? - Priyansha Gupta; Manish Kumar (Journal of Contaminant Hydrology, 2025)

Evaluation of multi-channel ceramic tubular membranes for high-salinity water desalination by vacuum membrane distillation - Rebecca Lee; N.M. Srivatsa Bettahalli; Marianne Pemberton; Edward Wazer; Benjamin Anacleto; Johann Schnittger; Marcus Weyd; Ingolf Voigt; Joachim Koschikowski; Manish Kumar; Jeffrey R. McCutcheon (Desalination, 2025)

Protein carbonylation reveals the molecular basis of cryoinjury in buffalo spermatozoa - S.K. Bhure; D.S. Kumara Wodeyar; Atul Kumar Sharma; Abhishek Kumar; Ajay Kumar; Manish Mahawar; S.K. Ghosh; G. Taru Sharma (Cryobiology, 2025)

Engineering single Pd atom in W18O49 nanowire for ultra-sensitive crop pest detection and remote data communication - Prem Kumar; Kanchan Swami; Nilakantha Tripathy; Rajashri R. Urkude; Ankita Dadhich; Parul Sharma; Manish Singh; Kesavan Subaharan; Abir De Sarkar; Vijayakumar Shanmugam (Chemical Engineering Journal, 2025)

Application of explainable artificial intelligence to decode water-induced soil erosion in Lidder watershed of the Greater Himalayas - Syed Irtiza Majid; Manish Kumar; Sourav Bhadwal (Stochastic Environmental Research and Risk Assessment, 2025)

A Comprehensive Analysis of Silvipastoral Potential in Indian Agroforestry Landscapes - Susmita Shil; Asha K. Raj; Ankita Bhardwaj; Umakanta Dash; Lalitkumar L. Maurya; M. N. Ashwath; Manish Kumar Mankur; Vijay Kumar (Small-scale Forestry, 2025)

Comprehensive insights into pancreatic cancer treatment approaches and cutting-edge nanocarrier solutions: from pathology to nanomedicine - Rohit Sharma; Sourabh Kumar; Kumari Komal; Rashmi Ghosh; Shubham Thakur; Ravi Raj Pal; Manish Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Calcium Dynamics in Strawberry (Fragaria x ananassa Duch.) Plant: from Soil to Fruit - Sudhanshu Singh; Akash Kumar; Niharika Thakur; Avantika Bisht; Anmol; Shailesh Kumar Singh; Manish Bakshi (Journal of Soil Science and Plant Nutrition, 2025)

Unlocking the molecular pathway of atopic dermatitis: journey so far and roads ahead - Sourabh Kumar; Rohit Sharma; Kumari Komal; Dinesh Kumar; Rashmi Ghosh; Manish Kumar (Inflammopharmacology, 2025)

Tracking Aonla rust: climate cues, cultivar resilience, and field-based management - Shubham Patel; Hemant Kumar Singh; Jitendra Kumar; Manish Kumar Maurya; Sushil Kumar Singh (Indian Phytopathology, 2025)

Pollution source tracing and health impact of PM10 elements using DN-PMF in sub-urban sites of the Indian Himalayan Region - Sakshi Gupta; Priyanka Srivastava; Jagdish Chandra Kuniyal; Renu Lata; Soumen Raul; Anit Dawar; Sheetal Chaudhary; Archana Bawari; Anil Singh Salal; Shilpa Thakur; Manish Naja; Abhijit Chatterjee; et al. (Environmental Geochemistry and Health, 2025)

Characterization and retrieval of snow grain size in the Bhilangana region of the Upper Himalayas using hyperspectral PRISMA data - Manish Rawat; Ashish Pandey; Dhananjay Paswan Das; Praveen Kumar Gupta (Applied Geomatics, 2025)

Synthesis and Characterization of Innovative Tetraazamacrocyclic Complexes of La(III) and their Antibacterial, Antifungal, Antioxidant and Antidiabetic Activity - Medha Babel; Jaswant Raj; Manish Kumar Yadav; Nighat Fahmi; Anita Kumari (Journal of Fluorescence, 2025)

Neuroprotective Activity of Eriodictyol Against Streptozotocin-Induced Diabetic Peripheral Neuropathy in Wistar Rats by Targeting Wnt/β-Catenin Pathway - Renu Malik; Balvinder Singh; Ajay Singh Kushwah; Manish Kumar (NeuroMolecular Medicine, 2025)

Molecular Subtyping and Classification of PIK3CA Mutations in Metastatic Breast Cancer - Amrit Kaur Kaler; Manish Jethani; Mandar Nadkarni; Yash Tiwarekar; Varsha Balaji; Tanmay Wairkar; Bijal Kulkarni; Nevitha Athikari; Shalaka Satpute; Ratika Agarwal; Shruthi Kumar; Vidhi Shah; et al. (Current Tissue Microenvironment Reports, 2025)

Vertical Distribution Profiling of E. coli and Salinity in Tokyo Coastal Waters Following Rainfall Events Under Various Tidal Conditions - Chomphunut Poopipattana; Manish Kumar; Hiroaki Furumai (Journal of Marine Science and Engineering, 2025)
Urban estuarine environments face increasing water safety risks due to microbial contamination from combined sewer overflows (CSOs), particularly during heavy rainfall events. In megacities like Tokyo, where waterfronts are widely used for recreation, such contamination poses significant public health risks. The challenge is compounded by the variability in both intensity and spatial distribution of rainfall across the catchment, combined with complex tidal dynamics making effective water quality management difficult. To address this challenge, we conducted a series of hydrodynamic–microbial fate simulations to examine the spatial and vertical behavior of Escherichia coli (E. coli) under different rainfall–tide conditions. Focusing on the Sumida River estuary, rainfall data from eight drainage areas were classified into six event types using cluster analysis. Two contrasting events were selected for detailed analysis: a light rainfall (G2, 15 mm over 13 h) and an intense event (G6, 272 mm over 34 h). Vertical water quality profiling was performed along an 8.5 km transect from the Kanda–Sumida River confluence to the Tokyo Bay Tunnel, illustrating E. coli and salinity. The results showed that the rainfall intensity and tidal phase at the event onset are critical in shaping both the magnitude and vertical distribution of microbial contamination. The intense event (G6) led to deep microbial intrusion (up to 6–7 m) and major salinity disruption, while the lighter event (G2) showed surface-layer confinement. Salinity gradients were more strongly affected during G6, indicating freshwater intrusion. Tidal phase also influenced transport: the flood-high condition retained E. coli, whereas ebb-low tides facilitated downstream flushing. These findings highlight the influence of rainfall intensity and tidal timing on microbial distribution and support the use of vertical profiling in estuarine water quality management. They also support the development of dynamic, event-based water quality risk assessment tools. With appropriate local calibration, the modeling framework is transferable to other urban estuarine systems to support proactive and adaptive water quality management.

Enhancing urban resilience against elevation-driven precipitation risks in Indian smart cities - Shekhar Singh; Vijay Jain; Manish Kumar Goyal (Urban Climate, 2025)

Land use alters the alignment of Arsenic and Chromium co-contamination in the unconsolidated aquifer under reducing environments of the Mid-Gangetic Plains - Aseem Saxena; Manish Kumar; Rajesh Singh; Kanchan D. Bahukhandi (Science of The Total Environment, 2025)

Paleo-productivity reconstruction in Bay of Bengal during the past 1.3 Ma: Implications for glacial-interglacial dynamics and southern hemispheric processes - Barnita Banerjee; Monalisa Mallick; Vikash Kumar; E.V.S.S.K. Babu; Ozelim Luan; G. Balu; T. Vijaya Kumar; Nihar Ranjan Kar; Tanveer Hassan; Manish Tiwari; Thamizharasan Sakthivel; Prosenjit Ghosh; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Isomers of perfluorooctanesulfonate exhibit preferential infiltration and contrasting ionic associations between surface water and groundwater - Vivek Agarwal; Manish Kumar; Kanika Dogra; Sandra Mejia-Avendaño (Journal of Hazardous Materials, 2025)

Unlocking sustainability: Integrating omics for advanced wastewater treatment - Manish Kumar; Shiwangi Dogra; Nilotpal Das; Siddhant Dash; Ashutosh Sharma; Aurea Karina Ramírez Jiménez; Alfredo Díaz Lara; Shane A. Snyder; Futoshi Kurisu (Journal of Environmental Chemical Engineering, 2025)

Crop yield and resource use efficiency as influenced by crop establishment and conservation tillage in the rice-wheat cropping system - Bharat Bhushan Vashisht; Bijesh Maharjan; Sandeep Sharma; Arham Tater; Manish Yadav; Samanpreet Kaur; Surinder Kumar Jalota (Field Crops Research, 2025)

Protecting wetlands for future generations: A comprehensive approach to the water-climate-society nexus in South Asia - Shivukumar Rakkasagi; Manish Kumar Goyal (Environmental Impact Assessment Review, 2025)

Understanding the pathways, pollution and potential solutions pertaining to pesticides: Circular engineering for persistent chemicals - Manish Kumar; Siddhant Dash; Jürgen Mahlknecht; Alan Kolok; Shiwangi Dogra; Keisuke Kuroda; Tomohiro Tobino; Abrahan Mora; Absar Ahmad Kazmi; Rajesh Singh; Pravin Kumar Mutiyar; Rajesh Roshan Dash; et al. (Current Opinion in Environmental Science & Health, 2025)

Sericin and Xanthan gum-based biopolymer films with enhanced stretchability and cell-proliferation capability - Saurav Kumar; Saikat Biswas; Prasanna Kumar Byram; Pravin Vasudeo Vaidya; Santanu Dhara; Nishant Chakravorty; Manish Kaushal (Carbohydrate Polymers, 2025)

Morphometric Analysis for Prioritizing Erosion-Prone Watersheds in Manjeera Using Multi-Criteria Decision-Making Techniques - Shravan Kumar S. M.; Manish Pandey; N. V. Umamahesh (Water Conservation Science and Engineering, 2025)

Identification and assessment of potentially dangerous glacial lakes in Uttarakhand, India - Megha Raut; Santosh Pant; Pankaj Kunmar; Manish Mehta; Suraj Kumar Singh (Natural Hazards, 2025)

Rhizofiltration of Caesium and Strontium Through the Use of Aquatic Plants Eichhornea crassipes (Mart.) Solms and Monochoria hastata (L.) Solms-Laub - Brundaban Sarojini Manisha Singh; Nabin Kumar Dhal; Manish Kumar; Dinakrushna Mohapatra; Hariharan Seshadri; Krishan Kumar; Dharitri Mishra (International Journal of Environmental Research, 2025)

Comprehensive validation of bactericidal efficacy of umbelliferone against multidrug-resistant pathogens through multifaceted antimicrobial assays - Neetesh Mandal; Gulshan Sen; Abhishek Pathak; Kuldeep Gauliya; Manish Kumar Manjhi; Devanshi Chandel Upadhyay; Mohammed Latif Khan; Chandrama Prakash Upadhyay (Archives of Microbiology, 2025)

Biodiversity of predaceous Ladybird beetles (Coleoptera: Coccinellidae) in jackfruit ecosystem from the Gangetic Alluvial Zone of West Bengal, India - Tamoghno Majumder; Manish Kumar Naskar; Aloy Adak; Kusal Roy (International Journal of Tropical Insect Science, 2025)

Integrated mineral identification of PM10 using XRD, ATR-FTIR and SEM–EDX techniques in Indo-Gangetic Plain (IGP) and Indo-Himalayan Region (IHR) - Preeti Tiwari; Sakshi Gupta; Shobhna Shankar; Priyanka Srivastava; Bharat Ji Mehrotra; Manoj K. Srivastava; Manish Naja; Ranu Gadi; Manoj Kumar; Anit Dawar; Sudhir Kumar Sharma (Environmental Monitoring and Assessment, 2025)

Water policy review: Ensuring sustainable water management for India - Sachidanand Kumar; Manish Kumar Goyal (Journal of Environmental Management, 2025)

First evidence of microplastics in surface water of urban waterbodies in Bhopal city, India- abundance and their characteristics - Dinesh Kumar Gupta; Abhishek Giri; Diksha Choudhary; Amit Vishwakarma; Manish Mudgal; Pankaj Raizada; Pardeep Singh; Archana Singh (Journal of Contaminant Hydrology, 2025)

Retraction notice to “Enhancement of combustion characteristics of waste cooking oil biodiesel using TiO2 nanofluid blends through RSM” [Fuel 331(Part 1) (2023) 125681] - Harveer Singh Pali; Abhishek Sharma; Manish Kumar; Vivek Anand Annakodi; Van Nhanh Nguyen; Nishant Kumar Singh; Yashvir Singh; Dhinesh Balasubramanian; Balakrishnan Deepanraj; Thanh Hai Truong; Phuoc Quy Phong Nguyen (Fuel, 2025)

Modeling and experimental investigation of factors responsible for maximizing the betanin concentration by spiral-wound FO module using Na2SO4-based draw solution - Ketan Mahawer; Ashwani Kumar Tiwari; Abeer Mutto; Manish Jain (Food and Bioproducts Processing, 2025)

Nanocellulose supported ZnWO4/SrTiO3/MoO3 heterojunction: Highly efficient visible light photocatalyst for ciprofloxacin degradation - Shabnam Sambyal; Rohit Sharma; Aashish Priye; Manish Kumar; Vinay Chauhan; Pooja Shandilya (Chemical Engineering Journal, 2025)

Structural and functional insights from molecular modeling, docking, and MD simulations of bacterial xylanase: implications for biofuel efficiency - Arpita Sarangi; Sandesh Behera; Manish Paul; Sumanta Kumar Sahu; Rakesh kumar; Hrudayanath Thatoi (Systems Microbiology and Biomanufacturing, 2025)

Evolutionary Triggers of Plant Speciation in the Himalaya‐Tibet‐Hengduan Biodiversity Epicentre - Maharaj K. Pandit; Kumar Manish; Sandeep Sen; Kamaljit S. Bawa; Andrew H. Knoll; A. Alexander G. Webb; Peter D. Clift; Fabien L. Condamine; Carina Hoorn (Journal of Biogeography, 2025)
Background Past studies linking geologic and climatic controls on speciation in the Himalaya, Tibet and Hengduan (HTH) regions do not fully capture the mechanisms underlying patterns of plant diversity and endemism in hyperdiverse mountain ecosystems. Aims This study sheds new light on the orogenic and climatic drivers of plant endemism and diversity in the HTH region and unravels the mechanisms behind plant speciation and assembly. Materials & Methods We re‐examine the past findings on geo‐climatic controls on speciation in the HTH. We also analyse new datasets on the elevational patterns of endemic species richness in the HTH regions and correlate these with the hypsometric profiles based on digital elevation models of these regions. Results We discover that the phased evolution of HTH mountain‐building and climate oscillations, and species radiations were not exactly synchronous, but were interspersed with periods of inactivity. We find an inverse yet overlapping relationship between elevation‐area troughs (EATs) of hypsometric profiles and peaks of endemic plant richness in the HTH, indicating that most endemic species occupy the higher elevational belts with the least geographic areas. These elevational belts comprise geographically and biologically isolated habitats. Discussion and Conclusions We infer that orogeny, monsoon and glaciations have shaped the highly dissected HTH landscapes, characterised by high‐relief topography, leading to population isolation, speciation and endemism, albeit with temporal lags. Glacial–interglacial cycles have further promoted isolation, co‐habitation, hybridisation and polyploidy among plant populations, generating and accelerating endemic radiations. Our results provide crucial evidence linking mountain‐building, climatic events and landform development with plant species richness and endemism in the HTH regions and potentially in other mountain ecosystems.

Fluorosis among wild fauna of India: assessing toxicity and its effects on the ecosystem - Shruti Shaurya; Debabrata Mondal; Manish Kumar; Rashmi Rekha Kumari; Prabhakar Sharma; Anup Das; Pankaj Kumar (Environmental Monitoring and Assessment, 2025)

Unveiling the physicochemical and electrochemical features of sodium deficient-Na0.8Fe(SO4)2 as cathode for sodium-ion batteries - Jena Akash Kumar Satrughna; Archana R. Kanwade; Shraddha M. Rajore; Manish Kumar Tiwari; Yuta Ito; Atsushi Ogura; Hyunju Lee; Yoshio Ohshita; Sawanta S. Mali; Jyoti V. Patil; Chang Kook Hong; Parasharam M. Shirage (Next Research, 2025)

Evaluation of some plant products against Trogoderma granarium everts and Rhyzopertha dominica fabricius in pearl millet and their effects on nutritional composition and organoleptic characteristics - Sudhir Dayal Yadav; Shalini Pandey; Ankur Tripathi; Mujahid Khan; Prashant Sahni; Rahul Bhardwaj; Manish Kumar; Ram Singh (Journal of Stored Products Research, 2025)

Seasonality in negative removal of pharmaceutical and personal care products at the Himalayan foothills wastewater treatment plants - Rahul Silori; Durga Madhab Mahapatra; Syed Mohammad Tauseef; Pinakshi Biswas; Bhanu Prakash Vellanki; Ritusmita Goswami; Mats Leifels; Abrahan Mora; Jürgen Mahlknecht; Manish Kumar (Journal of Environmental Chemical Engineering, 2025)

Dual-action photocatalyst: MnO2/CuO decorated 3D porous carbonaceous matrix as reusable photocatalyst for rapid removal of industrial dyes and antibiotics from contaminated-water - Mansi Pahuja; Sree Vishnu; Indranil De; M.V. Jyothirmai; Soumyadip Sharangi; Seema Rani; Jyoti; Subhabrata Das; E.M. Harini; Mohd Afshan; Rajashri Urkude; Daya Rani; et al. (Journal of Environmental Chemical Engineering, 2025)

Novel Hall voltage-assisted enhanced ammonia sensing properties of polyaniline/zinc ferrite composite-based sensor - Mainak Swarnakar; Partha Sarathi Mandal; Mohd Ali; Chandra Shekhar Pati Tripathi; Suchandra Mukherjee; Aritra Banerjee; Sanat Kumar Adhikari; Souvik Chatterjee; Manish Pal Chowdhury (Journal of Environmental Chemical Engineering, 2025)

Green revolution to clinical burden: Connecting the dots between pesticide consumption and cancer incidents in India - Siddhant Dash; Priyansha Gupta; Manish Kumar (Current Opinion in Environmental Science & Health, 2025)

A novel framework for wetland health assessment using hydro-ecological indicators and landscape metrics - Manish Rawat; Ashish Pandey; Praveen Kumar Gupta; Basant Yadav; J. G. Patel (Modeling Earth Systems and Environment, 2025)

Sources, distribution and migration of micro-nano-plastics from terrestrial to aquatic environments and its environmental and health impacts: a systematic review - Manish Kumar; Kancheti Mrunalini; Zhuoqing Zhou; Rajesh U. Modi; Shiv Bolan; Ch Srinivasa Rao; Melanie Braun; Olivia Wrigley; Yang Li; Liuwei Wang; Alessandra Leri; Renu Dhupper; et al. (Journal of Soils and Sediments, 2025)

Fostering Nutritional Equity: Biofortification Strategies, Socioeconomic Implications, and Regulatory Policies for Developing Biofortified Staple Crop - Kuldeep Gauliya; Abhishek Pathak; Neetesh Mandal; Manish Kumar Manjhi; Devanshi Chandel Upadhyaya; Aman Raj; Chandrama Prakash Upadhyaya (Journal of Soil Science and Plant Nutrition, 2025)

Characterization of unique Himalayan rice germplasm: DUS evaluation, morphological profiling, and molecular fingerprinting - Vinaykumar Rachappanavar; Jatinder Kumar Sharma; Manish Kumar Sharma (Journal of Crop Science and Biotechnology, 2025)

A novel approach to analyzing the 3D slope of Mount St. Helens via soft computing techniques - Sumit Kumar; Divesh Ranjan Kumar; Manish Kumar; Warit Wipulanusat; Manop Kaewmoracharoen (Earth Science Informatics, 2025)

Exploring the utilization potential of Lantana camara: particleboard and briquette development - V. R. Ramkumar; K. Thanigai; Ritesh Kumar; G. Murali; V. Prakash; Veer Singh Gautam; Manish Ranjan; Narasimha Murthy (Journal of the Indian Academy of Wood Science, 2025)

A mini-review on heavy metals accumulation in seaweed of India: prospects for phyco-remediation - Dharitri Mishra; Suman Patra; S. Dinesh Kumar; Manish Kumar; R Sathish; Nabin Kumar Dhal (Environmental Monitoring and Assessment, 2025)

Alkalinity-salinity-sustainability: Decadal groundwater trends and its impact on agricultural water quality in the Indian Peninsula - Durga Prasad Panday; Aanchal Kumari; Manish Kumar (Science of The Total Environment, 2025)

Beyond DNA interactions: Insights into idarubicin's binding dynamics with tRNA using spectroscopic and computational approaches - Sonika Charak; Chandra Mohan Srivastava; Dhruv Kumar; Lovika Mittal; Shailendra Asthana; Ranjana Mehrotra; Manish Shandilya (Journal of Photochemistry and Photobiology B: Biology, 2025)

Interaction of cesium compounds with abundant inorganic compounds of atmosphere: Effect on cloud formation potential and settling - Gaurav Mishra; Manish Kumar; S.N. Tripathi; Manish Joshi; Sidyant Kumar; T. Saud; Sudha Chauhan; Arshad Khan; B.K. Sapra (Journal of Hazardous Materials, 2025)

HR-MS-based bioactive profiling of green Banana flour and millets-based Murukku snack - Tomaly Saha; Manish Kumar Singh; Dinesh Chandra Rai; Arvind Kumar (Food and Humanity, 2025)

Synthesis and studies of advanced adsorbent zeolites by using red mud and rice husk ash as a thermal insulation agent - Kamna Chaturvedi; Manish Dhangar; Medha Mili; Avanish Kumar Srivastava; Sarika Verma (Arabian Journal of Geosciences, 2025)

Impact of post-anthropogenic forest fire on soil carbon dynamics and physicochemical properties in tropical dry deciduous Sulia Reserve Forest, Odisha - Sudipta Nayak; Manish Kumar; Nabin Kumar Dhal (Environmental Monitoring and Assessment, 2025)

Assessment and estimation of runoff and soil loss using novel machine learning techniques for conservation bench terraces - Ambrish Kumar; Manish Kumar; Narinder Kumar Sharma; Bihari Lal Dhyani; Uday Mandal (Science of The Total Environment, 2025)

Relationship between daily precipitation extremes and temperature in changing climate across smart cities of Central India - Vijay Jain; Sachidanand Kumar; Manish Kumar Goyal (Journal of Environmental Management, 2025)

Antimicrobial peptides in Clarias batrachus epidermal mucus: Characterization and therapeutic potential - Ahmed Hussain; Manish Kumar; Kunal Mukhopadhyay; Abhijit Dutta; Shashwati Ghosh Sachan (Fish & Shellfish Immunology, 2025)

Role of transpiration in modulating ecosystem services in secondary tropical montane forests of Eastern Himalaya in India - Manish Kumar; Yangchenla Bhutia; Girish R Varma; Gladwin Joseph; Jagdish Krishnaswamy (Ecohydrology & Hydrobiology, 2025)

Thiourea Mitigates Potassium Deficiency in Soybean Varieties Through Redox or ABA Dependent Mechanisms - Sripati Abhiram Sahoo; Reema Devi Singh; Jayant Kulkarni; Granthali Sanket Kamble; Manish Pandey; Satish Balkrishna Verulkar; Ashish Kumar Srivastava (Journal of Plant Growth Regulation, 2025)

Impact of Biochar and Water Regimes on Arsenic Transfer and Uptake in Rice: Insights into Transporter Behaviour and Soil–Plant Dynamics - Rubina Khanam; Lipsa Tripathy; Parameswaran Chidambaranathan; Pedda Ghouse Peera Sheikh Kulsum; Jajati Mandal; Mohammad Shahid; Manish Debnath; Raj Kishore Sahoo; Sushmita Munda; Sanghamitra Samantray; Amaresh Kumar Nayak (Exposure and Health, 2025)

Identification and molecular characterization of flavonoid biosynthetic genes and their expression analysis in wheatgrass (Triticum aestivum L.) during leaf rust infection - Maria Adhikary; Prashanta Kumar Deb; Biswatrish Sarkar; Shailendra Kumar Jha; Manish Kumar; Kunal Mukhopadhyay (Acta Physiologiae Plantarum, 2025)

A Phase II/III multicenter randomized single blind non-inferiority immunogenicity and safety study of TeddyVac™ vaccine of Human Biologicals Institute in healthy subjects of 10 years to 60 years of age - Sai Krishna Susarla; Manish Narang; Prashant Namdev Khandgave; Lipilekha Patnaik; Vasudev Rajapantula; Satish M; Rajashakar BC; Devi Prasad Sahoo; Anand Kumar Kanakasapapathy (Infectious Diseases, 2025)

Nanotechnology and artificial intelligence in cancer treatment - Yashdeep Mukheja; Kashish Pal; Akanksha Ahuja; Ankan Sarkar; Bhavneesh Kumar; Anurag Kuhad; Kanwaljit Chopra; Manish Jain (Next Research, 2025)

Optimizing whole grain rice fortification using microwave-assisted screw conveying spraying and drying setup: Exploring solution absorption, gelatinization, and micronutrient retention - Ankanksha Kumari; Ujala Ahuja; Manish Kumar Pandey; Anupam Roy (Food Chemistry, 2025)

Assessing soybean yield in Madhya Pradesh by using a multi-model approach - Raghavendra Nargund; Kuldeep Singh Rautela; Manish Kumar Goyal; Nishant K. Sinha; Monoranjan Mohanty; Virender Singh Bhatia (Field Crops Research, 2025)

Integrating evolving energy economy scenarios in dynamic life cycle assessment of buildings - Sejal Sanjay Shanbhag; Manish Kumar Dixit (Environmental Impact Assessment Review, 2025)

Advancing against drug-resistant tuberculosis: an extensive review, novel strategies and patent landscape - Meghana N. Patel; Archita J. Patel; Manish N. Nandpal; Manan A. Raval; Ravish J. Patel; Amit A. Patel; Keshav Raj Paudel; Philip M. Hansbro; Sachin Kumar Singh; Gaurav Gupta; Kamal Dua; Samir G. Patel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Modulating Productivity of Strawberries (Fragaria x ananassa Duch.) Through Artificial Full-Spectrum Light in Indoor Vertical Farming - Pallvi Verma; Gurpreet Singh; Shailesh Kumar Singh; Anis Ahmad Mirza; Manish Bakshi; Anmol; Lakshya; Lokesh Kumar; Rupesh (Journal of Soil Science and Plant Nutrition, 2025)

Nanostructured lipid carriers in Rheumatoid Arthritis: treatment, advancements and applications - Swarnika Sharma; Rashmi Ghosh; Arockia Babu Marianesan; Sumaya Hussain; Jai Deo Pandey; Manish Kumar (Inflammopharmacology, 2025)

Phase equilibria modelling, fluid inclusion study, and U-Pb zircon dating of ultra-high temperature mafic granulites from Rampur domain, Eastern Ghats province: implications for the Indo-Antarctic correlation - Divya Prakash; Rajeev Kumar Pandey; Saurabh Singh; Chandra Kant Singh; Manish Kumar; Bikash Mahanta; Aditya Kharya; Himanshu K. Sachan; Kamesh Sharma (Contributions to Mineralogy and Petrology, 2025)

Afobazole: a potential drug candidate which can inhibit SARS CoV-2 and mimicry of the human respiratory pacemaker protein - Govinda Rao Dabburu; Anjali Garg; Neelja Singhal; Manish Kumar (In Silico Pharmacology, 2025)

Glacial landforms and geometric transformations: tracing the history of Pensilungpa and Durung-Drung glaciers in Suru and Doda River valleys, Western Himalaya, Ladakh - Pankaj Kunmar; Ajay Singh Rana; Vinit Kumar; Manish Mehta; H. C. Nainwal (Environmental Monitoring and Assessment, 2025)

Cluster analysis of geophysical data for geology differentiation in Agnigundala mineralized belt of Cuddapah Basin, India - D Vijayakumar; G Srinivasa Rao; W Dinesh Singh; Manish Kumar; S K Pal (Journal of Earth System Science, 2025)

Microbial drivers of biogeochemical cycles in deep sediments of the Kathiawar Peninsula Gulfs of India - Chandrashekar Mootapally; Parth Sharma; Siddhant Dash; Manish Kumar; Shiksha Sharma; Ramesh Kothari; Neelam Nathani (Science of The Total Environment, 2025)

Evaluation of soil heavy metals in Raniganj open-cast coal mines in India: Spatial distribution, Positive Matrix Factorization and Monte Carlo Simulation - Silvia Dutta; Manish Kumar Jain; Dheeraj Kumar (Process Safety and Environmental Protection, 2025)

Tectonically deformed coal: Focus on microstructures & implications for basin evolution - Manish Kumar Srivastava; Kaushal Kishor; Alok K. Singh; Soumyajit Mukherjee; Shivranjan Kumar Bharti (Marine and Petroleum Geology, 2025)

Petrophysical Characterization of Metamorphic Rocks using X-ray Micro-CT data – Implications for fluid flow - Ritwik Chakraborty; Michael Späth; Akash Kumar; Benjamin Busch; Britta Nestler; Manish A. Mamtani; Christoph Hilgers (Journal of Structural Geology, 2025)

The nexus of microplastics, food and antimicrobial resistance in the context of aquatic environment: Interdisciplinary linkages of pathways - Shiwangi Dogra; Manish Kumar; Jian Zang (Journal of Contaminant Hydrology, 2025)

Ultrahigh-temperature granulites from the Shillong-Meghalaya Gneissic Complex, NE India: Implications for the Indo-Antarctic Correlation - Bikash Mahanta; Divya Prakash; Manish Kumar; Saurabh Singh; Rajeev Kumar Pandey; Chandra Kant Singh; Roopali Yadav; Jesus Solé Vinas (Journal of Asian Earth Sciences, 2025)

Characterizing metabolome signature of colostrum, transition and mature milk of indigenous cows (Bos indicus) adapted to high altitude environment of Leh-Ladakh - Amarjeet; Umesh Kumar; Monika Sodhi; Dinesh Kumar; Prince Vivek; Saket K. Niranjan; Ranjit Singh Kataria; Sudarshan Kumar; Manish Sharma; Manish Tiwari; Rajeev A.K. Aggarwal; Vijay K. Bharti; et al. (Food Chemistry, 2025)

Methyl donor ameliorates CCl4-induced liver fibrosis by inhibiting inflammation, and fibrosis through the downregulation of EGFR and DNMT-1 expression - Manish Bishnolia; Poonam Yadav; Sumeet Kumar Singh; Nirmal Manhar; Sonu Rajput; Amit Khurana; Jasvinder Singh Bhatti; Umashanker Navik (Food and Chemical Toxicology, 2025)

Investigation of spatiotemporal changes of drought trend in Indian River Basin system over the century - Preeti Rajput; Mukesh Kumar Verma; Nikhil Ghodichore; Manish Kumar Sinha (Theoretical and Applied Climatology, 2025)

Neurons Specialize in Presynaptic Autophagy: A Perspective to Ameliorate Neurodegeneration - Abhishek Kumar Mishra; Manish Kumar Tripathi; Dipak Kumar; Satya Prakash Gupta (Molecular Neurobiology, 2025)

Integrating omics data for personalized medicine in treating psoriasis - Manish Ramchandani; Amit Kumar Goyal (Medicinal Chemistry Research, 2025)

Identification of novel microRNAs and their target genes associated with stress-tolerant phytohormones in wheat (Triticum aestivum L.) during leaf rust pathogenesis - Uzma Afreen; Kunal Mukhopadhyay; Manish Kumar (Journal of Plant Diseases and Protection, 2025)

Insights into Mechanisms, Responses, and Strategies for Alleviating Drought Stress in Rice: A Current Synopsis - Atreyee Chatterjee; Manish Kumar; Sharadindu Adak; Narottam Dey; Rup Kumar Kar (Journal of Crop Health, 2025)

Advancements in nose-to-brain drug targeting for Alzheimer’s disease: a review of nanocarriers and clinical insights - Kumari Komal; Rashmi Ghosh; Debayan Sil; Rohit Sharma; Sourabh Kumar; Prachi pandey; Manish Kumar (Inflammopharmacology, 2025)

HIV associated motor neuron disease (MND): A case series with systematic review of literature - Farsana Mustafa; Sapna Mittal; Divyani Garg; Ayush Agarwal; Ajay Garg; Baidnath Kumar Gupta; Manish Soneja; Achal Kumar Srivastava (Journal of NeuroVirology, 2025)

Dietary pineapple peel ethanolic extract alleviates crowding stress in Labeo rohita fingerlings with enhancement of growth performance and IGF-1 expression, physio-biochemical profile, antioxidant status and immunological responses - Soumyodeep Bhattacharya; Parimal Sardar; Narottam Prasad Sahu; Naseemashahul Shamna; Manish Jayant; Manas Kumar Maiti; Atshaya Sundararajan (Animal Feed Science and Technology, 2025)

Geo-electrical characterization and delineation of subsurface fractures to detect in-situ seepage in lake waters - Anil Kumar Misra; Rakesh Kr. Ranjan; Nishchal Wanjari; Swapan Dolui; Manish Kumar Keshare; Kuldeep Dutta; Bidyutjyoti Baruah (Arabian Journal of Geosciences, 2025)

Estimation of peak discharge and flood frequency in the Yamuna River Basin, India - Omvir Singh; Jyoti Sharma; Manish Kumar; Sachin Pandwar; Dinesh Kumar (Journal of Earth System Science, 2025)

Correction to: Retaliation of Alstonia scholaris (L.) R.Br. to caesium and strontium in hydroponics: effect on morpho‑physiology and induction of enzymatic defence - B. S. Manisha Singh; Nabin Kumar Dhal; Manish Kumar; Dinakrushna Mohapatra; Hariharan Seshadri; Monalisha Nayak (Environmental Monitoring and Assessment, 2025)

Poultry litter extract as solid waste supplement for enhanced microalgal biomass production and wastewater treatment - Shatakshi Kashyap; Nisha Das; Manish Kumar; Sanjeev Mishra; Shashi Kumar; Manoranjan Nayak (Environmental Science and Pollution Research, 2025)

Synthesis, retrieval, and industrial applications of magnetic nanoparticles in recent times - Arunima Singh; Manish Kumar Sinha; Snigdha Khuntia (Journal of Water Process Engineering, 2025)

Spatio-temporal analysis of extreme air pollution and risk assessment - Kuldeep Singh Rautela; Manish Kumar Goyal (Journal of Environmental Management, 2025)

Optimizing soil properties, water use efficiency, and crop yield through biochar and organic manure integration in organic soil - Peeyush Sharma; Vikas Abrol; Jasiya Nazir; R.K. Samnotra; Sushil Kumar Gupta; Shrdha Anand; Jayanta Kumar Biswas; Smriti Shukla; Manish Kumar (Journal of Environmental Management, 2025)

A decade of conservation agriculture in intensive cereal systems: Transitioning to soil resilience and stable yield trends in a climate crisis - Hanuman Sahay Jat; Shivani Khokhar; Kailash Prajapat; Madhu Choudhary; Manish Kakraliya; Manoj Kumar Gora; Mahesh Kumar Gathala; Parbodh Chander Sharma; Andrew McDonald; Jagdish K. Ladha; Mangi Lal Jat (Journal of Environmental Management, 2025)

Untapping the potential of algae for β-glucan production: A review of biological properties, strategies for enhanced production and future perspectives - Vijay Kumar; Manish S. Bhoyar; Chandra S. Mohanty; Puneet S. Chauhan; Kiran Toppo; Sachitra K. Ratha (Carbohydrate Polymers, 2025)

Role of AI&ML in Modernizing Water and Wastewater Treatment Processes - Rajneesh Kumar; Manish Kumar Goyal (Water, Air, & Soil Pollution, 2025)

Pyrene functionalized organic cation receptor-based “turn-on” fluorescence approach for monitoring of chlorpyrifos in food, soil, and water samples - Manish Kumar; Aman Dhiman; Gagandeep Singh; Navneet Kaur; Narinder Singh (Analytica Chimica Acta, 2025)

Health impacts, ozone and secondary organic aerosol formation potential of aromatic hydrocarbons (C6-C8) in the Central Himalayas and the Indo-Gangetic Plain - Mahendar Chand Rajwar; Manish Naja; Prajjwal Rawat; Sethuraman Venkataramani; Rakesh Kumar Tiwari (Environmental Science and Pollution Research, 2024)

Assessing tiger habitat suitability and population dynamics in panna tiger reserve with MCDA techniques - Pankaj Lavania; Manmohan Dobriyal; Manish Srivastav; A. K. Singh; K. K. Singh; Anjana Suchita Tirki; Uttam Kumar Sharma; Pavan Kumar (Environment, Development and Sustainability, 2024)

Manifestations of a glacier surge in central Himalaya using multi-temporal satellite data - Vinit Kumar; Ajay Singh Rana; Manish Mehta; Gautam Rawat (Environmental Science and Pollution Research, 2024)

Glacial interglacial variations in the natural iron fertilization during the low sea ice periods along the eastern continental margin of Antarctica - T. Sarathchandraprasad; Manish Tiwari; Vikash Kumar; Sharmila Sherin; M.G. Yadava (Science of The Total Environment, 2024)

Corroboration of arsenic variation over the Indian Peninsula through standardized precipitation evapotranspiration indices and groundwater level fluctuations: Water quantity indicators for water quality prediction - Durga Prasad Panday; Manish Kumar; Vivek Agarwal; Juan Antonio Torres-Martínez; Jürgen Mahlknecht (Science of The Total Environment, 2024)

Hydraulic recharge and element dynamics during salinization in an overexploited coastal aquifer of the world's driest zone: Atacama Desert - Janeth González-Domínguez; Abrahan Mora; Samuel Chucuya; Edwin Pino-Vargas; Juan Antonio Torres-Martínez; Jaime Dueñas-Moreno; Lia Ramos-Fernández; Manish Kumar; Jürgen Mahlknecht (Science of The Total Environment, 2024)

Spatio-temporal analysis of riverbank changes using remote sensing and geographic information system - S.M. Shravan Kumar; Manish Pandey; Anoop Kumar Shukla (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Pre-combustion mercury removal potential of rapid pyrolysis in high ash coal and mode of occurrence - Jyoti Kumari; Hridesh Agarwalla; Reginald E. Masto; Monalisa Gangopadhyay; Rabi Narayan Senapati; Manish Kumar (Fuel, 2024)

Real-time optimal hierarchy control of HVAC system with maximized ancillary service support in smart buildings: An experimental approach - Manish Kumar Yadav; Ashu Verma; B.K. Panigrahi; Dibakar Rakshit (Energy and Buildings, 2024)

Unlocking the potential of remote sensing for arsenic contamination detection and management: Challenges and perspectives - Vivek Agarwal; Manish Kumar; Durga Prasad Panday; Jian Zang; Francisco Munoz-Arriola (Current Opinion in Environmental Science & Health, 2024)

DNA methylation in wheat: current understanding and future potential for enhancing biotic and abiotic stress tolerance - Uzma Afreen; Kunal Mukhopadhyay; Manish Kumar (Physiology and Molecular Biology of Plants, 2024)

Harnessing the power of clustered regularly interspaced short palindromic repeats (CRISPR) based microfluidics for next-generation molecular diagnostics - Rasanpreet Kaur; Saurabh Gupta; Arjun Chauhan; Vidhi Mishra; Manish Kumar Sharma; Jitendra Singh (Molecular Biology Reports, 2024)

5-mC methylation study of sORFs in 3ˈUTR of transcription factor JUNGBRUNNEN 1-like during leaf rust pathogenesis in wheat - Uzma Afreen; Manish Kumar (Molecular Biology Reports, 2024)

Protective effect of Achyranthes aspera against compound 48/80, histamine and ovalbumin-induced allergic disorders in murine model - Amit Kaushik; Dewasya P. Singh; Mridula Sahu; Ashish Kumar; Pratibha; Pallavi Pandey; Manish K. Patel; Debabrata Chanda; Velusamy Sundaresan; Daya N. Mani; Ashutosh K. Shukla (Molecular Biology Reports, 2024)

An accretive detection method for in silico identification and validation of circular RNAs in wheat (Triticum aestivum L.) using RT-qPCR - Umang Kumar Dhandhanya; Kunal Mukhopadhyay; Manish Kumar (Molecular Biology Reports, 2024)

Infusing genetic variability for productivity and drought tolerance traits from Brassica carinata into Brassica juncea genotypes - Omkar Maharudra Limbalkar; Prashant Vasisth; Rajendra Singh; Mahesh Rao; Guman Singh; Lal Singh; Gokulan Dhanasekaran; Manish Kumar; Mohan Lal Meena; Nanjundan Joghee; Chiter Mal Parihar; Viswanathan Chinnusamy; et al. (Genetic Resources and Crop Evolution, 2024)

Experimental and computational evaluation of anti-malarial and antioxidant potential of transition metal (II) complexes with tridentate schiff base derived from pyrrolopyrimidine - Abhay D. Bagul; Manish Kumar; Amer M. Alanazi; Aisha Tufail; Nasir Tufail; Digamber D. Gaikwad; Amit Dubey (BioMetals, 2024)

The Neoteric Paradigm of Biomolecule-Functionalized Albumin-Based Targeted Cancer Therapeutics - Swati Gunjkar; Ujala Gupta; Rahul Nair; Priti Paul; Mayur Aalhate; Srushti Mahajan; Indrani Maji; Manish K. Chourasia; Santosh Kumar Guru; Pankaj Kumar Singh (AAPS PharmSciTech, 2024)

Advancing groundwater quality predictions: Machine learning challenges and solutions - Juan Antonio Torres-Martínez; Jürgen Mahlknecht; Manish Kumar; Frank J. Loge; Dugin Kaown (Science of The Total Environment, 2024)

First reporting of BA.1* and BA.2* recombinant SARS-CoV-2 lineage XAP from Indian wastewaters - Manish Kumar; Durga Madhab Mahapatra (Science of The Total Environment, 2024)

Rapid transfer of the leaf rust resistance gene Lr52 for the improvement of bread wheat cultivar HD3086 - Naman Raj; Hariom Shukla; Priyanka Agarwal; Ajay Kumar Chandra; Ramesh Bhurta; Subhash Bijarania; Manish Kumar Choudhary; Raghunandan K; Niharika Mallick; Niranjana M; Arun Kumar M. B; Lekshmy Sathee; et al. (Physiological and Molecular Plant Pathology, 2024)

Deciphering anhydrobiosis and plant parasitism of the wheat seed gall nematode, Anguina tritici through transcriptomic analysis - Manish Kumar; Ashish Kumar Singh; Ramesh Bhurta; Sharanbasappa D. Madival; Yashwant Kumar Yadava; Pradeep Kumar Jain; Mahender Singh Saharan; Vishal Singh Somvanshi; Anil Sirohi (Physiological and Molecular Plant Pathology, 2024)

Performance study of the bioreactor for the biodegradation of methyl orange dye by luffa immobilized Stenotrophomonas maltophilia and kinetic studies: A sustainable approach - Anshuman Mishra; Dhananjay Singh; Ram Sharan Singh; Vinay Mishra; Manish Kumar; Balendu Shekher Giri (Groundwater for Sustainable Development, 2024)

Reduction of local scour around a circular bridge pier using the collars and sacrificial piles in non-uniform sediment - Mangu Rahul Bharadwaj; Lav Kumar Gupta; Manish Pandey (Geomorphology, 2024)

Ecohydrological and hydrogeological dynamics of groundwater springs in Eastern Himalaya, India - Manish Kumar; Sumit Sen; Himanshu Kulkarni; Shrinivas Badiger; Girish R. Varma; Jagdish Krishnaswamy (Groundwater for Sustainable Development, 2024)

From orchard to table: Significance of fruit microbiota in postharvest diseases management of citrus fruits - Manoj Kumar Solanki; Zhen Wang; Amit Kaushik; Vipin Kumar Singh; Rajib Roychowdhury; Manish Kumar; Dharmendra Kumar; Joginder Singh; Sandeep Kumar Singh; Bhavana Dixit; Ajay Kumar (Food Control, 2024)

Zeolites in wastewater treatment: A comprehensive review on scientometric analysis, adsorption mechanisms, and future prospects - Sheetal Kumari; Jyoti Chowdhry; Manish Kumar; Manoj Chandra Garg (Environmental Research, 2024)

Progress and obstacles in employing carbon quantum dots for sustainable wastewater treatment - Ramsha Khan; Saurabh Shukla; Manish Kumar; Damià Barceló; Antonio Zuorro; Preeti Chaturvedi Bhargava (Environmental Research, 2024)

Enhanced photocatalytic degradation activity of titanium dioxide by adsorbing aromatic amines through N-bonding - Shivam Patel; Sagnik Mukherjee; Mahesh Neem; Subhadip Neogi; K.L. Ameta; Arvnabh Mishra; M.P. Deshpande; Manish Kumar Mishra (Colloids and Surfaces C: Environmental Aspects, 2024)

Long-term observations of NO2, SO2, HCHO, and CHOCHO over the Himalayan foothills: Insights from MAX-DOAS, TROPOMI, and GOME-2 - Prajjwal Rawat; Manish Naja; Mahendar C. Rajwar; H. Irie; Christophe Lerot; Mukesh Kumar; S. Lal (Atmospheric Environment, 2024)

Projected changes in monsoonal compound dry-hot extremes in India - Nikhil Kumar; Manish Kumar Goyal (Atmospheric Research, 2024)

Reliability-Based Design for Strip-Footing Subjected to Inclined Loading Using Hybrid LSSVM ML Models - Manish Kumar; Divesh Ranjan Kumar; Warit Wipulanusat (Geotechnical and Geological Engineering, 2024)

Evaluating the performance and detection efficiency of Weather Research Forecasting model with lightning parameterization schemes for identifying lightning hotspots over Northeast region in India - Unashish Mondal; S. K. Panda; Toru Terao; Manish Kumar; Devesh Sharma (Climate Dynamics, 2024)

Fe-doped nano-cobalt oxide green catalysts for sulfoxidation and photo degradation - Atul Soni; Minaxi S. Maru; Parth Patel; Jagriti Behal; Deepika Kaushal; Manish Kumar; Maheshwar S. Thakur; Sunil Kumar (Clean Technologies and Environmental Policy, 2024)

Optimization of dietary protein based on ideal protein concept for genetically improved farmed tilapia (GIFT) juveniles reared in inland saline water - Chetan K. Garg; Parimal Sardar; Narottam P. Sahu; Manas K. Maiti; Manish Jayant; Naseemashahul Shamna; Tincy Varghese; Ashutosh D. Deo; Vikas Kumar (Animal Feed Science and Technology, 2024)

Docetaxel-tethered di-Carboxylic Acid Derivatised Fullerenes: A Promising Drug Delivery Approach for Breast Cancer - Charu Misra; Jasleen Kaur; Manish Kumar; Lokesh Kaushik; Deepak Chitkara; Simran Preet; Muhammad Wahajuddin; Kaisar Raza (AAPS PharmSciTech, 2024)

Evaluation of infiltration rate and pedotransfer function under different landuse patterns for Kalyanpur block, Bihar - Rima Das; Ambrish Kumar; Manish Kumar; Ratnesh Kumar Jha; Ravish Chandra; Ravindra Kumar Tiwari (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Characterization, phytochemical profiling, antioxidant, and cytotoxicity of underutilized medicinal plants and composite flour - Neha Singh; Nipanshi Tyagi; Manish Singh; Hemant Ritturaj Kushwaha; Rakesh Kumar Sharma; Pallee Shree; Avneesh Mittal; Rajni Chopra; Meenakshi Garg (Food Chemistry, 2024)

Reverse osmosis silica fouling control with reactive micromixing - Weiliang Bai; Ruizhe Xu; Daniel King; Adam Boehnke; Igor Krupa; Peter Kasak; Anton Popelka; Navid B. Saleh; Manish Kumar (Desalination, 2024)

Plasma and radiation mediated green synthesis of gold Nanoparticles-immobilized bio-template based catalytic reactor ‘AuNICaR’: Mechanistic insights, catalytic performance and reusability analysis - Swarnima Rawat; Nilanjal Misra; Manish Singh; Ayan Ghosh; Shubhangi A. Shelkar; Mahesh Tiwari; Soumen Samanta; Virendra Kumar (Chemical Engineering Journal, 2024)

Correction: Finger millet (Eleusine coracana L.): from staple to superfood—a comprehensive review on nutritional, bioactive, industrial, and climate resilience potential - Simardeep Kaur; Arti Kumari; Karishma Seem; Gurkanwal Kaur; Deepesh Kumar; Surbhi Verma; Naseeb Singh; Amit Kumar; Manish Kumar; Sandeep Jaiswal; Rakesh Bhardwaj; Binay Kumar Singh; et al. (Planta, 2024)

An End-to-End Deep Learning Framework for Cyclone Intensity Estimation in North Indian Ocean Region Using Satellite Imagery - Manish Kumar Mawatwal; Saurabh Das (Journal of the Indian Society of Remote Sensing, 2024)

Conservation agriculture layered with subsurface drip fertigation influences weed dynamics, weed indices and productivity of rice-wheat system - Manish Kakraliya; H.S. Jat; R.S. Chhokar; Suresh Kumar; Madhu Choudhary; P.C. Sharma; M.L. Jat (Crop Protection, 2024)

A review of evolving climate and energy economy trends to enhance the dynamic life cycle assessment of buildings - Sejal Sanjay Shanbhag; Manish Kumar Dixit (Sustainable Cities and Society, 2024)

Preservation potential of essential oils on the postharvest quality and shelf-life attributes of mango fruit - Killi Prasad; Ram Asrey; Shruti Sethi; Manish Srivastav; Dinesh Singh; Ajay Arora; Alka Joshi; Vijay Rakesh Reddy; Nirmal Kumar Meena; Anamika Thakur; Karri Ramakrishna (South African Journal of Botany, 2024)

Exploring phenolic compounds as natural stress alleviators in plants- a comprehensive review - Nancy Saini; Anmol Anmol; Sanjeev Kumar; Ab Waheed Wani; Manish Bakshi; Zarina Dhiman (Physiological and Molecular Plant Pathology, 2024)

Unveiling the draft genome of the seed gall nematode, Anguina tritici: Insights and analysis - Ashish Kumar Singh; Antara Das; Kuldeep Kumar; Ila Joshi; Manish Kumar; Deshika Kohli; Ramanna Koulagi; Animesh Kumar; Kishor Gaikwad; Pradeep Kumar Jain; Anil Sirohi (Physiological and Molecular Plant Pathology, 2024)

Indian and global scenarios of Bisphenol A distribution and its new analogues: Prevalence & probability exceedance - Kanika Dogra; Dipa Lalwani; Shiwangi Dogra; Durga Prasad Panday; Nirav P. Raval; Murgesh Trivedi; Abrahan Mora; Misael Sebastian Gradilla Hernandez; Shane A. Snyder; Jürgen Mahlknecht; Manish Kumar (Journal of Hazardous Materials, 2024)

Traversing the prevalence of microplastics in soil-agro ecosystems: Origin, occurrence, and pollutants synergies - Kanika Dogra; Manish Kumar; Kanchan Deoli Bahukhandi; Jian Zang (Journal of Contaminant Hydrology, 2024)

On-farm evidence on breaking yield barriers through optimizing wheat cropping system in Indo Gangetic Plain - Radheshyam; Shankar Lal Jat; M.L. Jat; C.M. Parihar; H.S. Jat; A.K. Singh; Deepak Bijarniya; Smruti Ranjan Padhan; Praveen V. Kadam; Manish Kumar (European Journal of Agronomy, 2024)

Exploring polymorphism's impact on layer production traits: A deep dive into association studies and candidate genes in Kadaknath - Manjari Pandey; Sanjeev Kumar; Chandrahas; Subrat Kumar Bhanja; Manish Mehra (Ecological Genetics and Genomics, 2024)

Acceleration of bulk and surface charger transfer dynamics via FePi cocatalyst-coated Ti/(Sb)-Fe2O3:Sb/(Ti)-Fe2O3 type-II homojunction photoanode for photoelectrochemical performance - Periyasamy Anushkkaran; Ruturaj P. Patil; Weon-Sik Chae; Manish Kumar; Sun Hee Choi; Hyun Hwi Lee; Hyun Gyu Kim; Bong-Kyu Kim; Jum Suk Jang (Chemical Engineering Journal, 2024)

Nucleoside and non-nucleoside reverse transcriptase inhibitor drugs (NRTIs and NNRTIs) are capable of binding Chandipura virus polymerase protein (L) and inhibit virus replication - Dibyakanti Mandal; Deeksha Pandey; Debi P. Sarkar; Manish Kumar (VirusDisease, 2024)

Characterizing fuel flammability in a tropical dry community forest in Eastern India using laboratory and remote sensing based approaches - Satyajit Behera; Basanta Kumar Prusty; Mukunda Dev Behera; Manish Prabhakar Kale (Tropical Ecology, 2024)

Evaluation of Processing Quality Attributes of Potato (Solanum Spp.) Genotypes Grown in Mid-Hills of Himachal Pradesh - Vinaykumar Rachappanavar; Manish Kumar; Vinod Kumar; VU Patil; Vineeta Sharma (Potato Research, 2024)

Finger millet (Eleusine coracana L.): from staple to superfood—a comprehensive review on nutritional, bioactive, industrial, and climate resilience potential - Simardeep Kaur; Arti Kumari; Karishma Seem; Gurkanwal Kaur; Deepesh Kumar; Surbhi Verma; Naseeb Singh; Amit Kumar; Manish Kumar; Sandeep Jaiswal; Rakesh Bhardwaj; Binay Kumar Singh; et al. (Planta, 2024)
Main conclusion This review discusses the Finger millet's rich nutritional profile, bioactive potential, and industrial applications, combined with its climate resilience, which make it a promising crop for enhancing food security and promoting sustainable agriculture. This review also highlights its significant potential to address malnutrition and mitigate climate change impacts. Abstract The emergence of Finger millet from “poor man’s staple food” to “a nutrient rich cereal” has encouraged the need to explore this crop at a wider scale. It is a highly significant crop due to its rich nutritional and bioactive profile, diverse biological activities, and promising industrial applications, along with the high climate resilience. This comprehensive review evaluates its nutritional composition by comparing favorably with other cereals and millets and emphasizing its potential to address malnutrition and enhance food security. Furthermore, it explores the phytochemical/bioactive potential and strategies to enhance their bioavailability followed biological activities of Finger millet by highlighting its various health-promoting properties. The review also discusses industrial potential of finger millet including its role in nutraceutical and functional food production, as well as bioenergy generation. In addition, role of Finger millet as a climate-resilient crop; specifically, the available genetic resources and identification of genes and quantitative trait loci (QTLs) associated with major stress tolerance traits have also been discussed. By providing a comprehensive synthesis of existing knowledge, this study offers valuable insights for researchers, policymakers, and stakeholders engaged in efforts to promote sustainable agriculture, enhance food and nutrition security, and mitigate the impacts of climate change.

River pollution in India: exploring regulatory and remedial paths - Rajneesh Kumar; Manish Kumar Goyal; Rao Y. Surampalli; Tian C. Zhang (Clean Technologies and Environmental Policy, 2024)

Phenotypic and molecular characterization of clinically isolated antibiotics-resistant S. aureus (MRSA), E. coli (ESBL) and Acinetobacter 1379 bacterial strains - Daraksha Iram; Manish Singh Sansi; Anil Kumar Puniya; Kamal Gandhi; Sunita Meena; Shilpa Vij (Brazilian Journal of Microbiology, 2024)

Aerosol atmospheric rivers: patterns, impacts, and societal insights - Kuldeep Singh Rautela; Shivam Singh; Manish Kumar Goyal (Environmental Science and Pollution Research, 2024)

Engineered lignocellulosic based biochar to remove endocrine-disrupting chemicals: Assessment of binding mechanism - Vinay Kumar; Preeti Sharma; Ritu Pasrija; Pritha Chakraborty; Thazeem Basheer; Jithin Thomas; Satbir S. Sehgal; Manish Gupta; Khursheed Muzammil (Chemosphere, 2024)

Deep neural network model for predicting thermal-hydraulic performance of a solar air heater with artificial roughness: Sensitivity, generalization capacity, and computational efficiency - Siddharth Suman; Sarvapriya Singh; Santanu Mitra; Manish Kumar (Process Safety and Environmental Protection, 2024)

Water neutrality: Concept, challenges, policies, and recommendations - Rajneesh Kumar; Avinash Mishra; Manish Kumar Goyal (Groundwater for Sustainable Development, 2024)

Machine learning (ML): An emerging tool to access the production and application of biochar in the treatment of contaminated water and wastewater - Sheetal Kumari; Jyoti Chowdhry; Manish Kumar; Manoj Chandra Garg (Groundwater for Sustainable Development, 2024)

Decoding uranium variation over the Indian peninsula through leveraging standardized precipitation evapotranspiration indices and groundwater level fluctuations - Durga Prasad Panday; Manish Kumar (Groundwater for Sustainable Development, 2024)

Microplastics in freshwater: Unveiling sources, fate, and removal strategies - Sweta Upadhyay; Pradeep Kumar Sharma; Kanika Dogra; Prosun Bhattacharya; Manish Kumar; Vijay Tripathi; Rachan Karmakar (Groundwater for Sustainable Development, 2024)

Efficient solar-powered evaporator with multifunctional nanofiber - Manish Kumar; Pallavi Kadian; Kanchan Kumari; Rajat Sharma; Jaspreet Kaur Randhawa (Desalination, 2024)

Improving Water Efficiencies in Rural Agriculture for Sustainability of Water Resources: A Review - Manish Yadav; B. B. Vashisht; S. K. Jalota; T. Jyolsna; Samar Pal Singh; Arun Kumar; Amit Kumar; Gurjeet Singh (Water Resources Management, 2024)

Comparative transcriptome profile of embryos at different developmental stages derived from somatic cell nuclear transfer (SCNT) and in-vitro fertilization (IVF) in riverine buffalo (Bubalus bubalis) - Deepak Kumar; Manish Tiwari; Pallavi Goel; Manoj Kumar Singh; Naresh Lala Selokar; Prabhat Palta (Veterinary Research Communications, 2024)

Numerical simulation of local scour around the pier with and without airfoil collar (AFC) using FLOW-3D - Lav Kumar Gupta; Manish Pandey; P. Anand Raj (Environmental Fluid Mechanics, 2024)

CAR T-cell therapy: a potential treatment strategy for pediatric midline gliomas - Anand Kumar Das; Mainak Sinha; Saraj Kumar Singh; Anurag Chaudhary; Ashim Kumar Boro; Manish Agrawal; Sona Bhardwaj; Simmi Kishore; Katyayani Kumari (Acta Neurologica Belgica, 2024)

WITHDRAWN: Prospects of graphene quantum dots preparation using lignocellulosic wastes for application in photofermentative hydrogen production - Neha Srivastava; Basant Lal; Akbar Mohammad; Ashutosh Rai; Prakash Ranjan Deen; Rajeev Singh; Irfan Ahmad; Manish Srivastava; Vijai Kumar Gupta (Chemosphere, 2024)

Lignocellulosic biomass for biochar production: A green initiative on biowaste conversion for pharmaceutical and other emerging pollutant removal - Vinay Kumar; Neha Sharma; Balamurugan Panneerselvam; Lohith Kumar Dasarahally Huligowda; Mridul Umesh; Manish Gupta; Khursheed Muzammil; Yousef Zahrani; Musa Malmutheibi (Chemosphere, 2024)

Arsenic and fluoride in groundwater triggering a high risk: Probabilistic results using Monte Carlo simulation and species sensitivity distribution - Diego A. Padilla-Reyes; Jaime Dueñas-Moreno; Jürgen Mahlknecht; Abrahan Mora; Manish Kumar; Nancy Ornelas-Soto; Sandra Mejía-Avendaño; Carmen J. Navarro-Gómez; Prosun Bhattacharya (Chemosphere, 2024)

Graphene and its derivatives fabrication from paddy straw for improved and sustainable application in biofuels production: New Insight - Neha Srivastava; Rajeev Singh; Basant Lal; Akbar Mohammad; Ashutosh Kumar Rai; Irfan Ahmad; Manish Srivastava; Chang-Hyung Choi; Vijai Kumar Gupta (Process Safety and Environmental Protection, 2024)

Tricks and tracks of prevalence, occurrences, treatment technologies, and challenges of mixtures of emerging contaminants in the environment: With special emphasis on microplastic - Jayaraman Sethuraman Sudarsan; Kanika Dogra; Rakesh Kumar; Nirav P. Raval; Mats Leifels; Santanu Mukherjee; Mrugesh H. Trivedi; Mayur Shirish Jain; Jian Zang; Damià Barceló; Jürgen Mahlknecht; Manish Kumar (Journal of Contaminant Hydrology, 2024)

A novel approach to estimate rock deformation under uniaxial compression using a machine learning technique - Pradeep T.; Divesh Ranjan kumar; Manish Kumar; Pijush Samui; Danial Jahed Armaghani (Bulletin of Engineering Geology and the Environment, 2024)

A comparative study of health risks of selected potentially toxic metals in household dust from different socio-economical houses of Dhanbad city, India - Shravan Kumar; Manish Kumar Jain (Air Quality, Atmosphere & Health, 2024)

Geochemical and geochronological evolution of the UHT granulites from the Eastern Ghats Mobile Belt, India: implications from F-OH substitution in biotite, thermal events and cooling age - Saurabh Singh; Divya Prakash; Roopali Yadav; Manish Kumar; Bikash Mahanta; Jesús Solé Viñas (International Geology Review, 2024)

Exploiting fly ash as an ecofriendly pesticide/nematicide on Abesmoschus esculuntus: Insights into soil amendment-induced antioxidant fight against nematode mediated ROS - Adil Ameen Bhat; Adnan Shakeel; Aashaq Hussain Bhat; Mohamed F. Alajmi; Abrar Ahmed Khan; Manish Kumar (Chemosphere, 2024)

RETRACTED: Almond shell-derived biochar decreased toxic metals bioavailability and uptake by tomato and enhanced the antioxidant system and microbial community - Muhammad Imran Ghani; Mohammad Abass Ahanger; Tanveer Ali Sial; Sajjad Haider; Junaid Ali Siddique; Ruidong Fan; Yanjiang Liu; Esmat F. Ali; Manish Kumar; Xing Yang; Jörg Rinklebe; Xiaoyulong Chen; et al. (Science of The Total Environment, 2024)

Ensuring carbon neutrality via algae-based wastewater treatment systems: Progress and future perspectives - Amit Kumar; Saurabh Mishra; Nitin Kumar Singh; Manish Yadav; Hirendrasinh Padhiyar; Johnson Christian; Rupesh Kumar (Journal of Environmental Management, 2024)

A rapid and field-ready snap-chill polymerase spiral reaction (PSR) colorimetric assay for identification of buffalo (Bubalus bubalus) tissue - Jyoti Jawla; Manish Kumar Chatli (Food Bioscience, 2024)

COVID-19 in environment: Treatment, Infectivity, Monitoring, Estimation (TIME) - Manish Kumar; Ryo Honda; Daniel Snow; Payal Mazumder; Prosun Bhattacharya (Current Opinion in Environmental Science & Health, 2024)

CuO NWs boosted triboelectric microfluidic nanosensor functionalized by collagen-protein interactions for real-time platelet count monitoring - Jia-Cheng Lin; Kuldeep Kaswan; Subhodeep Chatterjee; Yu-Wen Wu; Manish Kumar Sharma; Ashok Ranjan; Snigdha Roy Barman; Yu-Zih Lin; Thierry Burnouf; Wilfrid Boireau; Ming-Yen Lu; Yong-Kwang Tu; et al. (Chemical Engineering Journal, 2024)

Transcriptome responses of Arabidopsis to necrotrophic fungus Alternaria brassicae reveal pathways and candidate genes associated with resistance - S. Hamsa; Sivasubramanian Rajarammohan; Manisha Aswal; Manish Kumar; Jagreet Kaur (Plant Molecular Biology, 2024)

Editorial Expression of Concern: Ellagic acid prevents dementia through modulation of PI3-kinase-endothelial nitric oxide synthase signaling in streptozotocin-treated rats - Manish Kumar; Nitin Bansal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Temporal dynamics of urban air pollutants and their correlation with associated meteorological parameters: an investigation in northern Indian cities - Pushpendra Singh Soni; Vikram Singh; Alok Sagar Gautam; Karan Singh; Manish Sharma; Rolly Singh; Alka Gautam; Surendra Pratap Singh; Sanjeev Kumar; Sneha Gautam (Environmental Monitoring and Assessment, 2024)

Prospects of earthworm coelomic fluid as a potential therapeutic agent to treat cancer - Shafiul Haque; Arif Hussain; Atiah H. Almalki; Mohammed F. Aldawsari; Basant Lal; Ashutosh Kumar Rai; Manish Srivastava; Marta Fiołka (Cancer and Metastasis Reviews, 2024)

Reactive oxygen species mediated apoptosis induction in human liver cancer cells by Emblica officinalis (Amla): a new trend in liver cancer treatment - Archana Chaudhary; Nandani kumari; Manish kumar; Md. Margoob Ahmad; Mohammad Shamsul Ola; Rizwanul Haque (Toxicology and Environmental Health Sciences, 2024)

Mineralogical Characteristics and Sources of Coarse Mode Particulate Matter in Central Himalayas - Sakshi Gupta; Shobhna Shankar; Priyanka Srivastava; Manish Naja; Ranu Gadi; Sudhir Kumar Sharma (Aerosol Science and Engineering, 2024)

Countermeasures for local scour around the bridge pier: a review - Mangu Rahul Bharadwaj; Lav Kumar Gupta; Manish Pandey; Manousos Valyrakis (Acta Geophysica, 2024)

Geochemical evaluation and the mechanism controlling groundwater chemistry using chemometric approach and groundwater pollution index (GPI) in the Kishangarh city of Rajasthan, India - Manish Kumar; Vipin Garg; Ramesh Kumar; Rajesh Kumar (Environmental Science and Pollution Research, 2024)

Single episode of moderate to severe traumatic brain injury leads to chronic neurological deficits and Alzheimer’s-like pathological dementia - Kumar Vaibhav; Mayuri Gulhane; Pankaj Ahluwalia; Manish Kumar; Meenakshi Ahluwalia; Ashiq M. Rafiq; Vibha Amble; Manuela G. Zabala; Jacob B. Miller; Liam Goldman; Ashis K. Mondal; Ferenc Deak; et al. (GeroScience, 2024)

Application of ensemble fuzzy weights of evidence-support vector machine (Fuzzy WofE-SVM) for urban flood modeling and coupled risk (CR) index for ward prioritization in NCT Delhi, India - Syed Irtiza Majid; Manish Kumar; Netrananda Sahu; Pankaj Kumar; Dinesh Kumar Tripathi (Environment, Development and Sustainability, 2024)

Unraveling the role of microRNA-like RNAs in enhancing Puccinia triticina pathogenicity in wheat by high-throughput sequencing data - Uzma Afreen; Manish Kumar; Kunal Mukhopadhyay (Physiological and Molecular Plant Pathology, 2024)

A comprehensive assessment of macro and microplastics from Rivers Ganga and Yamuna: Unveiling the seasonal, spatial and risk factors - Priyansha Gupta; Mahua Saha; Akshata Naik; M. Manish Kumar; Chayanika Rathore; Shrish Vashishth; Shukla Pal Maitra; K.D. Bhardwaj; Harsh Thukral (Journal of Hazardous Materials, 2024)

Conservation agriculture works as a catalyst for sustainable sodic soil reclamation and enhances crop productivity and input use efficiency: A scientific inquiry - Hanuman Sahay Jat; Manish Kakraliya; Raj Mukhopadhyay; Satyendra Kumar; Madhu Choudhary; Parbodh Chander Sharma (Journal of Environmental Management, 2024)

Introducing reverse Multi Influencing Factor technique in DRASTIC model for groundwater vulnerability assessment - Sandhya Ganwer; Manish Kumar Sinha; Amit Prakash Multaniya; Nikhil Ghodichore (Groundwater for Sustainable Development, 2024)

Spatio-temporal evaluation of drought adaptation in wheat revealed NDVI and MTSI as powerful tools for selecting tolerant genotypes - S. Srinatha Reddy; G Mahendra Singh; Uttam Kumar; Pradeep Bhati; Manish Vishwakarma; Sudhir Navathe; K.J. Yashavanthakumar; Vinod K. Mishra; Sandeep Sharma; Arun K. Joshi (Field Crops Research, 2024)

Ni(II) triggered sensing and reversible uptake of ammonia by tetrazole based Ni(II) metallogel: A one-pot mechanistic approach - Farahin Y. Vahora; Milan C. Makwana; Manish Kumar Mishra; Komal M. Vyas (Chemical Engineering Journal, 2024)

Radiative effect of atmospheric Brown clouds over the Indo-Gangetic plain - Manish Jangid; Tanerao Singh Sankhla; Sachchidanand Singh; Amit Kumar Mishra (Atmospheric Pollution Research, 2024)

Site-directed mutagenesis at the Glu78 in Ec-NhaA transporter impacting ion exchange: a biophysical study - Anuradha Yadav; Dinesh Kumar; Manish Dwivedi (European Biophysics Journal, 2024)

Cyanobacteria Based Nanoformulation of Biogenic CuO Nanoparticles for Plant Growth Promotion of Rice Under Hydroponics Conditions - Rajni Yadav; Manish Kumar; Rajesh Singh Tomar (Current Microbiology, 2024)

The F-box protein encoding genes of the leaf-rust fungi Puccinia triticina: genome-wide identification, characterization and expression dynamics during pathogenesis - Anupama Gidhi; Shailendra Kumar Jha; Manish Kumar; Kunal Mukhopadhyay (Archives of Microbiology, 2024)

Conversion of locally available materials to biochar and activated carbon for drinking water treatment - P.V. Nidheesh; Manish Kumar; G. Venkateshwaran; S. Ambika; S. Bhaskar; Vinay; Pooja Ghosh (Chemosphere, 2024)

A review on value-addition to plastic waste towards achieving a circular economy - Manish Kumar; Sachin Krushna Bhujbal; Kirtika Kohli; Ravindra Prajapati; Brajendra K. Sharma; Ankush D. Sawarkar; Kumar Abhishek; Shiv Bolan; Pooja Ghosh; M.B. Kirkham; Lokesh P. Padhye; Ashok Pandey; et al. (Science of The Total Environment, 2024)

Comparative study of reduction of pier scour using octagonal and circular collars - Lav Kumar Gupta; M. Rahul Bharadwaj; Manish Pandey (Ocean Engineering, 2024)

Remediation of Cr(VI) using a radiation functionalized green adsorbent: Adsorption modelling, mechanistic insights and prototype water purifier demonstration - Swarnima Rawat; Nilanjal Misra; Manish Singh; Mahesh Tiwari; Ayan Ghosh; Shubhangi A. Shelkar; Soumen Samanta; Narender Kumar Goel; Virendra Kumar (Journal of Water Process Engineering, 2024)

Unveiling the potential of NiFe layered double hydroxide (LDH)/CuWO4 S-scheme heterojunction for sulfamethoxazole photodegradation and nitrobenzene photoreduction to aniline - Rohit Sharma; Shabnam Sambyal; Parteek Mandyal; Nasarul Islam; Aashish Priye; Itika Kainthla; Manish Kumar; Vinay Chauhan; Pooja Shandilya (Journal of Environmental Chemical Engineering, 2024)

Fabrication of dual S-scheme based CuWO4/NiFe/WO3 heterojunction for visible-light-induced degradation and reduction applications - Rohit Sharma; Nasarul Islam; Aashish Priye; Deepak Kumar; Jay Singh; Manish Kumar; Prem P. Sharma; Vinay Chauhan; Pooja Shandilya (Journal of Environmental Chemical Engineering, 2024)

Arsenic contamination in the groundwater of Northeastern India: Critical understandings on geotectonic controls and the need for intervention - Nikita Neog; Ritusmita Goswami; Durga Prasad Panday; Abhay Kumar; M. Tamil Selvan; Annapurna Boruah; Manish Kumar (Current Opinion in Environmental Science & Health, 2024)

Deciphering the role of optimal P2/O3 phase fraction in enhanced cyclability and specific capacity of layered oxide cathodes - Samriddhi Saxena; Manish Badole; Hari Narayanan Vasavan; Velaga Srihari; Asish Kumar Das; Pratiksha Gami; Sonia Deswal; Pradeep Kumar; Sunil Kumar (Chemical Engineering Journal, 2024)

Strategies to utilize genome editing for increasing nitrogen use efficiency in crops - Amit Kumar; Meena Subbaiah; Jeet Roy; Sachin Phogat; Megha Kaushik; Manish Ranjan Saini; Jayanthi Madhavan; Amitha Mithra Sevanthi; Pranab Kumar Mandal (The Nucleus, 2024)

A comparative study on pretreatment of rice straw and saccharification by commercial and isolated cellulase–xylanase cocktails towards enhanced bioethanol production - Manish Paul; Gireesh Kumar Shroti; Sonali Mohapatra; Pradeep Kumar DasMohapatra; Hrudayanath Thatoi (Systems Microbiology and Biomanufacturing, 2024)

Assessment and modelling of hydro-sedimentological flows of the eastern river Dhauliganga, north-western Himalaya, India - Kuldeep Singh Rautela; Jagdish Chandra Kuniyal; Manish Kumar Goyal; Nidhi Kanwar; Ajay Singh Bhoj (Natural Hazards, 2024)

Development and Evaluation of Novel Amoxicillin and Phytic Acid-Loaded Gastro-Retentive Mucoadhesive Pectin Microparticles for the Management of Helicobacter pylori Infections - Ajit Mishra; Debalina Maity; Deepak Pradhan; Jitu Halder; Tushar Kanti Rajwar; Vineet Kumar Rai; Manoj Kumar Sarangi; Salim Manoharadas; Manish Ramchandani; Amit Goyal; Biswakanth Kar; Goutam Ghosh; et al. (Journal of Pharmaceutical Innovation, 2024)

Urban ozone variability using automated machine learning: inference from different feature importance schemes - Sankar Jyoti Nath; Imran A. Girach; S. Harithasree; Kalyan Bhuyan; Narendra Ojha; Manish Kumar (Environmental Monitoring and Assessment, 2024)

Satellite or ground-based measurements for air pollutants (PM2.5, PM10, SO2, NO2, O3) data and their health hazards: which is most accurate and why? - Zainab Mushtaq; Pargin Bangotra; Alok Sagar Gautam; Manish Sharma; Suman; Sneha Gautam; Karan Singh; Yogesh Kumar; Poonam Jain (Environmental Monitoring and Assessment, 2024)

Heavy metal pollution in indoor dust of residential, commercial, and industrial areas: a review of evolutionary trends - Arpita Roy; Aditya Kumar Jha; Abhishek Kumar; Tanushree Bhattacharya; Sukalyan Chakraborty; Nirav P. Raval; Manish Kumar (Air Quality, Atmosphere & Health, 2024)

Climatological features of rapidly intensifying tropical cyclones in the North Indian Ocean - Manish R. Ranalkar; Ram Kumar Giri; Kamaljit Ray (International Journal of Climatology, 2024)
The study investigates the climatological variation of rapidly intensifying tropical cyclones (RITCs) developed in the North Indian Ocean (NIO) using observational and reanalysis data from 1982 to 2020. The analysis reveals that out of 153 tropical cyclones (TC) developed in the NIO, 59 TCs underwent rapid intensification (RI). The monthly variation of RITCs exhibited bimodal distribution with a primary peak in November and a secondary peak in May. The percentage of RITCs during April–June is higher as compared to October–December. The study identifies the core zones of RI initiation in the Arabian Sea (AS) and the Bay of Bengal (BoB), respectively. The occurrences of RITCs over the AS have been observed to increase since 2000. Over 65% of RITCs occurred within 12 h of TC formation, and the duration of RI varies from 24 to 48 h. TCs with lifetime maximum intensity (LMI) less than 55 kt have not undergone RI. The trend in the 95th percentile of 24‐h intensity changes is positive but insignificant ( p ‐value >0.05) in the AS, and for the BoB, it is negative and significant ( p ‐value

A numerical model for the prediction of radon flux from uranium mill tailings at Jaduguda, India - Dibyendu Rana; Vivekanand Jha; RLokeswara Patnaik; Manish Kumar Singh; Sanjay Kumar Jha; Mukund S. Kulkarni (Environmental Science and Pollution Research, 2024)

Experimental and computational studies on the corrosion inhibition potential of a novel synthesized thiophene and pyridine-based 1,3,4-oxadiazole hybrid against mild steel corrosion in 1 N HCl - Deepak Sharma; Abhinay Thakur; Manish Kumar Sharma; Anand Bhardwaj; Ashish Sihmar; Hariom Dahiya; Ashok Kumar Sharma; Ashish Kumar; Avni Berisha; Hari Om (Environmental Science and Pollution Research, 2024)

Green synthesis and characterization of nano zinc oxide and comparative study of its impact on germination and metabolic activities of Solanum lycopersicum L. and Capsicum annuum L. - Nishant Singh; Manish Kumar Singh; Ravi Kumar Yadav; Zeba Azim; Jyotsna Raghuvansi (Vegetos, 2024)

Global water quality indices: Development, implications, and limitations - Dheeraj Kumar; Rakesh Kumar; Madhuben Sharma; Amit Awasthi; Manish Kumar (Total Environment Advances, 2024)

Sperm proteomic landscape is altered in breeding bulls with greater sperm DNA fragmentation index - Kathan Raval; Arumugam Kumaresan; Manish Kumar Sinha; Kamaraj Elango; John Peter Ebenezer Samuel King; Pradeep Nag; Nilendu Paul; Thirumala Rao Talluri; Shivanagouda Patil (Theriogenology, 2024)

Transboundary hazard and downstream impact of glacial lakes in Hindu-Kush Karakoram Himalayas - Saket Dubey; Ashim Sattar; Vivek Gupta; Manish Kumar Goyal; Umesh K. Haritashya; Jeffrey S. Kargel (Science of The Total Environment, 2024)

RETRACTED: Biochar modulating soil biological health: A review - Shiv Bolan; Shailja Sharma; Santanu Mukherjee; Manish Kumar; Ch. Srinivasa Rao; K.C. Nataraj; Gurwinder Singh; Ajayan Vinu; Arnab Bhowmik; Harmandeep Sharma; Ali El-Naggar; Scott X. Chang; et al. (Science of The Total Environment, 2024)

Cu2O/WO3: A promising S-scheme heterojunction for photocatalyzed degradation of carbamazepine and reduction of nitrobenzene - Parteek Mandyal; Rohit Sharma; Shabnam Sambyal; Nasarul Islam; Aashish Priye; Manish Kumar; Vinay Chauhan; Pooja Shandilya (Journal of Water Process Engineering, 2024)

Evaluating the future risk of coastal Ramsar wetlands in India to extreme rainfalls using fuzzy logic - Shivukumar Rakkasagi; Manish Kumar Goyal; Srinidhi Jha (Journal of Hydrology, 2024)

Impact of urbanization and temperature on local abundance of Drosophila repleta Wollaston (1858) in the Western Himalayas - Seema Ramniwas; Girish Kumar; Manish Pandey; Divya Singh (Journal of Asia-Pacific Entomology, 2024)

Assessing Climate Vulnerability of Ramsar Wetlands through CMIP6 Projections - Shivam Singh; Manish Kumar Goyal; Erumalla Saikumar (Water Resources Management, 2024)

Soil nitrogen availability determines the CO2 fertilization effect on tree species (Neolamarckia cadamba): growth and physiological evidence - Manish Singh; Hukum Singh; Amit Kumar; Narendra Kumar; Manoj Kumar; Santan Barthwal; Ajay Thakur (Environmental Sustainability, 2024)

Identification of sources of coarse mode aerosol particles (PM10) using ATR-FTIR and SEM-EDX spectroscopy over the Himalayan Region of India - Sakshi Gupta; Shobhna Shankar; Jagdish Chandra Kuniyal; Priyanka Srivastava; Renu Lata; Sheetal Chaudhary; Isha Thakur; Archana Bawari; Shilpa Thakur; Monami Dutta; Abhinandan Ghosh; Manish Naja; et al. (Environmental Science and Pollution Research, 2024)

Identification of Playa Lakes and tracking their evolution pathways using geochemical models in the Great Indian Thar desert - Manish Kumar; Rajesh Kumar; Chander Kumar Singh; Alok Kumar (Science of The Total Environment, 2024)

Exploring genetic landscape of low-density polyethylene degradation for sustainable troubleshooting of plastic pollution at landfills - Roshani Mishra; Priyank Chavda; Rakesh Kumar; Ramesh Pandit; Madhvi Joshi; Manish Kumar; Chaitanya Joshi (Science of The Total Environment, 2024)

Multi-criteria thermoeconomic optimization of a geothermal energy-driven green hydrogen production plant coupled to an alkaline electrolyzer - Zhaoyang Zuo; Manish Saraswat; Ibrahim Mahariq; Tirumala Uday Kumar Nutakki; Aliashim Albani; Asiful H. Seikh; Van Fang Lee (Process Safety and Environmental Protection, 2024)

Characterizing the spatio-temporal distribution, detection, and prediction of aerosol atmospheric rivers on a global scale - Kuldeep Singh Rautela; Shivam Singh; Manish Kumar Goyal (Journal of Environmental Management, 2024)

Statistical investigation of combustion and emission characteristics of biofuels according to their physical properties: A way to explore suitable alternative fuels - Manish Kumar; Srinibas Karmakar; Vikas Nimesh (Fuel, 2024)

Various additive release from microplastics and their toxicity in aquatic environments - Ying Yu; Manish Kumar; Shiv Bolan; Lokesh P. Padhye; Nanthi Bolan; Sixu Li; Liuwei Wang; Deyi Hou; Yang Li (Environmental Pollution, 2024)

A new multispectral index for canopy nitrogen concentration applicable across growth stages in ryegrass and barley - Manish Kumar Patel; Dongryeol Ryu; Andrew W. Western; Glenn J. Fitzgerald; Eileen M. Perry; Helen Suter; Iain M. Young (Precision Agriculture, 2024)
Accurately monitoring Canopy Nitrogen Concentration (CNC) is a prerequisite for precision nitrogen (N) fertiliser management at the farm scale with carbon and N budgeting across the landscape and ecosystems. While many spectral indices have been proposed for CNC monitoring, their applicability and accuracy are often adversely affected by confounding factors such as aboveground biomass (AGB), crop type, growth stages, and environmental conditions, limiting their broader application and adoption; with AGB being one of the most dominant signals and confounding factors at canopy scale. The confounding effect can become more challenging as AGB is also physiologically linked with CNC across the growth stages. Additionally, the interplay between index form, selection of optimal wavebands and their bandwidths remains poorly understood for CNC index design. This study proposes robust and cost-effective 2- and 4-waveband multispectral (MS) CNC indices applicable across a wide range of crop conditions. We collected 449 canopy reflectance spectra (400–980 nm) together with corresponding CNC and AGB measurements across four growth stages of ryegrass (winter and summer), and five growth stages of barley (winter-spring) in Victoria, Australia, in 2018 and 2019. All possible waveband (400–980 nm) combinations revealed that the best combination varied between seasons and crop types. However, the visible spectrum, particularly the blue region, presented high and consistent performance. Bandwidths of 10–40 nm outperformed either very narrow (2 nm) or very broad bandwidths (80 nm). The newly developed 2-waveband index (416 and 442 nm with 10-nm bandwidth; R 2 = 0.75 and NRMSE = 0.2) and 4-waveband index (512, 440, 414 and 588 nm with 40-nm bandwidth; R 2 = 0.81 and NRMSE = 0.17) exhibited the best performance, while validation with an independent dataset (from a different growing period to those used in the model development) obtained NRMSE values of 0.25 and 0.24, respectively. The 4-waveband index provides enhanced performance and permits use of broader bandwidths than its 2-waveband counterpart.

Groundwater quality assessment for drinking purpose using traditional and fuzzy-GIS-based water quality index in Gurugram District of Haryana, India - Akash Tiwari; Manish Kumar; Swati Thakur (Environmental Geochemistry and Health, 2024)

Prolonged follicular dominance is associated with dysregulated proteomic profile of the follicular fluid in Bos indicus cows - Rajbangshi Niribili; Sakthivel Jeyakumar; Arumugam Kumaresan; Maharajan Lavanya; Manish Kumar Sinha; Majumder Kausik; Kamaraj Elango; Shivanagouda Patil; Teja Allu; Vedamurthy G. Veerappa; Ayyasamy Manimaran; D.N. Das; et al. (Theriogenology, 2024)

Univariate and bivariate spatiotemporal characteristics of heat waves and relative influence of large-scale climate oscillations over India - Shivam Singh; Aditya Yadav; Manish Kumar Goyal (Journal of Hydrology, 2024)

Occurrence, ecological and health risk assessment of phthalates in a polluted urban river used for agricultural land irrigation in central Mexico - Jaime Dueñas-Moreno; Ivón Vázquez-Tapia; Abrahan Mora; Pabel Cervantes-Avilés; Jürgen Mahlknecht; Mariana V. Capparelli; Manish Kumar; Chongqing Wang (Environmental Research, 2024)

In vitro virulotyping, antifungal susceptibility testing and DNA fingerprinting of Microsporum canis strains of canine and feline origin - Jitendra Kumar Bagra; Sonu S. Nair; V. Athira; M. Suman Kumar; Manish Kumar; Prasad Thomas; Bablu Kumar; V.K. Chaturvedi; Premanshu Dandapat; Abhishek (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Response surface bioprocess provenance for enhanced chitinase production by Thermomyces dupontii for translation of chitinous waste to short-chain chitooligosaccharides - Rajni Kumari; Manish Kumar; Apoorva Upadhayay; Pawan K. Dadheech; V. Vivekanand; Nidhi Pareek (Biocatalysis and Agricultural Biotechnology, 2024)

Assessment and suitability of DUS traits to screen potato (Solanum tuberosum L.) genotypes for Phytophthora spp. infection resistance by using phenotypic and molecular (SSR) markers - Vinaykumar Rachappanavar; Manish Kumar; Vinod Kumar; Dalamu; Satish K. Gupta (Genetic Resources and Crop Evolution, 2024)

Regional air quality: biomass burning impacts of SO2 emissions on air quality in the Himalayan region of Uttarakhand, India - Alok Sagar Gautam; Sanjeev Kumar; Sneha Gautam; Karan Singh; Kripa Ram; Devendraa Siingh; Balram Ambade; Manish Sharma (Air Quality, Atmosphere & Health, 2024)

Artificial viruses: A nanotechnology based approach - Shareef Shaik; Rajesh Kumar; Manish Chaudhary; Charanjit Kaur; Navneet Khurana; Gurvinder Singh (DARU Journal of Pharmaceutical Sciences, 2023)

Ruminal content biochar supplementation for enhanced biomethanation of rice straw: Focusing on biochar characterization and dose optimization - Sachin Krushna Bhujbal; Pooja Ghosh; Virendra Kumar Vijay; Manish Kumar (Science of The Total Environment, 2023)

Early warning of statewide COVID-19 Omicron wave by sentineled urbanized sewer network monitoring using digital PCR in a province capital city, of Gujarat, India - Manish Kumar; Madhvi Joshi; Bhumika Prajapati; Kwanrawee Sirikanchana; Skorn Mongkolsuk; Rakesh Kumar; Tharindu Pollwatta Gallage; Chaitanya Joshi (Science of The Total Environment, 2023)

Nitrate prediction in groundwater of data scarce regions: The futuristic fresh-water management outlook - Jürgen Mahlknecht; Juan Antonio Torres-Martínez; Manish Kumar; Abrahan Mora; Dugin Kaown; Frank J. Loge (Science of The Total Environment, 2023)

Prevalence of pharmaceuticals and personal care products, microplastics and co-infecting microbes in the post-COVID-19 era and its implications on antimicrobial resistance and potential endocrine disruptive effects - Manish Kumar; Payal Mazumder; Rahul Silori; Suvendu Manna; Durga Prasad Panday; Nilotpal Das; Susanta Kumar Sethy; Keisuke Kuroda; Durga Madhab Mahapatra; Jürgen Mahlknecht; Vinay Kumar Tyagi; Rajesh Singh; et al. (Science of The Total Environment, 2023)

Hydrological evaluation of conservation bench terrace system in outer foothills of Himalayas using soft computing techniques - Ambrish Kumar; Narinder Kumar Sharma; Bihari Lal Dhyani; Manish Kumar; Chaitanya B. Pande (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Impact of airfoil collar on scour reduction around the bridge pier - Lav Kumar Gupta; Manish Pandey; P. Anand Raj (Ocean Engineering, 2023)

Corrigendum to “Pharmacological evaluation of bromelain in mouse model of Alzheimer’s disease” [NeuroToxicology 90 (2022) 19–34] - Rakesh Kumar; Rajan Kumar; Neha Sharma; Navneet Khurana; Sachin Kumar Singh; Saurabh Satija; Meenu Mehta; Manish Vyas (NeuroToxicology, 2023)

Predicting the spatiotemporal characteristics of atmospheric rivers: A novel data-driven approach - Samarth Meghani; Shivam Singh; Nagendra Kumar; Manish Kumar Goyal (Global and Planetary Change, 2023)

Experimental Investigation on Flow Configuration in Flexible and Rigid Vegetated Streams - Binit Kumar; Swagat Patra; Manish Pandey (Water Resources Management, 2023)

GIS-Based Flood Susceptibility Mapping of Srinagar District, India Using Weights-of-Evidence (WofE), Frequency Ratio (FR) and Fuzzy Gamma Operator (FGO) - Syed Irtiza Majid; Manish Kumar; Pankaj Kumar; Naresh Kumar Verma (Journal of the Indian Society of Remote Sensing, 2023)

Nitric Oxide Synthase Inhibition Prevents Cell Proliferation in Glioblastoma - Daniel Kruglyakov; Shashank Kumar Ojha; Maryam Kartawy; Manish Kumar Tripathi; Wajeha Hamoudi; Wisam Bazbaz; Igor Khaliulin; Haitham Amal (Journal of Molecular Neuroscience, 2023)

Correction to: Enhanced production of bacterial cellulose employing banana peel as a cost-effective nutrient resource - Rajni Kumari; Mesevilhou Sakhrie; Manish Kumar; V. Vivekanand; Nidhi Pareek (Brazilian Journal of Microbiology, 2023)

Enhanced production of bacterial cellulose employing banana peel as a cost-effective nutrient resource - Rajni Kumari; Mesevilhou Sakhrie; Manish Kumar; V. Vivekanand; Nidhi Pareek (Brazilian Journal of Microbiology, 2023)

Demystifying the decadal shift in the extent of groundwater in the coastal aquifers of Gujarat, India: A case of reduced extent but increased magnitude of seawater intrusion - Manish Kumar; Durga Prasad Panday; Chandrashekhar Bhagat; Nilkanth Herbha; Vivek Agarwal (Science of The Total Environment, 2023)

Alumina recovery from bauxite residue: A concise review - Manish Kumar Kar; Mehmet Ali Recai Ӧnal; Chenna Rao Borra (Resources, Conservation and Recycling, 2023)

PM2.5 air pollution prediction through deep learning using meteorological, vehicular, and emission data: A case study of New Delhi, India - Deepti Shakya; Vishal Deshpande; Manish Kumar Goyal; Mayank Agarwal (Journal of Cleaner Production, 2023)

Decoding the enigma of 100-year record-breaking rainfall over Tamil Nadu using wavelet analysis - Asok Raja S K; Durga Prasad Panday; Manish Kumar (Groundwater for Sustainable Development, 2023)

Fate of pesticides in agricultural runoff treatment systems: Occurrence, impacts and technological progress - Nitin Kumar Singh; Gaurav Sanghvi; Manish Yadav; Hirendrasinh Padhiyar; Johnson Christian; Vijai Singh (Environmental Research, 2023)

Response of wastewater-based epidemiology predictor for the second wave of COVID-19 in Ahmedabad, India: A long-term data Perspective - Manish Kumar; Madhvi Joshi; Guangming Jiang; Rintaro Yamada; Ryo Honda; Vaibhav Srivastava; Jürgen Mahlknecht; Damia Barcelo; Sabarathinam Chidambram; Anwar Khursheed; David W Graham; Ritusmita Goswami; et al. (Environmental Pollution, 2023)

Adsorptive removal of ciprofloxacin and sulfamethoxazole from aqueous matrices using sawdust and plastic waste-derived biochar: A sustainable fight against antibiotic resistance - Rahul Silori; Jian Zang; Nirav P. Raval; Balendu Shekher Giri; Jürgen Mahlknecht; Abrahan Mora; Jaime Dueñas-Moreno; Syed Mohammad Tauseef; Manish Kumar (Bioresource Technology, 2023)

Technology development and challenges for the transformation of municipal solid waste into sustainable energy production - Tirath Raj; Sandhya Sompura; K. Chandrasekhar; Sushil Kumar Singh; Srinath Pandey; Lalit Kumar Singh; Manish Singh Rajput; Deepak Kumar; Shashi Kant Bhatia; Anil Kumar Patel; Reeta Rani Singhania (Biomass and Bioenergy, 2023)

Heatwave magnitude impact over Indian cities: CMIP 6 projections - Manish Kumar Goyal; Anil Kumar Gupta; Jew Das; Vijay Jain; Shivukumar Rakkasagi (Theoretical and Applied Climatology, 2023)

Association of a novel begomovirus species with fenugreek yellow vein disease in India - Manish Kumar; Amalendu Ghosh; Kuldeep Singh Jadon; Baljeet Kaur; Rajesh K. Kakani; Ramesh K. Solanki (Molecular Biology Reports, 2023)

Development and Evaluation of Amorphous Solid Dispersion of Riluzole with PBPK Model to Simulate the Pharmacokinetic Profile - Kanchan Bharti; Deepika Deepika; Manish Kumar; Abhishek Jha; Manjit; Akhilesh; Vinod Tiwari; Vikas Kumar; Brahmeshwar Mishra (AAPS PharmSciTech, 2023)

Silica sources for arsenic mitigation in rice: machine learning-based predictive modeling and risk assessment - Rubina Khanam; Amaresh Kumar Nayak; Pedda Ghouse Peera Sheikh Kulsum; Jajati Mandal; Mohammad Shahid; Rahul Tripathy; Pratap Bhattacharyya; Panneer Selvam; Sushmita Munda; Sivashankari Manickam; Manish Debnath; Raghavendra Goud Bandaru (Environmental Science and Pollution Research, 2023)

Political competition and environment quality: a study of India - Yadawananda Neog; Manish Kumar Singh; Anup Kumar Yadava; Achal Kumar Gaur (Environmental Science and Pollution Research, 2023)

Influence of CoOx surface passivation and Sn/Zr-co-doping on the photocatalytic activity of Fe2O3 nanorod photocatalysts for bacterial inactivation and photo-Fenton degradation - Velu Manikandan; Periyasamy Anushkkaran; In Seon Hwang; Min Seok Song; Manish Kumar; Weon-Sik Chae; Hyun-Hwi Lee; Jungho Ryu; Mahadeo A. Mahadik; Jum Suk Jang (Chemosphere, 2023)

Three decadal urban drought variability risk assessment for Indian smart cities - Manish Kumar Goyal; Vikas Poonia; Vijay Jain (Journal of Hydrology, 2023)

A novel combinatorial approach for cleaner production of biodegradable sheets from the combination of paddy straw and pine needle waste - Akansha Gupta; Amrita Preetam; Pooja Ghosh; Kalpana Arora; Satyawati Sharma; Vivek Kumar; Manish Kumar (Journal of Cleaner Production, 2023)

Synthesis of enhanced hydrophilic UiO-66-(COOH)2/PSF hybrid membrane for efficient separation of o/w and removal of water pollutants - Dashrathbhai B. Kanzariya; Smit Vala; Surendra Sasikumar Jampa; Manish Kumar Sinha; Tapan K. Pal (Journal of Environmental Chemical Engineering, 2023)

Rice husk biochar - A novel engineered bio-based material for transforming groundwater-mediated fluoride cycling in natural environments - Rakesh Kumar; Prabhakar Sharma; Pushpa Kumari Sharma; Pawan Kumar Rose; Rakesh Kumar Singh; Nishant Kumar; Prafulla Kumar Sahoo; Jyoti Prakash Maity; Ashok Ghosh; Manish Kumar; Prosun Bhattacharya; Ashok Pandey (Journal of Environmental Management, 2023)

Potassium-phosphorus-sulfur augmented biochar production from potentially toxic elements abated gypsum pond wastewater of phosphate fertilizer industry - Arati Ray; Manish Kumar; Adnan Asad Karim; Kushalindu Biswas; Sibadutta Mohanty; Krushna Prasad Shadangi; Sunil Kumar; Binoy Sarkar (Journal of Environmental Chemical Engineering, 2023)

Prevalence of Endocrine Disrupting Chemicals in the urban wastewater treatment systems of Dehradun, India: Daunting presence of Estrone - Rahul Silori; Manish Kumar; Durga Madhab Mahapatra; Pinakshi Biswas; Bhanu Prakash Vellanki; Jürgen Mahlknecht; Syed Mohammad Tauseef; Damia Barcelo (Environmental Research, 2023)

Effective corrosion inhibition of mild steel using novel 1,3,4-oxadiazole-pyridine hybrids: Synthesis, electrochemical, morphological, and computational insights - Deepak Sharma; Abhinay Thakur; Manish Kumar Sharma; Renu Sharma; Suresh Kumar; Ashish Sihmar; Hariom Dahiya; Gaurav Jhaa; Ashish Kumar; Ashok Kumar Sharma; Hari Om (Environmental Research, 2023)

Natural sub-bituminous coal as filler enhances mechanical, insulation and flame retardant properties of coir–polypropylene bio-composites - M. S. Santosh; Sanjay Purushotham; P. Gopinathan; Vijaykumar Guna; V. G. Dileepkumar; Manish Kumar; Narendra Reddy (Environmental Geochemistry and Health, 2023)

Functional diversity and behavioral changes of microbial communities under salt affected soils - Madhu Choudhary; Hanuman S. Jat; Raj Mukhopadhyay; Manish Kakraliya; Tanuja Poonia; Anshul Phogat; Bharti Dixit; Rakesh Kumar; Sanjay Arora; R.K. Yadav; S.L. Krishnamurthy; Parbodh C. Sharma (Applied Soil Ecology, 2023)

Reasons for re-hospitalization in patients with tuberculous meningitis, and its impact on outcome: a prospective observational study - Manish Ramesh Patil; Imran Rizvi; Ravindra Kumar Garg; Hardeep Singh Malhotra; Neeraj Kumar; Ravi Uniyal; Shweta Pandey; Rajesh Verma; Praveen Kumar Sharma (Acta Neurologica Belgica, 2023)

Bamboo as a sustainable crop for land restoration in India: challenges and opportunities - Ankush D. Sawarkar; Deepti D. Shrimankar; Swati C. Manekar; Manish Kumar; Phani Kumar Garlapati; Lal Singh (Environment, Development and Sustainability, 2023)

Medicinal plants, phytoconstituents and traditional formulation as potential therapies for SARS-CoV-2: a review update - Pushpendra Singh; Manish Kumar Tripathi; Kuldeep Sharma; Anudita Bhargava; Sanjay Singh Negi (Vegetos, 2023)

Learning from intermittent water supply schedules: Visualizing equality, equity, and hydraulic capacity in Bengaluru and Delhi, India - David D.J. Meyer; Saurabh Singh; Jitendra Singh; Manish Kumar; Matthew He (Science of The Total Environment, 2023)

Effects of halotolerant rhizobacteria on rice seedlings under salinity stress - F.M. Ashik Mahmud; Md. Aminul Islam; Mehede Hassan Rubel; Sanjoy Kumar Mukharjee; Manish Kumar; Prosun Bhattacharya; Firoz Ahmed (Science of The Total Environment, 2023)

Techno-economic analysis of integrated bipolar membrane electrodialysis and batch reverse osmosis for water and chemical recovery from dairy wastewater - Dipak Ankoliya; Anurag Mudgal; Manish Kumar Sinha; Philip Davies; Kiho Park; Rubén Rodríguez Alegre; Vivek Patel; Jatin Patel (Journal of Cleaner Production, 2023)

Enhancing climate resilience in businesses: The role of artificial intelligence - Shivam Singh; Manish Kumar Goyal (Journal of Cleaner Production, 2023)

Microplastics in landfill leachate: Occurrence, health concerns, and removal strategies - Sandeep Singh; Sandeep K. Malyan; Chinmay Maithani; Sujata Kashyap; Vinay Kumar Tyagi; Rajesh Singh; Sarthak Malhotra; Manish Sharma; Amit Kumar; Bijay K. Panday; R.P. Pandey (Journal of Environmental Management, 2023)

Advances in the fabrication, modification, and performance of biochar, red mud, calcium oxide, and bentonite catalysts in waste-to-fuel conversion - Armel Nganda; Pankaj Srivastava; Bhawna Yadav Lamba; Ashok Pandey; Manish Kumar (Environmental Research, 2023)

Sewage sludge derived biochar and its potential for sustainable environment in circular economy: Advantages and challenges - Ramsha Khan; Saurabh Shukla; Manish Kumar; Antonio Zuorro; Ashok Pandey (Chemical Engineering Journal, 2023)

Thermal and mechanical investigation of chemically treated hybrid biomass epoxy bio-composite: An approach of pyrolysis kinetics - Manish Choudhary; Dhananjay Singh; Sandesh K. Jain; Deepak Singh; G.L. Devnani; Sunita Singh; Anil Kumar Patel; Reeta Rani Singhania; Balendu Shekher Giri; Manish Kumar (Bioresource Technology Reports, 2023)

Solasodine Containing Solanum torvum L. Fruit Extract Prevents Chronic Constriction Injury-Induced Neuropathic Pain in Rats: In Silico and In Vivo Evidence of TRPV1 Receptor and Cytokine Inhibition - Vivek Jain; Saurabh K. Sinha; Kajol Rustage; Ashutosh Pareek; Manish Srivastava; Mukesh K. Meena; Anshul Shakya; Madan Mohan Gupta; Nitish Rai; Aaushi Pareek; Yashumati Ratan; Min Hua Chen; et al. (Molecular Neurobiology, 2023)

Comparative assessment of growth performance of indigenous and cross-bred calves subjected to combined stressors (heat and nutritional) - C. G. Shashank; R. G. Prashant; Parveen Kumar; Nitish A. Kulkarni; Manish Tiwari; S. Jayakumar; V. Sejian (International Journal of Biometeorology, 2023)

Geoheritage Sites in Kumaun Himalaya of Uttarakhand, India - Girish Ch Kothyari; P. D. Pant; Bahadur Singh Kotlia; Manish Mehta; Harshita Joshi; Dinesh S. Chauhan; Rakesh K Dumka; Khayingshing Luirei; Moulishree Joshi; Bhuvan K Tamta; Achla Joshi; Ajay Kumar Taloor; et al. (Geoheritage, 2023)

Standardization of micro-FTIR methods and applicability for the detection and identification of microplastics in environmental matrices - Chayanika Rathore; Mahua Saha; Priyansha Gupta; Manish Kumar; Akshata Naik; Jacob de Boer (Science of The Total Environment, 2023)

Eco-friendly detoxification of hazardous Congo red dye using novel fungal strain Trametes flavida WTFP2: Deduced enzymatic biomineralization process through combinatorial in-silico and in-vitro studies - Barkha Sharma; Shalini Tiwari; Rakesh Kumar; Manish Kumar; Lakshmi Tewari (Journal of Hazardous Materials, 2023)

Assessment of hydrochemical shift in riverine aquifers of the mid-Gangetic plain of Uttar Pradesh, India - Piyush Tripathi; Manish Kumar; Chandrashekhar Bhagat; Pawan Kumar Jha (Groundwater for Sustainable Development, 2023)

Association of microplastics with heavy metals and antibiotic resistance bacteria/genes in natural ecosystems - A perspective through science mapping approach - Payal Mazumder; Siddhant Dash; Manish Kumar; Rahul Silori; Ananda Tiwari; Meena Khwairakpam; Ajay S. Kalamdhad (Groundwater for Sustainable Development, 2023)

Global co-occurrences of multi-(emerging)-contaminants in the hotspots of arsenic polluted groundwater: A pattern of menace - Manish Kumar; Nilotpal Das; Sachin Tripathi; Atul Verma; Pawan Kumar Jha; Prosun Bhattacharya; Jürgen Mahlknecht (Current Opinion in Environmental Science & Health, 2023)

Antimicrobial resistance surge in the context of pollution, war, and pandemic - Rahul Silori; Vikalp Shrivastava; Payal Mazumder; Manish Kumar (Current Opinion in Environmental Science & Health, 2023)

Surface functionalized nanoparticles: A boon to biomedical science - Kanchan Upadhyay; Raunak Kumar Tamrakar; Sabu Thomas; Manish Kumar (Chemico-Biological Interactions, 2023)

Feeding the future: role of OsAUX5 in enhancing rice nutritional value - Kongkong Mondal; Manish Tiwari; Roshan Kumar Singh; Manoj Prasad; Narottam Dey (Plant Cell Reports, 2023)

Groundwater quality assessment for drinking purpose in Gurugram district of Haryana, India - Akash Tiwari; Manish Kumar; Swati Thakur; Syed Irtiza Majid (Arabian Journal of Geosciences, 2023)

Optimization of a novel trapezoidal staggered ribs configuration for enhancement of a solar air heater performance using CFD - Sarvapriya Singh; Siddharth Suman; Santanu Mitra; Manish Kumar (Environmental Science and Pollution Research, 2023)
A novel transverse trapezoidal staggered ribs configuration as artificial roughness is investigated using CFD to understand the fluid flow and heat transfer behaviors for improving the performance of a solar air heater. In addition, experimental validation of Nusselt numbers for smooth duct against CFD results is established. The staggered ribs arrangement outperforms the continuous ribs and insights obtained from the thermal-fluid flow behaviors are further applied to optimize the staggered arrangements of the rib. Reynolds number Re is varied from 5000 to 24,000, and rib parameters are optimized with a special focus on understanding the effects of discontinuous rib width ( w ) and gap width ( g ). Two widely studied shapes of rib, namely, cylindrical and rectangular, are also investigated for the transverse staggered arrangement with the same optimized parameters for the comparison of thermo-hydraulic performances. Trapezoidal ribs having discontinuous rib width of 50 mm and gap width of 10 mm give the maximum thermo-hydraulic performance of 1.57 at Reynolds number of 5000. The optimized staggered trapezoidal ribs outperform the staggered cylindrical and rectangular ribs. However, staggered rectangular ribs give the highest increase in the Nusselt number and these may be preferred for application when pressure drop is not of concern.

Stress exposure histories revealed by biochemical changes along accentuated lines in teeth - Christine Austin; Piyush Kumar; Elizabeth A. Carter; Joonsup Lee; Tanya M. Smith; Katie Hinde; Manish Arora; Peter A. Lay (Chemosphere, 2023)

Determination of thermal degradation behavior and kinetics parameters of chemically modified sun hemp biomass - Manish Choudhary; Sandesh Kumar Jain; Dhananjay Singh; Keerti Srivastava; Anil K. Patel; Jürgen Mahlknecht; Balendu Shekher Giri; Manish Kumar (Bioresource Technology, 2023)

An insight into omics analysis and metabolic pathway engineering of lignin-degrading enzymes for enhanced lignin valorization - Manish Paul; Niteesh Kumar Pandey; Ayan Banerjee; Gireesh Kumar Shroti; Preeti Tomer; Rajesh Kumar Gazara; Hrudayanath Thatoi; Thallada Bhaskar; Saugata Hazra; Debashish Ghosh (Bioresource Technology, 2023)

An innovative approach to predict atmospheric rivers: Exploring convolutional autoencoder - Shivam Singh; Manish Kumar Goyal (Atmospheric Research, 2023)

Biomechanical analysis of Instrumented decompression and Interbody fusion procedures in Lumbar spine: a finite element analysis study - Shivam Saini; Nagaraj Manju Moger; Manish Kumar; Subrato Sarkar; Samarth Mittal; Syed Ifthekar; Kaustubh Ahuja; Indra Vir Singh; Pankaj Kandwal (Medical & Biological Engineering & Computing, 2023)

Fish parasites as proxy bioindicators of degraded water quality of River Saraswati, India - Jayanta Kumar Biswas; Sasanka Pramanik; Manish Kumar (Environmental Monitoring and Assessment, 2023)

RETRACTED: Rice straw derived graphene-silica based nanocomposite and its application in improved co-fermentative microbial enzyme production and functional stability - Mohammed Asiri; Neha Srivastava; Rajeev Singh; Amer Al Ali; Subhash C. Tripathi; Abdulaziz Alqahtani; Mohd Saeed; Manish Srivastava; Ashutosh Kumar Rai; Vijai Kumar Gupta (Science of The Total Environment, 2023)

Modeling of standardized groundwater index of Bihar using machine learning techniques - Shomya Kumari; Deepak Kumar; Manish Kumar; Chaitanya B. Pande (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Carbon and water footprints of major crop production in India - Amaresh Kumar NAYAK; Rahul TRIPATHI; Manish DEBNATH; Chinmaya Kumar SWAIN; Biswaranjan DHAL; Shanmugam VIJAYKUMAR; Anshuman Debasis NAYAK; Sangita MOHANTY; Mohammad SHAHID; Anjani KUMAR; Manoj RAJAK; Khitish Chandra MOHARANA; et al. (Pedosphere, 2023)

Carbon footprint assessment of a wood multi-residential building considering biogenic carbon - Claudiane M. Ouellet-Plamondon; Livia Ramseier; Maria Balouktsi; Laetitia Delem; Greg Foliente; Nicolas Francart; Antonio Garcia-Martinez; Endrit Hoxha; Thomas Lützkendorf; Freja Nygaard Rasmussen; Bruno Peuportier; Jarred Butler; et al. (Journal of Cleaner Production, 2023)

Screening of pharmaceutical and personal care products (PPCPs) along wastewater treatment system equipped with root zone treatment: A potential model for domestic waste leachate management - Manish Kumar; Rahul Silori; Payal Mazumder; Syed Mohammad Tauseef (Journal of Environmental Management, 2023)

Generation of map on natural environmental background absorbed dose rate in India - Manish K. Mishra; S.K. Jha; Aditi C. Patra; D.G. Mishra; S.K. Sahoo; S.K. Sahu; Gopal P. Verma; Shashank S. Saindane; Pratip Mitra; S. Garg; Vandana Pulhani; I.V. Saradhi; et al. (Journal of Environmental Radioactivity, 2023)

Moving forward with COVID-19: Future research prospects of wastewater-based epidemiology methodologies and applications - Guangming Jiang; Yanchen Liu; Song Tang; Masaaki Kitajima; Eiji Haramoto; Sudipti Arora; Phil M. Choi; Greg Jackson; Patrick M. D'Aoust; Robert Delatolla; Shuxin Zhang; Ying Guo; et al. (Current Opinion in Environmental Science & Health, 2023)

Transparent-flexible thermoelectric module from In/Ga co-doped ZnO thin films - Athorn Vora-ud; Anh Tuan Thanh Pham; Dai Cao Truong; Somporn Thoawankeaw; Hoa Thi Lai; Thu Bao Nguyen Le; Nhat Minh Quang Tran; Mekhala Insawang; Pennapa Muthitamongkol; Mati Horprathum; Manish Kumar; Sungkyun Park; et al. (Chemical Engineering Journal, 2023)

Isomeric acceptors incorporation enables 18.1% efficiency ternary organic solar cells with reduced trap-assisted charge recombination - Jie Lv; Qianguang Yang; Wanyuan Deng; Haiyan Chen; Manish Kumar; FuQing Zhao; Shirong Lu; Hanlin Hu; Zhipeng Kan (Chemical Engineering Journal, 2023)

Neuroprotective Effects of Carbonic Anhydrase Inhibition and Cyclic Adenosine Monophosphate Activation in Mouse Model of Transient Global Cerebral Ischemia and Reperfusion - Manish Kumar; Komalpreet Kaur; Thakur Gurjeet Singh (NeuroMolecular Medicine, 2023)

State of art soft computing based simulation models for bearing capacity of pile foundation: a comparative study of hybrid ANNs and conventional models - Manish Kumar; Vinay Kumar; Balaji Ganesh Rajagopal; Pijush Samui; Avijit Burman (Modeling Earth Systems and Environment, 2023)

Recent advancements in antimony (Sb) removal from water and wastewater by carbon-based materials: a systematic review - Kumar Abhishek; Neha Parashar; Manvendra Patel; Subrata Hait; Anamika Shrivastava; Pooja Ghosh; Prabhakar Sharma; Ashok Pandey; Manish Kumar (Environmental Monitoring and Assessment, 2023)

Retaliation of Alstonia scholaris (L.) R.Br. to caesium and strontium in hydroponics: effect on morpho-physiology and induction of enzymatic defence - B. S. Manisha Singh; Nabin Kumar Dhal; Manish Kumar; Dinakrushna Mohapatra; Hariharan Seshadri; Monalisha Nayak (Environmental Monitoring and Assessment, 2023)

Effect of Spray Operating Parameters on Viability of Bacillus thuringiensis Based Biopesticide Under Laboratory Condition - Manish Kumar; Champat Raj Mehta; Vinod Kumar Bhargav; Manoj Kumar Tripathi; Kamal Nayan Agrawal; Vattiprolu Bhushana Babu (Agricultural Research, 2023)

Contemporary Drift in Emerging Micro(nano)plastics Removal and Upcycling Technologies from Municipal Wastewater Sludge: Strategic Innovations and Prospects - Vinay; Deepti Surana; Pooja Ghosh; Manish Kumar; Sunita Varjani; Vivek Kumar; Giorgio Mannina (Current Pollution Reports, 2023)

Isolation and whole genome sequencing of Pseudomonas aeruginosa strain RK1 and its biocontrol potential against phytopathogens of rice - Ram Jatan; Richa Kamboj; Manish Kumar; Nitin Kumar; Priyanka Jain; Charu Lata; Joshitha Vijayan; Vandana Rai; Nagendra Kumar Singh; Deepak Singh Bisht (Biologia, 2023)

Potential arsenic–chromium–lead Co-contamination in the hilly terrain of Arunachal Pradesh, north-eastern India: Genesis and health perspective - Ritusmita Goswami; Chandrashekhar Bhagat; Igo Lollen; Nikita Neog; Umesh B. Barache; Ritu Thakur; Jurgen Mahlknecht; Manish Kumar (Chemosphere, 2023)

Revealing the mode of action of Phenylalanine application in inducing fruit resistance to fungal pathogens - Manish Kumar Patel; Dalia Maurer; Oleg Feyngenberg; Danielle Duanis-Assaf; Noa Sela; Rinat Ovadia; Michal Oren-Shamir; Noam Alkan (Postharvest Biology and Technology, 2023)

Congo red dye adsorption onto cationic amino-modified walnut shell: Characterization, RSM optimization, isotherms, kinetics, and mechanism studies - Pawan Kumar Rose; Rajat Kumar; Rakesh Kumar; Manish Kumar; Prabhakar Sharma (Groundwater for Sustainable Development, 2023)

Probable maximum precipitation analysis of high rainfall regions in India - Durga Prasad Panday; Akansha Singh; Siddhant; Aditya Ketu; Raja; Asok Raja S K; Manish Kumar (Groundwater for Sustainable Development, 2023)

Investigation on combustion characteristics of acetone-butanol-ethanol/Jet A-1 mixture in a Swirl-stabilized combustor for its potential application in gas turbine engines - Manish Kumar; Srinibas Karmakar; Cheng Tung Chong (Fuel, 2023)

Global distribution of pesticides in freshwater resources and their remediation approaches - Sandeep Singh; Meenakshi Rawat; Sandeep K. Malyan; Rajesh Singh; Vinay Kumar Tyagi; Kaptan Singh; Sujata Kashyap; Sumant Kumar; Manish Sharma; B.K. Panday; R.P. Pandey (Environmental Research, 2023)

Microbial machinery dealing diverse aromatic compounds: Decoded from pelagic sediment ecogenomics in the gulfs of Kathiawar Peninsula and Arabian Sea - Neelam M. Nathani; Chandrashekar Mootapally; Parth Sharma; Solly Solomon; Rakesh Kumar; Abhay B. Fulke; Manish Kumar (Environmental Research, 2023)

Quantifying and reducing concentration polarization in reverse osmosis systems - Weiliang Bai; Laxmicharan Samineni; Progga Chirontoni; Igor Krupa; Peter Kasak; Anton Popelka; Navid B. Saleh; Manish Kumar (Desalination, 2023)

Insights of auxin signaling F-box genes in wheat (Triticum aestivum L.) and their dynamic expression during the leaf rust infection - Anupama Gidhi; Archit Mohapatra; Mehar Fatima; Shailendra Kumar Jha; Manish Kumar; Kunal Mukhopadhyay (Protoplasma, 2023)

Comparative study on the physicochemical properties, structural, and functional group analysis of pectin extracted from underutilized bael (Aegle marmelos) pulp, shell, and seed - Ragini Surolia; Manish Kumar Dubey; Tripti Bhatnagar; Anuradha Singh (Vegetos, 2023)

Auxin–cytokinin interplay shapes root functionality under low-temperature stress - Manish Tiwari; Ritesh Kumar; Senthil Subramanian; Colleen J. Doherty; S.V. Krishna Jagadish (Trends in Plant Science, 2023)

Effective flue gas desulfurization and denitrification using a one-step combined ozone and UV technique - Snigdha Khuntia; Manish Kumar Sinha; Parveen Dalal; Arunima Singh (Journal of Cleaner Production, 2023)

Development of genomic SSR markers in Gymnema sylvestre (Retz.) R.Br. ex Sm. using next generation DNA sequencing and their application in genetic diversity analysis - A.C. Polaiah; Parthvee R. Damor; R.N. Reddy; P. Manivel; K.T. Shivakumara; Manish K. Suthar; V. Thondaiman; G.N. Manjesh; K.H. Bindu; Jitendra Kumar (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Retrieving canopy nitrogen concentration and aboveground biomass with deep learning for ryegrass and barley: Comparing models and determining waveband contribution - Manish Kumar Patel; José Padarian; Andrew W. Western; Glenn J. Fitzgerald; Alex B. McBratney; Eileen M. Perry; Helen Suter; Dongryeol Ryu (Field Crops Research, 2023)

Occurrences of UV filters, endocrine disruptive chemicals, alkyl phenolic compounds, fragrances, and hormones in the wastewater and coastal waters of the Antarctica - Keshava Balakrishna; Yerabham Praveenkumarreddy; D'Souza Nishitha; Chikmagalur Mallappa Gopal; Jayakrishna Kanhangad Shenoy; Krishnamurthy Bhat; Neloy Khare; Kiran Dhangar; Manish Kumar (Environmental Research, 2023)

Genome-wide identification and annotation of SNPs and their mapping in candidate genes related to milk production and fertility traits in Badri cattle - Javid Ur Rahman; Devendra Kumar; Satya Pal Singh; Bijendra Narayan Shahi; Ashis Kumar Ghosh; Manish Kumar Verma; Abhishek Pathak; Aashaq Hussain Dar; Anil Kumar; Rabendra Kumar Sharma (Tropical Animal Health and Production, 2023)

At the intersection of life cycle assessment and indirect greenhouse gas emissions accounting - Amma Asantewaa Agyei Boakye; Terrie Boguski; Sarah Cashman; Christoph Koffler; Ashley Kreuder; Manish Kumar; Naveen Kumar Vipparla; Lisa Peterson (The International Journal of Life Cycle Assessment, 2023)

Bioactivity of Zanthoxylum armatum fruit extract against Spodoptera frugiperda and Tuta absoluta - Dnyaneshwar M. Firake; Rituparna Ghosh; Manish Kumar; Arockiasamy Arun Prince Milton; Raj Kumari Sanjukta; Gajanan T. Behere; Sagar Pandit (Journal of Plant Diseases and Protection, 2023)

Genetic diversity and population structure assessment of Hellenia speciosa from Indian agro-ecological regions using inter-simple sequence repeat markers - Kamasamudra N. Prabhu; Vereena Rodrigues; Amit Kumar; Manish Kumar; Sharad Srivastava; Ashutosh K. Shukla; Velusamy Sundaresan (Horticulture, Environment, and Biotechnology, 2023)

Experimental investigation of a desalination system based on evacuated tube collector - Abhishek Tiwari; Manish K. Rathod; Amit Kumar (Environment, Development and Sustainability, 2023)

Resolution of conflict of reduced sludge production with EBPR by coupling OSA to A2/O process in a pilot scale SBR - Anwar Khursheed; Faris Mohammad A. Munshi; Abdulaziz Ibrahim Almohana; Abdulrhman Fahmi Alali; Mohab Amin Kamal; Shamshad Alam; Omar Alrehaili; Dar Tafazul Islam; Manish Kumar; Sunita Varjani; A.A. Kazmi; Vinay Kumar Tyagi (Chemosphere, 2023)

Efficient CO2/CH4 separation using [Bmim][Ac]/Pebax-1657 supported ionic liquid membranes and its prediction by density functional theory - Tushar Patil; Swapnil Dharaskar; Manish kumar Sinha; Jalaja Pandya; Satyam Shinde; Surendra Sasi kumar Jampa; Mika Sillanpaa; Chang Yoo (International Journal of Greenhouse Gas Control, 2023)

Prospects of microbial cellulase production using banana peels wastes for antimicrobial applications - Rajeev Singh; Abdullah Ali Saati; Hani Faidah; Farkad Bantun; Naif A. Jalal; Shafiul Haque; Ashutosh Kumar Rai; Manish Srivastava (International Journal of Food Microbiology, 2023)

Arctic climate-Indian monsoon teleconnection during the last millennium revealed through geochemical proxies from an Arctic fjord - Vikash Kumar; Manish Tiwari; Dmitry V. Divine; Matthias Moros; Arto Miettinen (Global and Planetary Change, 2023)

Phenylalanine induces mango fruit resistance against chilling injuries during storage at suboptimal temperature - Manish Kumar Patel; Michal Fanyuk; Oleg Feyngenberg; Dalia Maurer; Noa Sela; Rinat Ovadia; Michal Oren-Shamir; Noam Alkan (Food Chemistry, 2023)

Review on distribution, fate, and management of potentially toxic elements in incinerated medical wastes - Shiv Bolan; Lokesh P. Padhye; Manish Kumar; Vasileios Antoniadis; Srinidhi Sridharan; Yuanyuan Tang; Narendra Singh; Choolaka Hewawasam; Meththika Vithanage; Lal Singh; Jörg Rinklebe; Hocheol Song; et al. (Environmental Pollution, 2023)

Drinking water treatment and associated toxic byproducts: Concurrence and urgence - Manish Kumar; Shashank Shekhar; Rakesh Kumar; Pawan Kumar; Muthusamy Govarthanan; Tushara Chaminda (Environmental Pollution, 2023)

Understanding the underestimated: Occurrence, distribution, and interactions of microplastics in the sediment and soil of China, India, and Japan - Rahul Silori; Vikalp Shrivastava; Payal Mazumder; Chandrashekar Mootapally; Ashok Pandey; Manish Kumar (Environmental Pollution, 2023)

Bioenhancer potential of Aegle marmelos (L.) Corrêa essential oil with antifungal drugs and its mode of action against Candida albicans - Riya Bhattacharya; Anuradha Sourirajan; Prashant Sharma; Anil Kumar; Navneet Kumar Upadhyay; Rakesh Kumar Shukla; Kamal Dev; Balaji Krishnakumar; Manish Singh; Debajyoti Bose (Biocatalysis and Agricultural Biotechnology, 2023)

Modeling Soil Water Retention Under Different Pressures Using Adaptive Neuro-Fuzzy Inference System - Ahmed Elbeltagi; R. K. Jaiswal; R. V. Galkate; Manish Kumar; A. K. Lohani; Jaiveer Tyagi (Water Resources Management, 2023)
Soil Water Retention (SWR) is an important process in drainage, surface, and groundwater partitioning, hydrological modeling, water supply for irrigation, etc. Assessment of SWR characteristics is complex and difficult to conduct spatially in varied locations. Therefore, Pedotransfer Functions (PTF) which are empirical relations with easily available physical properties are commonly used. In the present study, the evaluation of soil moisture at different suction pressure using the adaptive neuro-fuzzy inference systems (ANFIS) approach based on soil texture (percentage of gravel, sand, silt, and clay) and compare with the PTF approach. The analysis was conducted for a total of eleven sites of two adjoining commands in India. The pressure plate apparatus along with coarse and fine sieve analysis, titration, and other tests were carried out to determine SWR, texture, organic carbon, and bulk density. The comparative analysis of Nash–Sutcliffe efficiencies of the best-fitted PTF models and ANFIS model confirmed that the ANFIS model can capture all variations of soil texture across all sites with Nash–Sutcliffe efficiency of nearly 1.0 indicative of an exact match, while no single PTF-based model can be used for all the sites. Therefore, the ANFIS model can be used to model soil water retention for the central India region using easily available texture properties of soils.

Pharmacognostic and Nutraceutical Potential of Momordica Dioica Roxb. Ex willd. Fruit - Akanksha Srivastava; Ankita Misra; Mridul Kant Chaudhary; Pushpendra Kumar Shukla; Manish Kumar; Sharad Srivastava (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

Stem cell therapy: a novel approach against emerging and re-emerging viral infections with special reference to SARS-CoV-2 - Vishal Khandelwal; Tarubala Sharma; Saurabh Gupta; Shoorvir Singh; Manish Kumar Sharma; Deepak Parashar; Vivek K. Kashyap (Molecular Biology Reports, 2023)

Glacier–glacial lake changes and modeling glacial lake outburst flood in Upper Ganga Basin, India - Manish Rawat; Rayees Ahmed; Sanjay Kumar Jain; Anil Kumar Lohani; Gopinadh Rongali; Kailash Chandra Tiwari (Modeling Earth Systems and Environment, 2023)

Evaluation of heavy metal and microbial contamination in various water resources of West and North Sikkim, India - Horthing V. Zimik; Anil Kumar Misra; Rakesh Kr. Ranjan; Nishchal Wanjari; Smriti Basnett; Goshaidas Roy; Anirudra Rai; Khushboo Sharma; Manish Kumar Keshare; Swapan Dolui (Environment, Development and Sustainability, 2023)

Origin of exotic blocks in Himalaya: a case study from Zildat ophiolitic mélange, Indus suture zone, Ladakh, India - Aditya Kharya; Shashi Ranjan Rai; Himanshu K. Sachan; Manish Kumar; Vikash Kumar (Carbonates and Evaporites, 2023)

Role of large-scale climate oscillations in precipitation extremes associated with atmospheric rivers: nonstationary framework - Shivam Singh; Manish Kumar Goyal; Srinidhi Jha (Hydrological Sciences Journal, 2023)

Nitrogen dioxide as proxy indicator of air pollution from fossil fuel burning in New Delhi during lockdown phases of COVID-19 pandemic period: impact on weather as revealed by Sentinel-5 precursor (5p) spectrometer sensor - Pavan Kumar; Aishwarya; Prashant Kumar Srivastava; Manish Kumar Pandey; Akash Anand; Jayanta Kumar Biswas; Martin Drews; Manmohan Dobriyal; Ram Kumar Singh; Manuel De la Sen; Sati Shankar Singh; Ajai Kumar Pandey; et al. (Environment, Development and Sustainability, 2023)

Current research trends on emerging contaminants pharmaceutical and personal care products (PPCPs): A comprehensive review - Manish Kumar; Srinidhi Sridharan; Ankush D. Sawarkar; Adnan Shakeel; Prathmesh Anerao; Giorgio Mannina; Prabhakar Sharma; Ashok Pandey (Science of The Total Environment, 2023)

Waste to catalyst: Role of agricultural waste in water and wastewater treatment - Manish Kumar; Selvaraj Ambika; Aydin Hassani; P.V. Nidheesh (Science of The Total Environment, 2023)

Prevalence of organic micropollutants in the Yamuna River, Delhi, India: seasonal variations and governing factors - Soma Mishra; Pradeep Kumar; Indu Mehrotra; Manish Kumar (Science of The Total Environment, 2023)

Estimation of time dependent scour depth around circular bridge piers: Application of ensemble machine learning methods - Sanjit Kumar; Manish Kumar Goyal; Vishal Deshpande; Mayank Agarwal (Ocean Engineering, 2023)

Pollution free UV-C radiation to mitigate COVID-19 transmission - Ashutosh Kumar; Abhishek Raj; Ankit Gupta; Sneha Gautam; Manish Kumar; Hemant Bherwani; Avneesh Anshul (Gondwana Research, 2023)

A thermo-chemical and biotechnological approaches for bamboo waste recycling and conversion to value added product: Towards a zero-waste biorefinery and circular bioeconomy - Zheli Ding; Sanjeev Kumar Awasthi; Manish Kumar; Vinay Kumar; Andrei Mikhailovich Dregulo; Vivek Yadav; Raveendran Sindhu; Parameswaran Binod; Surendra Sarsaiya; Ashok Pandey; Mohammad J. Taherzadeh; Rashmi Rathour; et al. (Fuel, 2023)

EI/IOT of PFCs: Environmental impacts/interactions, occurrences, and toxicities of perfluorochemicals - Armel Nganda; Manish Kumar; Vismaya Uday; Pankaj Srivastava; Bhaskar Jyoti Deka; Faiza Zitouni; Jurgen Mahlknecht (Environmental Research, 2023)

Janus kinase/signal transducers and activator of transcription (JAK/STAT) and its role in Lung inflammatory disease - Manish Purohit; Gaurav Gupta; Obaid Afzal; Abdulmalik Saleh Alfawaz Altamimi; Sami I. Alzarea; Imran Kazmi; Waleed Hassan Almalki; Monica Gulati; Indu Pal Kaur; Sachin Kumar Singh; Kamal Dua (Chemico-Biological Interactions, 2023)

Artificial intelligence and machine learning-based monitoring and design of biological wastewater treatment systems - Nitin Kumar Singh; Manish Yadav; Vijai Singh; Hirendrasinh Padhiyar; Vinod Kumar; Shashi Kant Bhatia; Pau-Loke Show (Bioresource Technology, 2023)

Impact of nanomaterials on sustainable pretreatment of lignocellulosic biomass for biofuels production: An advanced approach - Neha Srivastava; Rajeev Singh; Manish Srivastava; Akbar Mohammad; Steve Harakeh; Ravindra Pratap Singh; Dan Bahadur Pal; Shafiul Haque; Hossam H. Tayeb; Mohammed Moulay; Vijai Kumar Gupta (Bioresource Technology, 2023)

Enhancement in functional stability of microbial endoglanases produced using paddy straw via treatment with manganese oxide based porous nanocomposite synthesized from mixed fruit waste - Neha Srivastava; Rajeev Singh; Manish Srivastava; Akbar Mohammad; Steve Harakeh; Shafiul Haque; P.K. Mishra; Hossam H. Tayeb; Mohammed Moulay; Vijai Kumar Gupta (Bioresource Technology, 2023)

Selective COX-2 Inhibitor Etoricoxib’s Liposomal Formulation Attenuates M2 Polarization of TAMs and Enhances its Anti-metastatic Potential - Usmani Mohammed Akif; Javed Miyan; Rafquat Rana; Moinuddin; Narayan Kumar Goswami; Tanzeela; Smrati Bhadauria; Manish Kumar Chourasia (Pharmaceutical Research, 2023)

A comprehensive review of solar-driven desalination systems and its advancements - Abhishek Tiwari; Manish K. Rathod; Amit Kumar (Environment, Development and Sustainability, 2023)

Prediction of meteorological drought and standardized precipitation index based on the random forest (RF), random tree (RT), and Gaussian process regression (GPR) models - Ahmed Elbeltagi; Chaitanya B. Pande; Manish Kumar; Abebe Debele Tolche; Sudhir Kumar Singh; Akshay Kumar; Dinesh Kumar Vishwakarma (Environmental Science and Pollution Research, 2023)

Assessment of genetic diversity in Tecomella undulata by using ISSR markers - Vijay Daneva; R. S. Beniwal; Subhash Kajla; Anil Kumar Poonia; Manish Kumar; Kajal (Vegetos, 2023)

Glacial lake outburst flood risk assessment using remote sensing and hydrodynamic modeling: a case study of Satluj basin, Western Himalayas, India - Manish Rawat; Sanjay Kumar Jain; Rayees Ahmed; Anil Kumar Lohani (Environmental Science and Pollution Research, 2023)

Aggregation behaviour of black carbon in aquatic solution: Effect of ionic strength and coexisting metals - Kiran Dhangar; Manish Kumar; Marwan Aouad; Jurgen Mahlknecht; Nirav P. Raval (Chemosphere, 2023)

Monkeypox outbreak: Wastewater and environmental surveillance perspective - Ananda Tiwari; Sangeet Adhikari; Devrim Kaya; Md. Aminul Islam; Bikash Malla; Samendra P. Sherchan; Ahmad I. Al-Mustapha; Manish Kumar; Srijan Aggarwal; Prosun Bhattacharya; Kyle Bibby; Rolf U. Halden; et al. (Science of The Total Environment, 2023)

Rheology of nano ZnO - Hydroxypropyl Methylcellulose (HPMC) based suspensions and structural properties of resulting films - Gulshan Kumar Malik; Jayeeta Mitra; Manish Kaushal (Journal of Food Engineering, 2023)

Correlation between SARS-CoV-2 RNA concentration in wastewater and COVID-19 cases in community: A systematic review and meta-analysis - Xuan Li; Shuxin Zhang; Samendra Sherchan; Gorka Orive; Unax Lertxundi; Eiji Haramoto; Ryo Honda; Manish Kumar; Sudipti Arora; Masaaki Kitajima; Guangming Jiang (Journal of Hazardous Materials, 2023)

RETRACTED: Enhancement of combustion characteristics of waste cooking oil biodiesel using TiO2 nanofluid blends through RSM - Harveer Singh Pali; Abhishek Sharma; Manish Kumar; Vivek Anand Annakodi; Van Nhanh Nguyen; Nishant Kumar Singh; Yashvir Singh; Dhinesh Balasubramanian; Balakrishnan Deepanraj; Thanh Hai Truong; Phuoc Quy Phong Nguyen (Fuel, 2023)

Phytochemical screening, antibacterial, anti-biofilm and quorum sensing inhibiting activity of Alpinia nigra leaf extract against infectious pathogen Pseudomonas aeruginosa PAO1 - Manish Kumar Gupta; Rashmi Singh; Latha Rangan (Food Control, 2023)

Photodegradation of a mixture of five pharmaceuticals commonly found in wastewater: Experimental and computational analysis - Sanjeeb Mohapatra; Daniel Snow; Patrick Shea; Andy Gálvez-Rodríguez; Manish Kumar; Lokesh P. Padhye; Suparna Mukherji (Environmental Research, 2023)

A sustainable approach to the degradation of dyes by fungal species isolated from industrial wastewaters: Performance, parametric optimization, kinetics and degradation mechanism - Roshan Gul; Priyanka Sharma; Raman Kumar; Ahmad Umar; Ahmed A. Ibrahim; Mohsen A.M. Alhamami; Vivek Sheel Jaswal; Manish Kumar; Ashutosh Dixit; Sotirios Baskoutas (Environmental Research, 2023)

Ultra-fast and low-cost electroactive biochar production for electroactive-constructed wetland applications: A circular concept for plant biomass utilization - Yamini Mittal; Pratiksha Srivastava; Naresh Kumar; Manish Kumar; Saroj Kumar Singh; Fernando Martinez; Asheesh Kumar Yadav (Chemical Engineering Journal, 2023)

Butyl butyrate, Jet A-1 and their blends: Combustion performance in the swirl stabilized burner at different inlet air temperature - Manish Kumar; Srinibas Karmakar (Biomass and Bioenergy, 2023)

Sustainable utilization of dairy waste paneer whey by Pediococcus pentosaceus NCDC 273 for lactic acid production - Surya Kant Verma; Daraksha Iram; Manish Singh Sansi; Kush Kumar Pandey; Shilpa Vij; Shiv Kumar Sood (Biocatalysis and Agricultural Biotechnology, 2023)

Drought indicator analysis and forecasting using data driven models: case study in Jaisalmer, India - Ahmed Elbeltagi; Manish Kumar; N. L. Kushwaha; Chaitanya B. Pande; Pakorn Ditthakit; Dinesh Kumar Vishwakarma; A. Subeesh (Stochastic Environmental Research and Risk Assessment, 2023)

Screening of Capsicum germplasm and inheritance of resistance to chilli leaf curl virus - Rajeev Kumar Yadav; Krishna M. Reddy; K. V. Ashwathappa; Manish Kumar; P. Naresh; Madhavi K. Reddy (Indian Phytopathology, 2022)

Moderate resolution LAI prediction using Sentinel-2 satellite data and indirect field measurements in Sikkim Himalaya - Sujoy Mudi; Somnath Paramanik; Mukunda Dev Behera; A Jaya Prakash; Nikhil Raj Deep; Manish P. Kale; Shubham Kumar; Narpati Sharma; Prerna Pradhan; Manoj Chavan; Partha Sarathi Roy; Dhiren G. Shrestha (Environmental Monitoring and Assessment, 2022)

Land surface temperature distribution in Mahanadi delta: impact of land use land cover change - Rahul Tripathi; Khitish Chandra Moharana; Dibyendu Chatterjee; Manish Debnath; Sangita Mohanty; Anjani Kumar; Shanmugam Vijayakumar; Bhabani Shankar Satapathy; Bandaru Raghavendra Goud; Amaresh Kumar Nayak (Arabian Journal of Geosciences, 2022)

Correction: Cadastral resurvey and integration of geospatial technique using high-resolution satellite image (HRSI): a case study in Indian district - Hemant Dansena; Amit Prakash Multaniya; Manish Kumar Sinha; Kamal Kishor Sahu; M. K. Beg (Applied Geomatics, 2022)

Cadastral resurvey and integration of geospatial technique using high-resolution satellite image (HRSI): a case study in Indian district - Hemant Dansena; Amit Prakash Multaniya; Manish Kumar Sinha; Kamal Kishor Sahu; M. K. Beg (Applied Geomatics, 2022)

Assessment and characterization of bioaerosols from an indoor environment-operated wastewater management facility: unraveling pathogenicity in research laboratories - Nitin Kumar Singh; Gaurav Sanghvi; Manish Yadav; Hirendrasinh Padhiyar; Abhishek Gupta; Johnson Christian; Arti Thanki (Aerobiologia, 2022)

Walking through crossroads–rice responses to heat and biotic stress interactions - Ritesh Kumar; Rajeev N. Bahuguna; Manish Tiwari; Madan Pal; Viswanathan Chinnusamy; Sheshshayee Sreeman; Raveendran Muthurajan; S. V. Krishna Jagadish (Theoretical and Applied Genetics, 2022)

Seasonal immune rhythm of leukocytes in the freshwater snakehead fish, Channa punctatus - Ajay Kumar Bhardwaj; Rakesh Kumar Chandra; Atanu Kumar Pati; Manish Kumar Tripathi (Journal of Comparative Physiology B, 2022)

Correction to: Spatio-temporal variability and trend analysis of rainfall in Wainganga river basin, Central India, and forecasting using state-space models - Nanabhau S. Kudnar; Pranaya Diwate; Varun Narayan Mishra; Prashant K. Srivastava; Akshay Kumar; Manish Pandey (Theoretical and Applied Climatology, 2022)

Spatio-temporal variability and trend analysis of rainfall in Wainganga river basin, Central India, and forecasting using state-space models - Nanabhau S. Kudnar; Pranaya Diwate; Varun Narayan Mishra; Prashant K. Srivastava; Akshay Kumar; Manish Pandey (Theoretical and Applied Climatology, 2022)

Modelling daily reference evapotranspiration based on stacking hybridization of ANN with meta-heuristic algorithms under diverse agro-climatic conditions - Ahmed Elbeltagi; Nand Lal Kushwaha; Jitendra Rajput; Dinesh Kumar Vishwakarma; Luc Cimusa Kulimushi; Manish Kumar; Jingwen Zhang; Chaitanya B. Pande; Pandurang Choudhari; Sarita Gajbhiye Meshram; Kusum Pandey; Parveen Sihag; et al. (Stochastic Environmental Research and Risk Assessment, 2022)

Investigating the spatio-temporal correlation between urban heat island and atmospheric pollution island interaction over Delhi, India using geospatial techniques - Manish Kumar Mishra; Aneesh Mathew (Arabian Journal of Geosciences, 2022)

Mechanisms and Pathways for Coordinated Control of Fine Particulate Matter and Ozone - Narendra Ojha; Meghna Soni; Manish Kumar; Sachin S. Gunthe; Ying Chen; Tabish U. Ansari (Current Pollution Reports, 2022)

Genotoxicity of sodium arsenite on Vicia faba root meristematic cells - Tajinder Kaur; Manish Kumar; Satwinderjeet Kaur (The Nucleus, 2022)

Neuroprotective Effects of Theobromine in permanent bilateral common carotid artery occlusion rat model of cerebral hypoperfusion - Javeed Ahmad Bhat; Manish Kumar (Metabolic Brain Disease, 2022)

Promising protein biomarkers in the early diagnosis of Alzheimer’s disease - Lalit Sharma; Aditi Sharma; Deepak Kumar; Manish Kumar Asthana; H. Lalhlenmawia; Ashwani Kumar; Sanjib Bhattacharyya; Deepak Kumar (Metabolic Brain Disease, 2022)

Characterization of thermo-physiological, hematological, and molecular changes in response to seasonal variations in two tropically adapted native cattle breeds of Bos indicus lineage in hot arid ambience of Thar Desert - Gayatri Gujar; Vijay Kumar Choudhary; Prince Vivek; Monika Sodhi; Monika Choudhary; Manish Tiwari; Nampher Masharing; Manishi Mukesh (International Journal of Biometeorology, 2022)

Study on effect of tire burning on particulate matter concentration and respiratory deposition doses to the workers and inhabitants during road pavement activity - Shweta Kumari; Suresh Pandian Elumalai; Manish Kumar Jain (Air Quality, Atmosphere & Health, 2022)

Clarify the nexus between life cycle assessment and circularity indicators: a SETAC/ACLCA interest group - Michael Saidani; Ashley Kreuder; Guillermo Babilonia; Pahola Thathiana Benavides; Nick Blume; Seth Jackson; Christoph Koffler; Manish Kumar; Christine Minke; Jennifer Richkus; Cheryl Smith; Michele Wallace (The International Journal of Life Cycle Assessment, 2022)

Improved neuroprotective activity of Fisetin through SNEDDS in ameliorating the behavioral alterations produced in rotenone-induced Parkinson’s model - Rajan Kumar; Rakesh Kumar; Navneet Khurana; Sachin Kumar Singh; Shelly Khurana; Surajpal Verma; Neha Sharma; Manish Vyas; Kamal Dua; Rubiya Khursheed; Ankit Awasthi; Sukriti Vishwas (Environmental Science and Pollution Research, 2022)

Appraisal of fluoroquinolone-loaded carubinose-linked hybrid nanoparticles for glycotargeting to alveolar macrophages - Priyanka Maurya; Ravi Saklani; Samipta Singh; Raquibun Nisha; Ravi Raj Pal; Nidhi Mishra; Priya Singh; Abhiram Kumar; Manish K. Chourasia; Shubhini A. Saraf (Drug Delivery and Translational Research, 2022)

Pathotyping and antimicrobial susceptibility testing of Escherichia coli isolates from neonatal calves - Damini P. Khawaskar; D. K. Sinha; Michael V. Lalrinzuala; V. Athira; Manish Kumar; Lalsangzuala Chhakchhuak; K. Mohanapriya; I. Sophia; Abhishek; O. R. Vinodh Kumar; Pallab Chaudhuri; B. R. Singh; et al. (Veterinary Research Communications, 2022)

Impacts of soil qualities and Prosopis juliflora on density, canopy volume and community position of Leptadenia pyrotechnica in Arid regions of India - Manish Mathur; Mahesh Kumar; C. B. Pandey (Tropical Ecology, 2022)

Intraspecific Variation in Gloriosa Superba (L.) Population from Western Himalayas (India) and Evaluation of in vitro Antigout Potential - Ankita Misra; Pushpendra Kumar Shukla; Manish Kumar; Poonam Rawat; Sharad Srivastava (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Inferring the factors for origin and diversifications of endemic Himalayan flora using phylogenetic models - Kumar Manish; Maharaj K. Pandit; Sandeep Sen (Modeling Earth Systems and Environment, 2022)

Mineralogical and fluid inclusion constraints on the formation of the Karakorum Migmatite: implications for H2O-fluxed melting and exhumation of the South Tibetan Crust - Vikash Kumar; Ian W. Honsberger; Aditya Kharya; Himanshu K. Sachan; Shashi Ranjan Rai; Manish Kumar (Contributions to Mineralogy and Petrology, 2022)

Enrichment of primary macronutrients in biochar for sustainable agriculture: A review - Adnan Asad Karim; Manish Kumar; Ekta Singh; Aman Kumar; Sunil Kumar; Arati Ray; Nabin Kumar Dhal (Critical Reviews in Environmental Science and Technology, 2022)

Applications of Data-driven Models for Daily Discharge Estimation Based on Different Input Combinations - Manish Kumar; Ahmed Elbeltagi; Chaitanya B. Pande; Ali Najah Ahmed; Ming Fai Chow; Quoc Bao Pham; Anuradha Kumari; Deepak Kumar (Water Resources Management, 2022)

Mesenchymal Stem Cell Therapy in the Treatment of Neurodegenerative Cerebellar Ataxias: a Systematic Review and Meta-analysis - Manish Bhartiya; Amit Kumar; Rakesh K. Singh; Divya M Radhakrishnan; Roopa Rajan; Achal Kumar Srivastava (The Cerebellum, 2022)

Synthesis and characterization of zinc derivatized 3, 5-dihydroxy 4′, 7-dimethoxyflavone and its anti leishmaniasis activity against Leishmania donovani - Manish Kumar Gupta; Adarsh Kumar Chiranjivi; Tanmay Dutta; Vikash Kumar Dubey; Latha Rangan (BioMetals, 2022)

A report on tectonically sculptured unique glacier landform: a case study from the Tethys Kumaun Himalaya, India - Manish Mehta; Rahul Devrani; Khayingshing Luirei; Vinit Kumar (Geosciences Journal, 2022)

Anti-viral activity of methyl 1-chloro-7-methyl-2-propyl-1h-benzo[d] imidazole-5-carboxylate against white spot syndrome virus in freshwater crab (Paratelphusa hydrodromous) - K. Karthikeyan; A. T. Manish Kumar; D. Harshini; G. Pooja; J. Arul Daniel; Pavani Yasam; G. Gracevictoria; M. Priayanka; P. Krishnaraj; R. Vidya; S. Asha Devi; Sabbasani Rajasekhara Reddy; et al. (Aquaculture International, 2022)

Applicability of machine learning techniques for multi-time step ahead runoff forecasting - Tarate Suryakant Bajirao; Ahmed Elbeltagi; Manish Kumar; Quoc Bao Pham (Acta Geophysica, 2022)

Comparative proteomics and variations in extracellular matrix of Candida tropicalis biofilm in response to citral - Apurva Chatrath; Manish Kumar; Ramasare Prasad (Protoplasma, 2022)

Identification of molecular marker linked to resistance gene loci against Indian isolate of Phytophthora capsici L. causing root rot in chilli (Capsicum annuum L.) - Manish Kumar; Madhavi Reddy Kambham; Dhoranalapalli Chinnappareddy Laksh Reddy; Subbaraman Sriram; Tejavathu Hatiya Singh (Australasian Plant Pathology, 2022)

Contamination and health risk assessment of potentially harmful elements associated with roadside dust in Dhanbad India - Dinesh Kumar Patel; Manish Kumar Jain (Stochastic Environmental Research and Risk Assessment, 2022)

A framework for risk-based assessment of urban floods in coastal cities - M. Dinesh Kumar; Shubham Tandon; Nitin Bassi; Pradipta Kumar Mohanty; Saurabh Kumar; Manish Mohandas (Natural Hazards, 2022)

Morpho-physio and anatomical characterization of the indigenous Himalayan crabapple: Malus baccata (L.) Borkh. (Rohru) and exotic Malus pumila Mill. for dwarfing traits - Chavlesh Kumar; Sanjay Kumar Singh; Mahendra Kumar Verma; Kallol Kumar Pramanick; Manish Srivastav; Sukhdeep Kaur; Rajeev Ranjan Kumar (Genetic Resources and Crop Evolution, 2022)

Decolorization and degradation of reactive orange 16 by Bacillus stratosphericus SCA1007 - Kriti Akansha; Ajar Nath Yadav; Manish Kumar; Debashis Chakraborty; Shashwati Ghosh Sachan (Folia Microbiologica, 2022)

Insights into the multifunctional roles of geminivirus-encoded proteins in pathogenesis - Ragunathan Devendran; Tsewang Namgial; Kishore Kumar Reddy; Manish Kumar; Fauzia Zarreen; Supriya Chakraborty (Archives of Virology, 2022)

Correction to: A modified social spider algorithm for an efficient data dissemination in VANET - Achyut Shankar; Rajaguru Dayalan; Chinmay Chakraborty; Chandramohan Dhasarathan; Manish Kumar (Environment, Development and Sustainability, 2022)

A modified social spider algorithm for an efficient data dissemination in VANET - Achyut Shankar; Rajaguru Dayalan; Chinmay Chakraborty; Chandramohan Dhasarathan; Manish Kumar (Environment, Development and Sustainability, 2022)

Implications of Phosphoinositide 3-Kinase-Akt (PI3K-Akt) Pathway in the Pathogenesis of Alzheimer’s Disease - Manish Kumar; Nitin Bansal (Molecular Neurobiology, 2022)

Interrelationship of Indoor Particulate Matter and Respiratory Dust Depositions of Women in the Residence of Dhanbad City, India - Shravan Kumar; Manish Kumar Jain (Environmental Science and Pollution Research, 2022)

Mesenchymal stem cells are prospective novel off-the-shelf wound management tools - Poonam Malhotra; Manish Shukla; Poonam Meena; Anupama Kakkar; Nitin Khatri; Rakesh K Nagar; Mukesh Kumar; Sumit K Saraswat; Supriya Shrivastava; Rajan Datt; Siddharth Pandey (Drug Delivery and Translational Research, 2022)

Assessment of Groundwater Quality Index Using Geographic Information System in Parts of Rural Ajmer and Bhilwara Districts of Rajasthan, India - Swatantra K. Dubey; Sudhanshu K. Pathak; Devesh Sharma; Mukand S. Babel; Manish Kumar (Water Conservation Science and Engineering, 2021)

Investigating water quality of an urban water body using ground and space observations - Manish Kumar; Mukesh Kumar; Derrick Mario Denis; Om Prakash Verma; Lakhan Lal Mahato; Kamal Pandey (Spatial Information Research, 2021)

Lacidipine Attenuates Symptoms of Nicotine Withdrawal in Mice - Kunal Khurana; Manish Kumar; Nitin Bansal (Neurotoxicity Research, 2021)

A strategy to decrease vectorial competence of dengue mosquito Aedes aegypti by alteration of its gut microbiota using Indian traditional medicinal plants - Kamal Kumar Gupta; Meenakshi Prejneshu; Mohit Aggarwal; Chetkar Chandra Keshvam; Vinay Kumar Dubey; Manish Kumar Mishra; Naresh Singh (International Journal of Tropical Insect Science, 2021)

Molecular identification of brinjal little leaf disease associated with Solanum melongena L. in Eastern Uttar Pradesh, India - Smriti Mall; Priyam Panda; Manish Kumar (Indian Phytopathology, 2021)

Current trends in diagnosis and treatment strategies of COVID-19 infection - Varsha Tiwari; Manish Kumar; Abhishek Tiwari; Biswa Mohan Sahoo; Sunil Singh; Suresh Kumar; Renu Saharan (Environmental Science and Pollution Research, 2021)

A review on efficient electromagnetic interference shielding materials by recycling waste—a trio of land to lab to land concept - Sarika Verma; Medha Mili; Manish Dhangar; Krishnasamy Jagatheesan; Sriparna Paul; Harsh Bajpai; Nimisha Vedanti; Jyotirmoy Mallik; Mohammed Akram Khan; Hari Narayan Bhargaw; Sayed Azhar Rasheed Hashmi; Avanish Kumar Srivastava (Environmental Science and Pollution Research, 2021)

Genome-wide identification and functional prediction of salt- stress related long non-coding RNAs (lncRNAs) in chickpea (Cicer arietinum L.) - Neeraj Kumar; Chellapilla Bharadwaj; Sarika Sahu; Aalok Shiv; Abhishek Kumar Shrivastava; Sneha Priya Pappula Reddy; Khela Ram Soren; Basavannagouda Siddannagouda Patil; Madan Pal; Anjali Soni; Manish Roorkiwal; Rajeev Kumar Varshney (Physiology and Molecular Biology of Plants, 2021)
LncRNAs (long noncoding RNAs) are 200 bp length crucial RNA molecules, lacking coding potential and having important roles in regulating gene expression, particularly in response to abiotic stresses. In this study, we identified salt stress-induced lncRNAs in chickpea roots and predicted their intricate regulatory roles. A total of 3452 novel lncRNAs were identified to be distributed across all 08 chickpea chromosomes. On comparing salt-tolerant (ICCV 10, JG 11) and salt-sensitive cultivars (DCP 92–3, Pusa 256), 4446 differentially expressed lncRNAs were detected under various salt treatments. We predicted 3373 lncRNAs to be regulating their target genes in cis regulating manner and 80 unique lncRNAs were observed as interacting with 136 different miRNAs, as eTMs (endogenous target mimic) targets of miRNAs and implicated them in the regulatory network of salt stress response. Functional analysis of these lncRNA revealed their association in targeting salt stress response-related genes like potassium transporter, transporter family genes, serine/threonine-protein kinase, aquaporins like TIP1-2, PIP2-5 and transcription factors like, AP2, NAC, bZIP, ERF, MYB and WRKY. Furthermore, about 614 lncRNA-SSRs (simple sequence repeats) were identified as a new generation of molecular markers with higher efficiency and specificity in chickpea. Overall, these findings will pave the understanding of comprehensive functional role of potential lncRNAs, which can help in providing insight into the molecular mechanism of salt tolerance in chickpea.

Water spread mapping of multiple lakes using remote sensing and satellite data - Vaibhav Deoli; Deepak Kumar; Manish Kumar; Alban Kuriqi; Ahmed Elbeltagi (Arabian Journal of Geosciences, 2021)

Actual evapotranspiration and crop coefficients for tropical lowland rice (Oryza sativa L.) in eastern India - Sumanta Chatterjee; Paul C. Stoy; Manish Debnath; Amaresh Kumar Nayak; Chinmaya Kumar Swain; Rahul Tripathi; Dibyendu Chatterjee; Smruthi Sagarika Mahapatra; Ammara Talib; Himanshu Pathak (Theoretical and Applied Climatology, 2021)

An assessment of snow-glacier melt runoff under climate change scenarios in the Himalayan basin - Vishal Singh; Sanjay Kumar Jain; Manish Kumar Goyal (Stochastic Environmental Research and Risk Assessment, 2021)

Assessment of glacial lake development and downstream flood impacts of critical glacial lake - Uttam Puri Goswami; Manish Kumar Goyal (Natural Hazards, 2021)

Linkage of water vapor distribution in the lower stratosphere to organized Asian summer monsoon convection - Bhupendra Bahadur Singh; Raghavan Krishnan; D. C. Ayantika; Ramesh K. Vellore; T. P. Sabin; K. Ravi Kumar; Simone Brunamonti; Sreeharsha Hanumanthu; Teresa Jorge; Peter Oelsner; Sunil Sonbawne; Manish Naja; et al. (Climate Dynamics, 2021)

SARS-Cov2: a meta-analysis of symptom distribution by continent in 7310 adult COVID-19 infected patients - Hitesh Singhavi; Ameya Pai; Manish Mair; Jinesh Singhavi; Prachi Gandhi; Andrew Baker; Sudip Das; Sanjeev Kumar; Peter Conboy (VirusDisease, 2021)

Ellagic acid prevents 3-nitropropionic acid induced symptoms of Huntington’s disease - Priya Sharma; Manish Kumar; Nitin Bansal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Genetic mapping for grain quality and yield-attributed traits in Basmati rice using SSR-based genetic map - Madhvi Sharma; Sunil S Gangurde; Romesh K Salgotra; Bupesh Kumar; Anil K Singh; Manish K Pandey (Journal of Biosciences, 2021)

Potential of hybrid wavelet-coupled data-driven-based algorithms for daily runoff prediction in complex river basins - Tarate Suryakant Bajirao; Pravendra Kumar; Manish Kumar; Ahmed Elbeltagi; Alban Kuriqi (Theoretical and Applied Climatology, 2021)

Lacidipine Prevents Scopolamine-Induced Memory Impairment by Reducing Brain Oxido-nitrosative Stress in Mice - Kunal Khurana; Manish Kumar; Nitin Bansal (Neurotoxicity Research, 2021)

Evolving scenario of big data and Artificial Intelligence (AI) in drug discovery - Manish Kumar Tripathi; Abhigyan Nath; Tej P. Singh; A. S. Ethayathulla; Punit Kaur (Molecular Diversity, 2021)

Inheritance of resistance in chilli against root and collar rot caused by Phytophthora capsici - Manish Kumar; Kambham Madhavi Reddy; Subbaraman Sriram; Rajeev Kumar Yadav (Journal of Plant Pathology, 2021)

Evaluation of precipitation datasets available on Google earth engine over India - Saket Dubey; Harshit Gupta; Manish Kumar Goyal; Nitin Joshi (International Journal of Climatology, 2021)
Monthly mean precipitation estimates of seven products (TerraClimate, TRMM, CHIRPS, PERSIANN‐CDR, GPM‐IMERG, ERA5 and CFSR) available on Google earth engine (GEE) are evaluated against gridded gauge‐based precipitation product available from Indian Meteorological Department (IMD) for their skills and presence of systematic biases (during 2001–2018). All these products represent the climatological features reasonably well. Presence of systematic biases in these products is also observed from their evaluation. Biases across the periphery of the country are relatively on the higher side in comparison to the central regions. The magnitude of spatial variability is represented better for winter precipitation in comparison to summer precipitation. During both winter and summer, ensemble mean of various products outperforms individual products in terms of both RMSE and correlation. Performance of these products is also assessed across various Indian states, elevation bands and climate zones. The ability of these products to represent the seasonality was observed to be highest for the states with mid‐ranged peaks (10–20 mm·day −1 ) which tend to decrease with both increasing and decreasing peaks. Ability of the precipitation products to resemble the annual cycle does not vary with the amount of precipitation, although individual disparity among the products exists. Additionally, an alternative approach for data evaluation using Multiple Triple Collocation (MTC) was performed for the period 2001–2015 using an additional dataset obtained from soil‐moisture‐based rainfall estimates (SM2RAIN). Results from MTC convey that ERA5 performs relatively poor in comparison to the other products for central India followed by CFSR. In brief, the comprehensive evaluation of precipitation products reported herein will act a valuable reference for the researchers as well as decision makers to select the optimal product for their intended application and will inform the users about the various uncertainties in the foundations and specification of these products.

Spadicoides obovata: a new record from Kumaun Himalaya, India - Manish Kumar Dubey; Ram Sanmukh Upadhyay; Ramesh Chandra Gupta (Vegetos, 2021)

Variability in alkaloid and phenolic content vis-a-vis antigout potential among the natural population of Gloriosa superba (L.) collected from Central India - Ankita Misra; Sharad Srivastava; Pushpendra Kumar Shukla; Manish Kumar; Md. Khalid; Poonam Kushwaha; Pawan Kumar Agrawal (Natural Product Research, 2021)

The role of disinfectants and sanitizers during COVID-19 pandemic: advantages and deleterious effects on humans and the environment - Kuldeep Dhama; Shailesh Kumar Patel; Rakesh Kumar; Rupali Masand; Jigyasa Rana; Mohd. Iqbal Yatoo; Ruchi Tiwari; Khan Sharun; Ranjan K. Mohapatra; Senthilkumar Natesan; Manish Dhawan; Tauseef Ahmad; et al. (Environmental Science and Pollution Research, 2021)

Parameter estimation of proton exchange membrane fuel cell using a novel meta-heuristic algorithm - Manish Kumar Singla; Parag Nijhawan; Amandeep Singh Oberoi (Environmental Science and Pollution Research, 2021)

Genetic analysis of yellow mosaic disease resistance in loofah - Manpreet Kaur; Budhavaram Varalakshmi; Manish Kumar; Eguru Sreenivasa Rao; Mottaiyan Pitchaimuthu; Basavaraju Mahesha; Rangarajan Venugopalan; Dhoranalapalli Chinnappareddy Laksh Reddy (Australasian Plant Pathology, 2021)

Estimation of apparent thermal diffusivity of soil at lesser-Himalayan experimental catchment, Uttarakhand, India, for analytical subsoil temperature modelling - Pravin R. Patil; Renoj J. Thayyen; Sharad Kumar Jain; Manish K. Nema (Arabian Journal of Geosciences, 2021)

Copula based analysis of meteorological, hydrological and agricultural drought characteristics across Indian river basins - Vikas Poonia; Srinidhi Jha; Manish Kumar Goyal (International Journal of Climatology, 2021)
Duration and severity are the two most important parameters used for drought characterization. In this study, we used a bivariate copula‐based approach to understand the joint dependence of drought duration and severity of three different drought types. Three types of bivariate copulas (Gumbel, Frank and Plackett) are estimated for modelling and the best fit copula is selected over 1,162 grid points (at a resolution of 0.5° × 0.5°) of India. Further, the joint dependence of drought duration and severity are analysed to infer important properties in terms of exceedance probability and return periods. Finally, conditional probability and conditional return periods of drought characteristics are also derived, which could be useful for proper planning and management of the water resource system. From the investigation, it is observed that drought events in the Western and Central India are longer and more severe whereas the ones in the south Indian river basins are more frequent but less severe. Moreover, similar results were also obtained for the conditional probability and conditional return periods. This study provides information regarding the severe and longer drought event hotspots all over the study area and thus helpful for the policymakers in developing effective drought prevention and mitigation strategies comprehensively at a national scale.

Impact of climate change on crop water and irrigation requirements over eastern Himalayan region - Vikas Poonia; Jew Das; Manish Kumar Goyal (Stochastic Environmental Research and Risk Assessment, 2021)

Little Ice Age glacier extent and temporal changes in annual mass balance (2016–2019) of Pensilungpa Glacier, Zanskar Himalaya - Manish Mehta; Vinit Kumar; Siddhi Garg; Aparna Shukla (Regional Environmental Change, 2021)

Revisiting regulatory roles of replication protein A in plant DNA metabolism - Supriyo Chowdhury; Arpita Basu Chowdhury; Manish Kumar; Supriya Chakraborty (Planta, 2021)

Molecular cloning, expression and in-silico characterization of rosmarinic acid synthase from Ocimum tenuiflorum L. - Manish Kumar Suthar; Parul M. Purohit; Parmeshwar Lal Saran (Journal of Plant Biochemistry and Biotechnology, 2021)

Protease Enzymes: Highlights on Potential of Proteases as Therapeutics Agents - Ravi Shankar; Prabhat Kumar Upadhyay; Manish Kumar (International Journal of Peptide Research and Therapeutics, 2021)

Prevalence of SARS-CoV-2 in Communities Through Wastewater Surveillance—a Potential Approach for Estimation of Disease Burden - Prosun Bhattacharya; Manish Kumar; Md. Tahmidul Islam; Rehnuma Haque; Sudip Chakraborty; Arslan Ahmad; Nabeel Khan Niazi; Zeynep Cetecioglu; David Nilsson; Julian Ijumulana; Tom van der Voorn; Md. Jakariya; et al. (Current Pollution Reports, 2021)
The episodic outbreak of COVID-19 due to SARS-CoV-2 is severely affecting the economy, and the global count of infected patients is increasing. The actual number of patients had been underestimated due to limited facilities for testing as well as asymptomatic nature of the expression of COVID-19 on individual basis. Tragically, for emerging economies with high population density, the situation has been more complex due to insufficient testing facilities for diagnosis of the disease. However, the recent reports about persistent shedding of viral RNA of SARS-CoV-2 in the human feces have created a possibility to track the prevalence and trends of the disease in communities, known as wastewater-based epidemiology (WBE). In this article, we highlight the current limitations and future prospects for WBE to manage pandemics.

A novel lincRNA identified in buffalo oocytes with protein binding characteristics could hold the key for oocyte competence - Sunny Dholpuria; Sandeep Kumar; Manish Kumar; Parul Sarwalia; Rakesh Kumar; Tirtha Kumar Datta (Molecular Biology Reports, 2021)

Spondias pinnata (L.f.) Kurz Leaf Extract Derived Zinc Oxide Nanoparticles Induce Dual Modes of Apoptotic-Necrotic Death in HCT 116 and K562 Cells - Abdul Aziz Ahlam; V. S. Shaniba; P. R. Jayasree; P. R. Manish Kumar (Biological Trace Element Research, 2021)

Poly ethylene glycol mediated in vitro screening and physico-biochemical changes induced in mango callus due to moisture stress - Satyabrata Pradhan; Sanjay Kumar Singh; Manish Srivastav; Jai Prakash; Sanjay Kumar Lal; Jasdeep Chatrath Padaria; Amit Kumar Goswami; Naveen Kumar Maurya (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Deletion of both methionine sulfoxide reductase A and methionine sulfoxide reductase C genes renders Salmonella Typhimurium highly susceptible to hypochlorite stress and poultry macrophages - Sonu S. Nair; Tapan Kumar Singh Chauhan; Manoj Kumawat; Ratanti Sarkhel; Shekhar Apoorva; Arijit Shome; V. Athira; Bablu Kumar; Abhishek; Manish Mahawar (Molecular Biology Reports, 2021)

Correction to: Hydrogen fuel and fuel cell technology for cleaner future: a review - Manish Kumar Singla; Parag Nijhawan; Amandeep Singh Oberoi (Environmental Science and Pollution Research, 2021)

Hydrogen fuel and fuel cell technology for cleaner future: a review - Manish Kumar Singla; Parag Nijhawan; Amandeep Singh Oberoi (Environmental Science and Pollution Research, 2021)

Low frequency global‐scale modes and its influence on rainfall extremes over India: Nonstationary and uncertainty analysis - Srinidhi Jha; Jew Das; Manish Kumar Goyal (International Journal of Climatology, 2021)
The variability in the extreme rainfall events is of growing concern in the context of climate change. Several high rainfall events have occurred in India in recent years and simulations from the Intergovernmental Panel on Climate Change suggest a rise in extremes. The low‐frequency global‐scale modes/oscillations are widely considered as the significant drivers of inter‐annual variability of the Indian rainfall pattern and extreme rainfall events. To account for climate external forcings, we assessed the influence of El Nino Southern Oscillation, Indian Ocean Dipole and Atlantic Multidecadal Oscillation on extreme precipitation over 24 major river basins of India using the nonstationary extreme value analysis. Moreover, the uncertainty in the parameters of the fitted nonstationary extreme value distribution is assessed using Bayesian inference. It was found that extreme precipitation events in the country are dominated by these oscillations, especially in central India. Moreover, the return levels of high rainfall were found to be intensifying with increasing return period. We also observed that uncertainty in return levels was significant in almost every river basin. The results presented here contribute to a better understanding of the large‐scale climate variability and its impact on high rainfall pattern, which would provide an essential understanding of the rainfall‐induced hazard prevention and enhance the risk management strategy.

Occurrence of Cotton leaf curl Multan virus and associated betasatellites with leaf curl disease of Bhut-Jolokia chillies (Capsicum chinense Jacq.) in India - Sneha Yogindran; Manish Kumar; Lingaraj Sahoo; Keithellakpam Sanatombi; Supriya Chakraborty (Molecular Biology Reports, 2021)

Reliability analysis of settlement of pile group - Manish Kumar; Pijush Samui; Deepak Kumar; Wengang Zhang (Innovative Infrastructure Solutions, 2021)

Size-dependent chemical depletion of sediments in glacial environments: a case study of Mandakini Valley, central Himalaya, India - Tanuj Shukla; Vinit Kumar; Manish Mehta; Bahadur S. Kotlia; Meenakshi; Suraj Mal (Hydrological Sciences Journal, 2021)

Multilocus sequence analysis of a ‘Candidatus Phytoplasma australasia’-related strain associated with peanut little leaf disease in India - Surabhi Mitra; Manish Kumar; Karuba Vemana; Karla Saratbabu; Antony Masilamani Johnson; Swarup Mishra; Carmine Marcone; Govind P. Rao (Journal of Plant Pathology, 2021)

Advances and clinical challenges for translating nerve conduit technology from bench to bed side for peripheral nerve repair - Poonam Meena; Anupama Kakkar; Mukesh Kumar; Nitin Khatri; Rakesh Kumar Nagar; Aarti Singh; Poonam Malhotra; Manish Shukla; Sumit Kumar Saraswat; Supriya Srivastava; Rajan Datt; Siddharth Pandey (Cell and Tissue Research, 2021)

Characterization of the leaf rust responsive ARF genes in wheat (Triticum aestivum L.) - Saket Chandra; Lopamudra Satapathy; Srirupa Basu; Shailendra Kumar Jha; Manish Kumar; Kunal Mukhopadhyay (Plant Cell Reports, 2020)

Reliability Analysis of Settlement of Pile Group in Clay Using LSSVM, GMDH, GPR - Manish Kumar; Pijush Samui (Geotechnical and Geological Engineering, 2020)

Making Waves Perspectives of Modelling and Monitoring of SARS-CoV-2 in Aquatic Environment for COVID-19 Pandemic - Manish Kumar; Sanjeeb Mohapatra; Payal Mazumder; Ashwin Singh; Ryo Honda; Chuxia Lin; Rina Kumari; Ritusmita Goswami; Pawan Kumar Jha; Meththika Vithanage; Keisuke Kuroda (Current Pollution Reports, 2020)

Chevon Meat Storage Stability Infused with Response Surface Methodology Optimized Origanum vulgare Leaf Extracts - Niraj S. Jagtap; Rajesh V. Wagh; Manish K. Chatli; O. P. Malav; Pavan Kumar; Nitin Mehta (Agricultural Research, 2020)

Host-induced silencing of the Colletotrichum gloeosporioides conidial morphology 1 gene (CgCOM1) confers resistance against Anthracnose disease in chilli and tomato - Binod Kumar Mahto; Anjulata Singh; Manish Pareek; Manchikatla V. Rajam; Swatismita Dhar-Ray; Pallavolu M. Reddy (Plant Molecular Biology, 2020)

Statistical inferences from measured data on concentrations of naturally occurring radon, thoron, and decay products in Kumaun Himalayan belt - Ankur Kumar; Prakhar Singh; Tarun Agarwal; Manish Joshi; Poonam Semwal; Kuldeep Singh; Parmanad Prakash Pathak; Rakesh Chand Ramola (Environmental Science and Pollution Research, 2020)

Understanding the climate change impact on crop yield over Eastern Himalayan Region: ascertaining GCM and scenario uncertainty - Jew Das; Vikas Poonia; Srinidhi Jha; Manish Kumar Goyal (Theoretical and Applied Climatology, 2020)

Fumaric acid protect the cadmium-induced hepatotoxicity in rats: owing to its antioxidant, anti-inflammatory action and aid in recast the liver function - Gurpreet Kaur; Thippeswamy Boreddy Shivanandappa; Manish Kumar; Ajay Singh Kushwah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Microbes involved in arsenic mobilization and respiration: a review on isolation, identification, isolates and implications - Payal Mazumder; Subhash Kumar Sharma; Kaling Taki; Ajay S. Kalamdhad; Manish Kumar (Environmental Geochemistry and Health, 2020)

Partitioning of eddy covariance-measured net ecosystem exchange of CO2 in tropical lowland paddy - Sumanta Chatterjee; Chinmaya Kumar Swain; Amaresh Kumar Nayak; Dibyendu Chatterjee; Pratap Bhattacharyya; Smruthi Sagarika Mahapatra; Manish Debnath; Rahul Tripathi; Prabhat Kumar Guru; Biswaranjan Dhal (Paddy and Water Environment, 2020)

Exploring the anti-stress effects of imatinib and tetrabenazine in cold-water immersion-induced acute stress in mice - Manish Kumar; Nirmal Singh; Amteshwar Singh Jaggi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Sediment and Submarine Groundwater Discharge Mediated Arsenic Flux into the Bay of Bengal, India: an Appraisal - Anant Misra; Ashwin Singh; D. S. Suresh Babu; Vikrant Jain; Mithila Verma; Brijesh K. Bansal; Manish Kumar (Current Pollution Reports, 2020)

Association of a begomovirus-satellite complex with yellow vein and leaf curl disease of hollyhock (Alcea rosea) in India - Manish Kumar; R. Vinoth Kumar; Supriya Chakraborty (Archives of Virology, 2020)

Chemical composition, antioxidant and antiproliferative activities of essential oil from rhizome and leaves of Curcuma mutabilis Škorničk., M. Sabu & Prasanthk., endemic to Western Ghats of India - T. Soumya; P. R. Jayasree; M. Deepak; P. R. Manish Kumar (Natural Product Research, 2020)

Assessment of drought trend and variability in India using wavelet transform - Ashutosh Sharma; Manish Kumar Goyal (Hydrological Sciences Journal, 2020)

Thermoluminescence Studies of β and γ-Irradiated Geological Materials for Environment Monitoring - Gu Cheng-lin; Vikas Dubey; Kamal Kumar Kushwah; Manish Kumar Mishra; Ekta Pandey; Ratnesh Tiwari; Angesh Chandra; Neha Dubey (Journal of Fluorescence, 2020)

Biochars evaluation for chromium pollution abatement in chromite mine wastewater and overburden of Sukinda, Odisha, India - Sanghamitra Mohapatra; Manish Kumar; Adnan Asad Karim; Nabin Kumar Dhal (Arabian Journal of Geosciences, 2020)

G × E interactions in QTL introgression lines of Spanish-type groundnut (Arachis hypogaea L.) - A. L. Rathnakumar; Surendra S. Manohar; Hajisaheb L. Nadaf; Sudam C. Patil; Milind P. Deshmukh; P. P. Thirumalaisamy; Narendra Kumar; H. B. Lalwani; P. Nagaraju; Basavaraj Yenagi; S. S. Patil; J. Suryawanshi; et al. (Euphytica, 2020)

Spatio-temporal variation of air pollutants around the coal mining areas of Jharia Coalfield, India - Shilpi Mondal; Gurdeep Singh; Manish Kumar Jain (Environmental Monitoring and Assessment, 2020)

Comparative RNA sequencing based transcriptome profiling of regular bearing and alternate bearing mango (Mangifera indica L.) varieties reveals novel insights into the regulatory mechanisms underlying alternate bearing - Nimisha Sharma; Anand Kumar Singh; Sanjay Kumar Singh; Ajay Kumar Mahato; Manish Srivastav; Nagendra Kumar Singh (Biotechnology Letters, 2020)

Translational genomics for achieving higher genetic gains in groundnut - Manish K. Pandey; Arun K. Pandey; Rakesh Kumar; Chogozie Victor Nwosu; Baozhu Guo; Graeme C. Wright; Ramesh S. Bhat; Xiaoping Chen; Sandip K. Bera; Mei Yuan; Huifang Jiang; Issa Faye; et al. (Theoretical and Applied Genetics, 2020)
Key message Groundnut has entered now in post-genome era enriched with optimum genomic and genetic resources to facilitate faster trait dissection, gene discovery and accelerated genetic improvement for developing climate-smart varieties. Abstract Cultivated groundnut or peanut ( Arachis hypogaea ), an allopolyploid oilseed crop with a large and complex genome, is one of the most nutritious food. This crop is grown in more than 100 countries, and the low productivity has remained the biggest challenge in the semiarid tropics. Recently, the groundnut research community has witnessed fast progress and achieved several key milestones in genomics research including genome sequence assemblies of wild diploid progenitors, wild tetraploid and both the subspecies of cultivated tetraploids, resequencing of diverse germplasm lines, genome-wide transcriptome atlas and cost-effective high and low-density genotyping assays. These genomic resources have enabled high-resolution trait mapping by using germplasm diversity panels and multi-parent genetic populations leading to precise gene discovery and diagnostic marker development. Furthermore, development and deployment of diagnostic markers have facilitated screening early generation populations as well as marker-assisted backcrossing breeding leading to development and commercialization of some molecular breeding products in groundnut. Several new genomics applications/technologies such as genomic selection, speed breeding, mid-density genotyping assay and genome editing are in pipeline. The integration of these new technologies hold great promise for developing climate-smart, high yielding and more nutritious groundnut varieties in the post-genome era.

Integrating genomics for chickpea improvement: achievements and opportunities - Manish Roorkiwal; Chellapilla Bharadwaj; Rutwik Barmukh; Girish P. Dixit; Mahendar Thudi; Pooran M. Gaur; Sushil K. Chaturvedi; Asnake Fikre; Aladdin Hamwieh; Shiv Kumar; Supriya Sachdeva; Chris O. Ojiewo; et al. (Theoretical and Applied Genetics, 2020)
Key message Integration of genomic technologies with breeding efforts have been used in recent years for chickpea improvement. Modern breeding along with low cost genotyping platforms have potential to further accelerate chickpea improvement efforts. Abstract The implementation of novel breeding technologies is expected to contribute substantial improvements in crop productivity. While conventional breeding methods have led to development of more than 200 improved chickpea varieties in the past, still there is ample scope to increase productivity. It is predicted that integration of modern genomic resources with conventional breeding efforts will help in the delivery of climate-resilient chickpea varieties in comparatively less time. Recent advances in genomics tools and technologies have facilitated the generation of large-scale sequencing and genotyping data sets in chickpea. Combined analysis of high-resolution phenotypic and genetic data is paving the way for identifying genes and biological pathways associated with breeding-related traits. Genomics technologies have been used to develop diagnostic markers for use in marker-assisted backcrossing programmes, which have yielded several molecular breeding products in chickpea. We anticipate that a sequence-based holistic breeding approach, including the integration of functional omics, parental selection, forward breeding and genome-wide selection, will bring a paradigm shift in development of superior chickpea varieties. There is a need to integrate the knowledge generated by modern genomics technologies with molecular breeding efforts to bridge the genome-to-phenome gap. Here, we review recent advances that have led to new possibilities for developing and screening breeding populations, and provide strategies for enhancing the selection efficiency and accelerating the rate of genetic gain in chickpea.

A review of bismuth-based sorptive materials for the removal of major contaminants from drinking water - Manish Ranjan; Prabhat Kumar Singh; Arun Lal Srivastav (Environmental Science and Pollution Research, 2020)

Isolation and Identification of Protein l-Isoaspartate-O-Methyltransferase (PIMT) Interacting Proteins in Salmonella Typhimurium - Prasanta Kumar Koustasa Mishra; Anil Gattani; Manish Mahawar (Current Microbiology, 2020)

Identification of phytoplasma in six fruit crops in India - Govind Pratap Rao; Ashutosh Rao; Manish Kumar; Hemavati Ranebennur; Surabhi Mitra; Ashok Kumar Singh (European Journal of Plant Pathology, 2020)

Pollution evaluation, spatial distribution, and source apportionment of trace metals around coal mines soil: the case study of eastern India - Azeem Uddin Siddiqui; Manish Kumar Jain; Reginald Ebhin Masto (Environmental Science and Pollution Research, 2020)

Anti-diabetic Effect of Emblica-officinalis (Amla) Against Arsenic Induced Metabolic Disorder in Mice - Manish Kumar Singh; Shailendra Dwivedi; Suraj Singh Yadav; Rajesh Singh Yadav; Sanjay Khattri (Indian Journal of Clinical Biochemistry, 2020)

Bioremediation of Textile Dye Procion Red Yellow by Using Pseudomonas fluorescens - Badri Vishal Pandey; Manish Kumar Dubey; Ram Sanmukh Upadhyay (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

The major lightning regions and associated casualties over India - Pramod Kumar Yadava; Manish Soni; Sunita Verma; Harshbardhan Kumar; Ajay Sharma; Swagata Payra (Natural Hazards, 2020)

Silymarin Protects Against Impaired Autophagy Associated with 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine-Induced Parkinsonism - Manish Kumar Tripathi; Mohd Sami Ur Rasheed; Abhishek Kumar Mishra; Devendra Kumar Patel; Mahendra Pratap Singh (Journal of Molecular Neuroscience, 2020)

Arsenic exposure and perception of health risk due to groundwater contamination in Majuli (river island), Assam, India - Ritusmita Goswami; Manish Kumar; Nivedita Biyani; Patrick J. Shea (Environmental Geochemistry and Health, 2020)

First report on Obelidium megarhizum (Chytridiaceae) from India - Manish Kumar Dubey; Andleeb Zehra; Swarnmala Samal; Ram Sanmukh Upadhyay (Vegetos, 2019)

Identification and Validation of Leaf Rust Responsive Wheat isomiRs and their Target Genes in both Wheat and Puccinia triticina - Summi Dutta; Manish Kumar; Kunal Mukhopadhyay (Tropical Plant Biology, 2019)

Pharmacognostic Evaluation and Pharmacological Validation of Sphaeranthus indicus DC - Surabhi Tiwari; Pushpendra Kumar Shukla; Akanksha Srivastava; Manish Kumar; Ankita Misra; Sharad Srivastava (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Chlorpheniramine maleate containing chitosan-based nanoparticle-loaded thermosensitive in situ gel for management in allergic rhinitis - Manish Kumar; Pooja Upadhayay; Ravi Shankar; Monika Joshi; Shailendra Bhatt; Anuj Malik (Drug Delivery and Translational Research, 2019)

Manilkara zapota (L.) P. Royen Leaf Extract Derived Silver Nanoparticles Induce Apoptosis in Human Colorectal Carcinoma Cells Without Affecting Human Lymphocytes or Erythrocytes - V. S. Shaniba; Ahlam Abdul Aziz; P. R. Jayasree; P. R. Manish Kumar (Biological Trace Element Research, 2019)

Molecular Assessment of Anaplasma marginale in Bovine and Rhipicephalus (Boophilus) microplus Tick of Endemic Tribal Belt of Coastal South Gujarat, India - Niranjan Kumar; Jayesh B. Solanki; Anju Varghese; Mehul M. Jadav; Bhupamani Das; Manish D. Patel; Dharmesh C. Patel (Acta Parasitologica, 2019)

Sucrose and saccharin differentially modulate depression and anxiety-like behavior in diabetic mice: exposures and withdrawal effects - Manish Kumar; Monica Chail (Psychopharmacology, 2019)

Market-based mechanism and ‘climate justice’: reframing the debate for a way forward - Manish Kumar Shrivastava; Saradindu Bhaduri (International Environmental Agreements: Politics, Law and Economics, 2019)

Spatial homogeneity of extreme precipitation indices using fuzzy clustering over northeast India - Manish Kumar Goyal; Gupta Shivam; Arup K. Sarma (Natural Hazards, 2019)

First report of Brachysporium britannicum (Trichosphaeriaceae) from India - Manish Kumar Dubey; Zoya Shah; Ram Sanmukh Upadhyay; Ramesh Chandra Gupta (Indian Phytopathology, 2019)

QTLian breeding for climate resilience in cereals: progress and prospects - Mukesh Choudhary; Shabir Hussain Wani; Pardeep Kumar; Pravin K. Bagaria; Sujay Rakshit; Manish Roorkiwal; Rajeev K. Varshney (Functional & Integrative Genomics, 2019)

Temporal evolution of submicron particles during extreme fireworks - Sunil K. Yadav; Manish Kumar; Yashasvi Sharma; Prashant Shukla; Ram S. Singh; Tirthankar Banerjee (Environmental Monitoring and Assessment, 2019)

Water vapor flux in tropical lowland rice - Dibyendu Chatterjee; Amaresh Kumar Nayak; S. Vijayakumar; Manish Debnath; Sumanta Chatterjee; Chinmaya Kumar Swain; Priyanka Bihari; S. Mohanty; Rahul Tripathi; Mohammad Shahid; Anjani Kumar; H. Pathak (Environmental Monitoring and Assessment, 2019)

Genetic diversity and population structure analysis of wild Malus genotypes including the crabapples (M. baccata (L.) Borkh. & M. sikkimensis (Wenzig) Koehne ex C. Schneider) collected from the Indian Himalayan region using microsatellite markers - Chavlesh Kumar; Sanjay K. Singh; Rakesh Singh; Kallol K. Pramanick; Mahendra K. Verma; Manish Srivastav; Gunjan Tiwari; Debjani R. Choudhury (Genetic Resources and Crop Evolution, 2019)

Reliability Analysis of Pile Foundation Using ELM and MARS - Manish Kumar; Pijush Samui (Geotechnical and Geological Engineering, 2019)

Air quality modelling using long short-term memory (LSTM) over NCT-Delhi, India - Mrigank Krishan; Srinidhi Jha; Jew Das; Avantika Singh; Manish Kumar Goyal; Chandrra Sekar (Air Quality, Atmosphere & Health, 2019)

Intermittent normobaric hypoxia facilitates high altitude acclimatization by curtailing hypoxia-induced inflammation and dyslipidemia - Anamika Gangwar; Pooja; Manish Sharma; Krishan Singh; Anita Patyal; Gopinath Bhaumik; Kalpana Bhargava; Niroj Kumar Sethy (Pflügers Archiv - European Journal of Physiology, 2019)

Performance evaluation of TRUPCR® HBV Real-time PCR assay for Hepatitis B virus DNA quantification in clinical samples: report from a tertiary care liver centre - Sujata Lall; Manish C. Choudhary; Supriya Mahajan; Guresh Kumar; Ekta Gupta (VirusDisease, 2019)

In-silico analysis of novel p.(Gly14Ser) variant of ATOX1 gene: plausible role in modulating ATOX1–ATP7B interaction - Niti Kumari; Aman Kumar; Amit Pal; Babu Ram Thapa; Manish Modi; Rajendra Prasad (Molecular Biology Reports, 2019)

Microzonation, ecological risk and attributes of metals in highway road dust traversing through the Kaziranga National Park, Northeast India: implication for confining metal pollution in the national forest - Upasona Devi; Kaling Taki; Tanya Shukla; Kali P. Sarma; Raza R. Hoque; Manish Kumar (Environmental Geochemistry and Health, 2019)

Leaf rust (Puccinia triticina) mediated RNAi in wheat (Triticum aestivum L.) prompting host susceptibility - Summi Dutta; Shailendra Kumar Jha; Kumble Vinod Prabhu; Manish Kumar; Kunal Mukhopadhyay (Functional & Integrative Genomics, 2019)

Characterization of land surface energy fluxes in a tropical lowland rice paddy - Dibyendu Chatterjee; Rahul Tripathi; Sumanta Chatterjee; Manish Debnath; Mohammad Shahid; Pratap Bhattacharyya; Chinmaya Kumar Swain; Rojalin Tripathy; Bimal K. Bhattacharya; Amaresh Kumar Nayak (Theoretical and Applied Climatology, 2019)

Biodiversity of methylotrophic microbial communities and their potential role in mitigation of abiotic stresses in plants - Manish Kumar; Divjot Kour; Ajar Nath Yadav; Raghvendra Saxena; Pankaj Kumar Rai; Anurag Jyoti; Rajesh Singh Tomar (Biologia, 2019)

Assessment of future water provisioning and sediment load under climate and LULC change scenarios in a peninsular river basin, India - Manas Khan; Ashutosh Sharma; Manish Kumar Goyal (Hydrological Sciences Journal, 2019)

Multistage gedrite in gedrite–hypersthene-bearing high-grade granulites from Daltonganj, Chhotanagpur granite–gneissic complex, Jharkhand, as evident from TEM and textural relations - S B Dwivedi; Ravi Ranjan Kumar; Manish Srivastava (Journal of Earth System Science, 2019)

Antioxidant and Antimicrobial Efficacy of Peptidic Hydrolysate Obtained from Porcine Blood - Akhilesh K. Verma; Manish Kumar Chatli; Pavan Kumar; Nitin Mehta (Agricultural Research, 2019)

Field evaluations of agrochemical toxicity to cyanobacteria in rice field ecosystem: a review - Manish Singh Kaushik; Ajay Kumar; Gerard Abraham; Nalinaxya Prasad Dash; Pawan Kumar Singh (Journal of Applied Phycology, 2019)

Indoor inhalation dose assessment for thoron-rich regions of Indian Himalayan belt - Poonam Semwal; Tarun Kumar Agarwal; Kuldeep Singh; Manish Joshi; Gurupad Singh Gusain; Bijay Kumar Sahoo; Rakesh Chand Ramola (Environmental Science and Pollution Research, 2019)

Switch in chemical weathering caused by the mass balance variability in a Himalayan glacierized basin: a case of Chhota Shigri Glacier - Naveen Kumar; AL. Ramanathan; Martyn Tranter; Parmanand Sharma; Manish Pandey; Prabhat Ranjan; N. Janardhan Raju (Hydrological Sciences Journal, 2019)

Malfunctioning of Chaperone-Mediated Autophagy in Parkinson’s Disease: Feats, Constraints, and Flaws of Modulators - Manish Kumar Tripathi; Charul Rajput; Saumya Mishra; Mohd Sami ur Rasheed; Mahendra Pratap Singh (Neurotoxicity Research, 2019)

An improved coupled framework for Glacier classification: an integration of optical and thermal infrared remote-sensing bands - Vishal Singh; Manish Kumar Goyal (International Journal of Remote Sensing, 2018)

The effects of PPR on the reproductive health of Black Bengal goats and the possible role played by oxidative stress - Pankaj Kumar; Amitava Dey; Abhay Kumar; Pradeep Kumar Ray; Poolangulam Chinnakkan Chandran; Rashmi Rekha Kumari; Manish Kumar (Tropical Animal Health and Production, 2018)

Spatiotemporal and joint probability behavior of temperature extremes over the Himalayan region under changing climate - Uttam P. Goswami; K. Bhargav; B. Hazra; Manish Kumar Goyal (Theoretical and Applied Climatology, 2018)

Corn cob silica as an antibacterial support for silver nanoparticles: efficacy on Escherichia coli and Listeria monocytogenes - Jaehong Shim; Payal Mazumder; Manish Kumar (Environmental Monitoring and Assessment, 2018)

Neurochemical and Behavioral Dysfunctions in Pesticide Exposed Farm Workers: A Clinical Outcome - Rajesh Kumar Kori; Manish Kumar Singh; Abhishek Kumar Jain; Rajesh Singh Yadav (Indian Journal of Clinical Biochemistry, 2018)

Prediction of indoor radon/thoron concentration in a model room from exhalation rates of building materials for different ventilation rates - Manish Kumar; Navjeet Sharma; Amit Sarin (Acta Geophysica, 2018)

Ellagic acid prevents dementia through modulation of PI3-kinase-endothelial nitric oxide synthase signalling in streptozotocin-treated rats - Manish Kumar; Nitin Bansal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Structure, mechanical properties and evolution of the lithosphere below the northwest continental margin of India - G. Srinivasa Rao; Manish Kumar; M. Radhakrishna (International Journal of Earth Sciences, 2018)

Sporidesmium binserum sp. nov. from Binser forest of Almora, Himalaya, India - Manish Kumar Dubey; Ram Sanmukh Upadhyay; Deeba Kamil; Ramesh Chandra Gupta (Indian Phytopathology, 2018)

Three-dimensional velocity measurements around bridge piers in gravel bed - Manish Pandey; P. K. Sharma; Z. Ahmad; Umesh Kumar Singh; Nilav Karna (Marine Georesources & Geotechnology, 2018)

A mechanistic approach to explore the neuroprotective potential of zonisamide in seizures - Baldeep Kumar; Bikash Medhi; Manish Modi; Biman Saikia; Savita Verma Attri; Ajay Patial (Inflammopharmacology, 2018)

Cross-Reactivity of Prokaryotic 16S rDNA-Specific Primers to Eukaryotic DNA: Mistaken Microbial Community Profiling in Environmental Samples - Shailendra Yadav; Arvind Kumar; Manish Gupta; S. S. Maitra (Current Microbiology, 2018)

Impact of land cover change on land surface temperature: A case study of Spiti Valley - Pankaj Kumar; Arif Husain; Ram Babu Singh; Manish Kumar (Journal of Mountain Science, 2018)

Stability assessment of jointed rock slope with different crack infillings under various thermomechanical loadings - Pushpendra Sharma; Amit Kumar Verma; Anil Negi; Manish Kumar Jha; Pradeep Gautam (Arabian Journal of Geosciences, 2018)

Rational Selection, Criticality Assessment, and Tiering of Quality Attributes and Test Methods for Analytical Similarity Evaluation of Biosimilars - Kristof Vandekerckhove; Andreas Seidl; Hiten Gutka; Manish Kumar; Gyöngyi Gratzl; David Keire; Todd Coffey; Henriette Kuehne (The AAPS Journal, 2018)

Concurrent modifications in the three homeologs of Ms45 gene with CRISPR-Cas9 lead to rapid generation of male sterile bread wheat (Triticum aestivum L.) - Manjit Singh; Manish Kumar; Marc C. Albertsen; Joshua K. Young; A. Mark Cigan (Plant Molecular Biology, 2018)

Inhibitory Mechanism on Combination of Phytic Acid with Methanolic Seed Extract of Syzygium cumini and Sodium Chloride over Bacillus subtilis - Alok Kumar Yadav; Preeti Sirohi; Saurabh Saraswat; Manjoo Rani; Manish Pratap Singh; Sameer Srivastava; Nand K. Singh (Current Microbiology, 2018)

Mutational analyses of regulatory genes, mexR, nalC, nalD and mexZ of mexAB-oprM and mexXY operons, in efflux pump hyperexpressing multidrug-resistant clinical isolates of Pseudomonas aeruginosa - Manju Suresh; N. Nithya; P. R. Jayasree; K. P. Vimal; P. R. Manish Kumar (World Journal of Microbiology and Biotechnology, 2018)

Evaluation of dried blood spot as an alternative sample collection method for hepatitis C virus RNA quantitation and genotyping using a commercial system - Supriya Mahajan; Manish Chandra Choudhary; Guresh Kumar; Ekta Gupta (VirusDisease, 2018)

Bioconversion of Chitin to Bioactive Chitooligosaccharides: Amelioration and Coastal Pollution Reduction by Microbial Resources - Manish Kumar; Amandeep Brar; V. Vivekanand; Nidhi Pareek (Marine Biotechnology, 2018)

Field evidences showing rapid frontal degeneration of the Kangriz glacier, western Himalayas, Jammu & Kashmir - Siddhi Garg; Aparna Shukla; Manish Mehta; Vinit Kumar; Shruti Anna Samuel; S. K. Bartarya; Uma Kant Shukla (Journal of Mountain Science, 2018)

Fullerenol-Based Intracellular Delivery of Methotrexate: A Water-Soluble Nanoconjugate for Enhanced Cytotoxicity and Improved Pharmacokinetics - Shradha Bahuguna; Manish Kumar; Gajanand Sharma; Rajendra Kumar; Bhupinder Singh; Kaisar Raza (AAPS PharmSciTech, 2018)

Fabrication of 3-O-sn-Phosphatidyl-L-serine Anchored PLGA Nanoparticle Bearing Amphotericin B for Macrophage Targeting - Pankaj K. Singh; Anil K. Jaiswal; Vivek K. Pawar; Kavit Raval; Animesh Kumar; Himangsu K. Bora; Anuradha Dube; Manish K. Chourasia (Pharmaceutical Research, 2018)

Geochemical Assessment of Fluoride Pollution in Groundwater of Tribal Region in India - Anshumali; Manish Kumar; Nikki Chanda; Abhay Kumar; Bijendra Kumar; Madavi Venkatesh (Bulletin of Environmental Contamination and Toxicology, 2018)

Toxicity of biocides to native cyanobacteria at different rice crop stages in wetland paddy field - Nalinaxya Prasad Dash; Manish Singh Kaushik; Ajay Kumar; Gerard Abraham; Pawan Kumar Singh (Journal of Applied Phycology, 2018)

Detection and identification of four 16Sr subgroups of phytoplasmas associated with different legume crops in India - G. P. Rao; Madhupriya; Manish Kumar; Sonica Tomar; Bishnu Maya; S. K. Singh; Joy Michal Johnson (European Journal of Plant Pathology, 2018)

Protein requirement of juvenile striped catfish, Pangasianodon hypophthalmus - Manish Jayant; Ande Penchala Muralidhar; Narrottam Prasad Sahu; Kamal Kant Jain; Asim Kumar Pal; Prem Prakash Srivastava (Aquaculture International, 2018)

Assessment of ecosystem resilience to hydroclimatic disturbances in India - Ashutosh Sharma; Manish Kumar Goyal (Global Change Biology, 2018)
Recent studies have shown an increasing trend in hydroclimatic disturbances like droughts, which are anticipated to become more frequent and intense under global warming and climate change. Droughts adversely affect the vegetation growth and crop yield, which enhances the risks to food security for a country like India with over 1.2 billion people to feed. Here, we compared the response of terrestrial net primary productivity ( NPP ) to hydroclimatic disturbances in India at different scales (i.e., at river basins, land covers, and climate types) to examine the ecosystems’ resilience to such adverse conditions. The ecosystem water use efficiency (WUE e : NPP/Evapotranspiration) is an effective indicator of ecosystem productivity, linking carbon (C) and water cycles. We found a significant difference ( p WUE e across India at different scales. The ecosystem resilience analysis indicated that most of the river basins were not resilient enough to hydroclimatic disturbances. Drastic reduction in WUE e under dry conditions was observed for some basins, which highlighted the cross‐biome incapability to withstand such conditions. The ecosystem resilience at land cover and climate type scale did not completely relate to the basin‐scale ecosystem resilience, which indicated that ecosystem resilience at basin scale is controlled by some other ecohydrological processes. Our results facilitate the identification of the most sensitive regions in the country for ecosystem management and climate policy making, and highlight the need for taking sufficient adaptation measures to ensure sustainability of ecosystems.

Comparative Assessment of SWAT Model Performance in two Distinct Catchments under Various DEM Scenarios of Varying Resolution, Sources and Resampling Methods - Manish Kumar Goyal; Venkatesh K. Panchariya; Ashutosh Sharma; Vishal Singh (Water Resources Management, 2018)

Selective induction of DNA damage, G2 abrogation, and mitochondrial apoptosis by leaf extract of traditional medicinal plant Wrightia arborea in K562 cells - T. Lakshmipriya; T. Soumya; P. R. Jayasree; P. R. Manish Kumar (Protoplasma, 2018)

Spatio-temporal heterogeneity and changes in extreme precipitation over eastern Himalayan catchments India - Vishal Singh; Manish Kumar Goyal (Stochastic Environmental Research and Risk Assessment, 2017)

Identification and molecular characterization of a trans-acting small interfering RNA producing locus regulating leaf rust responsive gene expression in wheat (Triticum aestivum L.) - Summi Dutta; Dhananjay Kumar; Shailendra Jha; Kumble Vinod Prabhu; Manish Kumar; Kunal Mukhopadhyay (Planta, 2017)

Prediction of flow rate of karstic springs using support vector machines - Manish Kumar Goyal; Ashutosh Sharma; Konstantinos L. Katsifarakis (Hydrological Sciences Journal, 2017)

Association analysis for pomological traits in mango (Mangifera indica L.) by genic-SSR markers - Shiv Lal; Anand Kumar Singh; Sanjay Kumar Singh; Manish Srivastav; Bikram Pratap Singh; Nimisha Sharma; Nagendra Kumar Singh (Trees, 2017)

Response of Sandy Lake in Schirmacher Oasis, East Antarctica to the glacial-interglacial climate shift - Badanal Siddaiah Mahesh; Anish Kumar Warrier; Rahul Mohan; Manish Tiwari; Rajdeep Roy; Rajesh Asthana; Rasik Ravindra (Journal of Paleolimnology, 2017)

Numerical Simulation of Explosion in Twin Tunnel System - A. K. Verma; Manish Kumar Jha; Srinivas Mantrala; T. G. Sitharam (Geotechnical and Geological Engineering, 2017)

Evaluation of existing equations for temporal scour depth around circular bridge piers - Manish Pandey; P. K. Sharma; Z. Ahmad; Umesh Kumar Singh (Environmental Fluid Mechanics, 2017)

Probabilistic seasonal streamflow forecasts of the Citarum River, Indonesia, based on general circulation models - Netrananda Sahu; Andrew W. Robertson; Rizaldi Boer; Swadhin Behera; David G. DeWitt; Kaoru Takara; Manish Kumar; R. B. Singh (Stochastic Environmental Research and Risk Assessment, 2017)

Loss of crop yields in India due to surface ozone: an estimation based on a network of observations - Shyam Lal; Sethuraman Venkataramani; Manish Naja; Jagdish Chandra Kuniyal; Tuhin Kumar Mandal; Pradip Kumar Bhuyan; Kandikonda Maharaj Kumari; Sachchida Nand Tripathi; Ujjaini Sarkar; Trupti Das; Yerramsetti Venkata Swamy; Kotalo Rama Gopal; et al. (Environmental Science and Pollution Research, 2017)

Activation of defense response in tomato against Fusarium wilt disease triggered by Trichoderma harzianum supplemented with exogenous chemical inducers (SA and MeJA) - Andleeb Zehra; Mukesh Meena; Manish Kumar Dubey; Mohd. Aamir; R. S. Upadhyay (Brazilian Journal of Botany, 2017)

Elevational plant species richness patterns and their drivers across non-endemics, endemics and growth forms in the Eastern Himalaya - Kumar Manish; Maharaj K. Pandit; Yasmeen Telwala; Dinesh C. Nautiyal; Lian Pin Koh; Sudha Tiwari (Journal of Plant Research, 2017)

Impairment of ntcA gene revealed its role in regulating iron homeostasis, ROS production and cellular phenotype under iron deficiency in cyanobacterium Anabaena sp. PCC 7120 - Manish Singh Kaushik; Meenakshi Srivastava; Anumeha Singh; Arun Kumar Mishra (World Journal of Microbiology and Biotechnology, 2017)

Analysis of the change in temperature trends in Subansiri River basin for RCP scenarios using CMIP5 datasets - Shivam; Manish Kumar Goyal; Arup Kumar Sarma (Theoretical and Applied Climatology, 2017)

Genome-wide identification and characterization of NB-ARC resistant genes in wheat (Triticum aestivum L.) and their expression during leaf rust infection - Saket Chandra; Andaleeb Z. Kazmi; Zainab Ahmed; Gargi Roychowdhury; Veena Kumari; Manish Kumar; Kunal Mukhopadhyay (Plant Cell Reports, 2017)

Clinical significance of cathepsin L and cathepsin B in dilated cardiomyopathy - Siddharth Mehra; Manish Kumar; Mansi Manchanda; Ratnakar Singh; Bhaskar Thakur; Neha Rani; Sudheer Arava; Rajiv Narang; Dharamvir Singh Arya; Shyam S. Chauhan (Molecular and Cellular Biochemistry, 2017)

Nitrogenous agrochemicals inhibiting native diazotrophic cyanobacterial contribution in wetland rice ecosystem - Nalinaxya Prasad Dash; Ajay Kumar; Manish Singh Kaushik; Gerard Abraham; Pawan Kumar Singh (Journal of Applied Phycology, 2017)

Airborne particulate in Varanasi over middle Indo-Gangetic Plain: variation in particulate types and meteorological influences - Vishnu Murari; Manish Kumar; Alaa Mhawish; S. C. Barman; Tirthankar Banerjee (Environmental Monitoring and Assessment, 2017)

Multivariate statistical approach for assessment of subsidence in Jharia coalfields, India - Satya Prakash Sahu; Manish Yadav; Arka Jyoti Das; Amar Prakash; Ajay Kumar (Arabian Journal of Geosciences, 2017)

Impact of Mine Waste Leachates on Aquatic Environment: A Review - Manish Kumar Jain; Arpita Das (Current Pollution Reports, 2017)

Flood occurrences, damages, and management challenges in India: a geographical perspective - Omvir Singh; Manish Kumar (Arabian Journal of Geosciences, 2017)

Hydrogeochemical controls on mobilization of arsenic and associated health risk in Nagaon district of the central Brahmaputra Plain, India - Manish Kumar; Arbind Kumar Patel; Aparna Das; Pankaj Kumar; Ritusmita Goswami; Parismita Deka; Nilotpal Das (Environmental Geochemistry and Health, 2017)

Uncovering leaf rust responsive miRNAs in wheat (Triticum aestivum L.) using high-throughput sequencing and prediction of their targets through degradome analysis - Dhananjay Kumar; Summi Dutta; Dharmendra Singh; Kumble Vinod Prabhu; Manish Kumar; Kunal Mukhopadhyay (Planta, 2017)

A fuzzy c-means approach regionalization for analysis of meteorological drought homogeneous regions in western India - Manish Kumar Goyal; Ashutosh Sharma (Natural Hazards, 2016)

Cyanobacterial (unicellular and heterocystous) biofertilization to wetland rice influenced by nitrogenous agrochemical - N. P. Dash; Ajay Kumar; Manish Singh Kaushik; Pawan Kumar Singh (Journal of Applied Phycology, 2016)

Quality Attributes of Functional, Fiber-Enriched Pork Loaves - Akhilesh K. Verma; Manish Kumar Chatli; Nitin Mehta; Pavan Kumar; Om Prakash Malav (Agricultural Research, 2016)

Bioinspired Calcium Phosphate Nanoparticles Featuring as Efficient Carrier and Prompter for Macrophage Intervention in Experimental Leishmaniasis - Mohini Chaurasia; Pankaj K. Singh; Anil K. Jaiswal; Animesh Kumar; Vivek K. Pawar; Anuradha Dube; Sarvesh K. Paliwal; Manish K. Chourasia (Pharmaceutical Research, 2016)

Nitric oxide ameliorates the damaging effects of oxidative stress induced by iron deficiency in cyanobacterium Anabaena 7120 - Manish Singh Kaushik; Meenakshi Srivastava; Alka Srivastava; Anumeha Singh; Arun Kumar Mishra (Environmental Science and Pollution Research, 2016)

Study of temperature effect on thermal conductivity of Jhiri shale from Upper Vindhyan, India - Manish Kumar Jha; A. K. Verma; Sachin Maheshwar; Ankur Chauhan (Bulletin of Engineering Geology and the Environment, 2016)

Evidence for a fluid flow triggered spatio-temporal migration of seismicity in the 2001 Mw 7.7 Bhuj earthquake region, Gujarat, India, during 2001–2013 - Prantik Mandal; Manish Kumar; Koushik Biswas (Journal of Earth System Science, 2016)

Steep improvement in dissolution profile of ezetimibe through co-inclusion in urea - Manish Dhall; Anil Kumar Madan (Journal of Pharmaceutical Investigation, 2016)

Methylotrophic bacteria in sustainable agriculture - Manish Kumar; Rajesh Singh Tomar; Harshad Lade; Diby Paul (World Journal of Microbiology and Biotechnology, 2016)

Erratum to: Curcumin Delivery by Poly(Lactide)-Based Co-Polymeric Micelles: An In Vitro Anticancer Study - Preeti Kumari; Muddineti Omkara Swami; Prit Manish Lakhani; Sravan Kumar Nadipalli; Srividya Myneni; Balaram Ghosh; Swati Biswas (Pharmaceutical Research, 2016)

Resveratrol Protects from Toxin-Induced Parkinsonism: Plethora of Proofs Hitherto Petty Translational Value - Mohd Sami ur Rasheed; Manish Kumar Tripathi; Abhishek Kumar Mishra; Saurabh Shukla; Mahendra Pratap Singh (Molecular Neurobiology, 2016)

First report of association of potato virus X and potato virus Y and ‘Candidatus Phytoplasma trifolii’ in brinjal in India - Manish Kumar; Akshay Katiyar; Madhupriya; G. P. Rao (VirusDisease, 2016)

Modelling the impacts of future climate change on plant communities in the Himalaya: a case study from Eastern Himalaya, India - Kumar Manish; Yasmeen Telwala; Dinesh C. Nautiyal; Maharaj K. Pandit (Modeling Earth Systems and Environment, 2016)

Understanding the remobilization of copper, zinc, cadmium and lead due to ageing through sequential extraction and isotopic exchangeability - Manish Kumar (Environmental Monitoring and Assessment, 2016)

Assessing Potential Conservation and Restoration Areas of Freshwater Fish Fauna in the Indian River Basins - Jay P. Bhatt; Kumar Manish; Rajender Mehta; Maharaj K. Pandit (Environmental Management, 2016)

Lapse time dependent coda-Q (Q c) in the Kachchh, rift zone, Gujarat, India - Koushik Biswas; Manish Kumar; Prantik Mandal (Natural Hazards, 2016)

Marker-assisted improvement of grain protein content and grain weight in Indian bread wheat - Manish K. Vishwakarma; B. Arun; V. K. Mishra; P. S. Yadav; H. Kumar; Arun K. Joshi (Euphytica, 2016)

Devastation in the Kedarnath (Mandakini) Valley, Garhwal Himalaya, during 16–17 June 2013: a remote sensing and ground-based assessment - Rakesh Bhambri; Manish Mehta; D. P. Dobhal; Anil Kumar Gupta; Bhanu Pratap; Kapil Kesarwani; Akshaya Verma (Natural Hazards, 2016)

An angiotensin-converting enzyme-inhibitory metabolite with partial structure of microginin in a cyanobacterium Anabaena fertilissima CCC597, producing fibrinolytic protease - Suvendra Nath Bagchi; Shobha Sondhia; Manish Kumar Agrawal; Sonali Banerjee (Journal of Applied Phycology, 2016)

Bactericidal Activity of Nanopolymers Against Shrimp Pathogenic Bacterium Vibrio harveyi - K. K. Krishnani; V. Kathiravan; N. A. Shakil; Manish Kumar Singh; M. P. Brahmane; K. K. Meena; Biplab Sarkar; K. Choudhary; Mukesh Kumar Singh; Jitendra Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Floristic assessment of the important least concern plant species with taxonomic descriptions along the National Highway - Jitin Rahul; Manish Kumar Jain (Brazilian Journal of Botany, 2015)

Source and seasonal variation in the major ion chemistry of two eastern Himalayan high altitude lakes, India - Jyoti Prakash Deka; Goman Tayeng; Sangeeta Singh; Raza Rafiqul Hoque; Amit Prakash; Manish Kumar (Arabian Journal of Geosciences, 2015)

Insights from the Molecular Docking of Hydrolytic Products of Methyl Isocyanate (MIC) to Inhibition of Human Immune Proteins - Manish Kumar Tripathi; Mohammad Yasir; Vikram Singh Gurjar; Protiti Bose; Amit Dubey; Rahul Shrivastava (Interdisciplinary Sciences: Computational Life Sciences, 2015)

Cerebral malaria with diffuse subcortical microhaemorrhages and a transient splenial lesion - Ezaz Mohamed; Balaguruswamy Madan Mohan; Alok Kumar Udiya; Manish Paul; Sunil Kumar Jain (Acta Neurologica Belgica, 2015)

Ectopic expression of SbNHX1 gene in transgenic castor (Ricinus communis L.) enhances salt stress by modulating physiological process - Manish Kumar Patel; Mukul Joshi; Avinash Mishra; Bhavanath Jha (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Screening of a library of 4-aryl/heteroaryl-4H-fused pyrans for xanthine oxidase inhibition: synthesis, biological evaluation and docking studies - Ramandeep Kaur; Fatima Naaz; Sahil Sharma; Samir Mehndiratta; Manish Kumar Gupta; Preet Mohinder Singh Bedi; Kunal Nepali (Medicinal Chemistry Research, 2015)

Geospatial and hydrological modeling to assess hydropower potential zones and site location over rainfall dependent Inland catchment - Manish Kumar Goyal; Vishal Singh; Akshay H. Meena (Water Resources Management, 2015)

Aberrant Autophagy and Parkinsonism: Does Correction Rescue from Disease Progression? - Abhishek Kumar Mishra; Mohd Sami ur Rasheed; Saurabh Shukla; Manish Kumar Tripathi; Anubhuti Dixit; Mahendra Pratap Singh (Molecular Neurobiology, 2015)

Phylogenetic Study of Methanol Oxidizers from Chilika-Lake Sediments Using Genomic and Metagenomic Approaches - Kamlesh K. Meena; Manish Kumar; Snehasish Mishra; Sanjay Kumar Ojha; Goraksha C. Wakchaure; Biplab Sarkar (Indian Journal of Microbiology, 2015)

Unravelling earth system for sustainable solution - Tirthankar Banerjee; Manish Kumar (Environmental Science and Pollution Research, 2015)

Antiproliferative and Apoptosis Inducing Effects of Non-Polar Fractions from Lawsonia inermis L. in Cervical (HeLa) Cancer Cells - Manish Kumar; Paramjeet Kaur; Subodh Kumar; Satwinderjeet Kaur (Physiology and Molecular Biology of Plants, 2015)

Insights from the molecular docking of hydrolytic products of methyl iso cyanate (MIC) to inhibition of human immune proteins - Manish Kumar Tripathi; Mohammad Yasir; Vikram Singh Gurjar; Protiti Bose; Amit Dubey; Rahul Shrivastava (Interdisciplinary Sciences: Computational Life Sciences, 2015)

Evidence for non-self-similarity in the M w 7.7 2001 Bhuj earthquake sequence - Manish Kumar; V. S. Yallanki; Koushik Biswas; Prantik Mandal (Natural Hazards, 2015)

Temporal variability of MODIS aerosol optical depth and chemical characterization of airborne particulates in Varanasi, India - Vishnu Murari; Manish Kumar; S. C. Barman; T. Banerjee (Environmental Science and Pollution Research, 2015)

Identification and full-length molecular characterization of rare hepatitis C virus genotype 5a from India - Manish Chandra Choudhary; Ekta Gupta; Priyanka Pandey; Vidhya Natarajan; Shvetank Sharma; Chitranshu Vashishtha; Manoj Kumar Sharma; Syed N. Kazim; Shiv K. Sarin (Archives of Virology, 2015)

Transcriptome-wide analysis of WRKY transcription factors in wheat and their leaf rust responsive expression profiling - Lopamudra Satapathy; Dharmendra Singh; Prashant Ranjan; Dhananjay Kumar; Manish Kumar; Kumble Vinod Prabhu; Kunal Mukhopadhyay (Molecular Genetics and Genomics, 2014)

Identification of Homogeneous Rainfall Regimes in Northeast Region of India using Fuzzy Cluster Analysis - Manish Kumar Goyal; Vivek Gupta (Water Resources Management, 2014)

Monthly rainfall prediction using wavelet regression and neural network: an analysis of 1901–2002 data, Assam, India - Manish Kumar Goyal (Theoretical and Applied Climatology, 2014)

Linked Simulation-Optimization based Dedicated Monitoring Network Design for Unknown Pollutant Source Identification using Dynamic Time Warping Distance - Manish Kumar Jha; Bithin Datta (Water Resources Management, 2014)

Artificial microRNA mediated gene silencing in plants: progress and perspectives - Manish Tiwari; Deepika Sharma; Prabodh Kumar Trivedi (Plant Molecular Biology, 2014)

Photocontrol of differential gene expression and alterations in foliar anthocyanin accumulation: a comparative study using red and green forma Ocimum tenuiflorum - Pritesh Vyas; Inamul Haque; Manish Kumar; Kunal Mukhopadhyay (Acta Physiologiae Plantarum, 2014)

Phylogenetic analysis of heterocystous cyanobacteria (Subsections IV and V) using highly iterated palindromes as molecular markers - Prashant Singh; Manish Singh Kaushik; Meenakshi Srivastava; Arun Kumar Mishra (Physiology and Molecular Biology of Plants, 2014)

Piperlongumine, an alkaloid causes inhibition of PI3 K/Akt/mTOR signaling axis to induce caspase-dependent apoptosis in human triple-negative breast cancer cells - Shweta Shrivastava; Prasad Kulkarni; Dinesh Thummuri; Manish Kumar Jeengar; V. G. M. Naidu; Mallika Alvala; G. Bhanuprakash Redddy; Sistla Ramakrishna (Apoptosis, 2014)

Evaluation of Differences Among Vigna aconitifolia Varieties for Acquired Thermotolerance - Ramavtar Sharma; Manish Jain; Sushil Kumar; Vinod Kumar (Agricultural Research, 2014)

Modeling of Sediment Yield Prediction Using M5 Model Tree Algorithm and Wavelet Regression - Manish Kumar Goyal (Water Resources Management, 2014)

Statistical Analysis of Long Term Trends of Rainfall During 1901–2002 at Assam, India - Manish Kumar Goyal (Water Resources Management, 2014)

Characteristics of ambient ammonia over Delhi, India - S. K. Sharma; Manish Kumar; Rohtash; N. C. Gupta; Saraswati; Mohit Saxena; T. K. Mandal (Meteorology and Atmospheric Physics, 2014)

Natural Products Modulate Eicosanoid Mediated Nodulation in Poekilocerus pictus Fab. (Acrididae, Orthoptera) - Ajay Pratap Singh; Manish Kumar Jain; Smita Banerjee (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Characterization and functional analysis of eugenol O-methyltransferase gene reveal metabolite shifts, chemotype specific differential expression and developmental regulation in Ocimum tenuiflorum L. - Indu Kumari Renu; Inamul Haque; Manish Kumar; Raju Poddar; Rajib Bandopadhyay; Amit Rai; Kunal Mukhopadhyay (Molecular Biology Reports, 2014)

Climatic control on extreme sediment transfer from Dokriani Glacier during monsoon, Garhwal Himalaya (India) - Amit Kumar; Akshaya Verma; Dwarika Prasad Dobhal; Manish Mehta; Kapil Kesarwani (Journal of Earth System Science, 2014)

Expression of Ceratophyllum demersum phytochelatin synthase, CdPCS1, in Escherichia coli and Arabidopsis enhances heavy metal(loid)s accumulation - Devesh Shukla; Ravi Kesari; Manish Tiwari; Sanjay Dwivedi; Rudra Deo Tripathi; Pravendra Nath; Prabodh Kumar Trivedi (Protoplasma, 2013)

Flood events, fatalities and damages in India from 1978 to 2006 - Omvir Singh; Manish Kumar (Natural Hazards, 2013)

Zingerone Protects Against Stannous Chloride-Induced and Hydrogen Peroxide-Induced Oxidative DNA Damage In Vitro - Iyappan Rajan; Nithya Narayanan; Remitha Rabindran; P. R. Jayasree; P. R. Manish Kumar (Biological Trace Element Research, 2013)

Effect of Actin Polymerization Inhibitor During Oocyte Maturation on Parthenogenetic Embryo Development and Ploidy in Capra hircus - R. Ranjan; R. K. Singh; T. Yasotha; Manish Kumar; Gopal Puri; Kuldeep Kumar; Renu Singh; Sanjeev Bhure; D. Malakar; S. K. Bhanja; M. Sarkar; B. C. Das; et al. (Biochemical Genetics, 2013)

Comparative Evaluation of Porous Versus Nonporous Mucoadhesive Films as Buccal Delivery System of Glibenclamide - Ajay Kumar; Vikas Bali; Manish Kumar; Kamla Pathak (AAPS PharmSciTech, 2013)

Plant proteomics in India and Nepal: current status and challenges ahead - Renu Deswal; Ravi Gupta; Vivek Dogra; Raksha Singh; Jasmeet Kaur Abat; Abhijit Sarkar; Yogesh Mishra; Vandana Rai; Yelam Sreenivasulu; Ramesh Sundar Amalraj; Manish Raorane; Ram Prasad Chaudhary; et al. (Physiology and Molecular Biology of Plants, 2013)

Survivability of parthenogenetic embryos following in vivo transfer in naturally synchronized Capra hircus - Ravi Ranjan; Rakesh Kumar Singh; Thirupathi Yasotha; Manish Kumar; Kuldeep Kumar; Renu Singh; Monzamul Houque; Vijay Prakash Mourya; Gyanendra Singh; Mihir Sarkar; Bikash Chandra Das; Sadhan Bag (In Vitro Cellular & Developmental Biology - Animal, 2013)

Health care industries: potential generators of genotoxic waste - Pratibha Sharma; Manish Kumar; N. Mathur; A. Singh; P. Bhatnagar; M. Sogani (Environmental Science and Pollution Research, 2013)

Response Surface Method Coupled with First-Order Reliability Method Based Methodology for Groundwater Flow and Contaminant Transport Model for the Uranium Tailings Pond Site - Manish Chopra; Rohit Rastogi; A. Vinod Kumar; Faby Sunny; R. N. Nair (Environmental Modeling & Assessment, 2013)

Modeling of antitubercular activity of biphenyl analogs of 2-nitroimidazo[2,1-b][1,3]oxazine to rationalize their activity profile - Sourav Kalra; Ankit Kumar; Manish K. Gupta (Medicinal Chemistry Research, 2013)

Site Suitability Analysis for Urban Development Using GIS Based Multicriteria Evaluation Technique - Manish Kumar; Vasim Riyasat Shaikh (Journal of the Indian Society of Remote Sensing, 2013)

Docking and in silico ADMET studies of noraristeromycin, curcumin and its derivatives with Plasmodium falciparum SAH hydrolase: A molecular drug target against malaria - Dev Bukhsh Singh; Manish Kumar Gupta; Durg Vijay Singh; Sushil Kumar Singh; Krishna Misra (Interdisciplinary Sciences: Computational Life Sciences, 2013)

Application of ANN, Fuzzy Logic and Decision Tree Algorithms for the Development of Reservoir Operating Rules - A. R. Senthil kumar; Manish Kumar Goyal; C. S. P. Ojha; R. D. Singh; P. K. Swamee; R. K. Nema (Water Resources Management, 2013)

Synthesis of combretastatin analogs: evaluation of in vitro anticancer activity and molecular docking studies - Sunil Kumar; Sameer Sapra; Raj Kumar; Manish Kumar Gupta; Surrinder Koul; Tandeep Kour; Ajit Kumar Saxena; Om Prakash Suri; Kanahya Lal Dhar (Medicinal Chemistry Research, 2012)

Synthesis of 1,3,5-trisubstituted pyrazoline nucleus containing compounds and screening for antimicrobial activity - Manish Agrawal; Pankaj Kumar Sonar; Shailendra K. Saraf (Medicinal Chemistry Research, 2012)

Computational studies on molecular interactions of 6-thioguanosine analogs with anthrax toxin receptor 1 - Nitin K. Singh; Britto C. Pakkkianathan; Manish Kumar; Jayssima R. Daddam; Sridhar Jayavel; Mani Kannan; Girinath G. Pillai; Muthukalingan Krishnan (Interdisciplinary Sciences: Computational Life Sciences, 2012)

Role of ROS and COX-2/iNOS inhibition in cancer chemoprevention: a review - Manish Kumar; Subodh Kumar; Satwinderjeet Kaur (Phytochemistry Reviews, 2012)

Increase in growth, productivity and nutritional status of rice (Oryza sativa L. cv. Basmati) and enrichment in soil fertility applied with an organic matrix entrapped urea - Manoj Kumar; Kuldeep Bauddh; Manish Sainger; Poonam Ahlawat Sainger; Jay Shankar Singh; Rana Pratap Singh (Journal of Crop Science and Biotechnology, 2012)

Evaluation of machine learning tools as a statistical downscaling tool: temperatures projections for multi-stations for Thames River Basin, Canada - Manish Kumar Goyal; Donald H. Burn; C. S. P. Ojha (Theoretical and Applied Climatology, 2012)

Epiphytic pink-pigmented methylotrophic bacteria enhance germination and seedling growth of wheat (Triticum aestivum) by producing phytohormone - Kamlesh K. Meena; Manish Kumar; Marina G. Kalyuzhnaya; Mahesh S. Yandigeri; Dhananjaya P. Singh; Anil K. Saxena; Dilip K. Arora (Antonie van Leeuwenhoek, 2012)

Downscaling of surface temperature for lake catchment in an arid region in India using linear multiple regression and neural networks - Manish Kumar Goyal; C. S. P. Ojha (International Journal of Climatology, 2012)
In this paper, downscaling models are developed using a Linear Multiple Regression (LMR) and Artificial Neural Networks (ANNs) for obtaining projections of mean monthly maximum and minimum temperatures ( T max and T min) to lake‐basin scale in an arid region in India. The effectiveness of these techniques is demonstrated through application to downscale the predictands for the Pichola lake region in Rajasthan State in India, which is considered to be a climatically sensitive region. The predictor variables are extracted from: (i) the National Centers for Environmental Prediction (NCEP) reanalysis dataset for the period 1948–2000; and (ii) the simulations from the third‐generation Canadian Coupled Global Climate Model (CGCM3) for emission scenarios A1B, A2, B1, and COMMIT for the period 2001–2100. The scatter‐plots and cross‐correlations are used for verifying the reliability of the simulation of the predictor variables by the CGCM3 and to study the predictor–predictand relationships. The performance of the linear multiple regression and ANN models was evaluated based on several statistical performance indicators. The ANN‐based models are found to be superior to LMR‐based models and subsequently, the ANN‐based model is applied to obtain future climate projections of the predictands. An increasing trend is observed for T max and T min for A1B, A2, and B1 scenarios, whereas no trend is discerned with the COMMIT scenario by using predictors. Copyright © 2011 Royal Meteorological Society

Climate Policy in India: What Shapes International, National and State Policy? - Aaron Atteridge; Manish Kumar Shrivastava; Neha Pahuja; Himani Upadhyay (Ambio, 2012)

How Should Support for Climate-Friendly Technologies Be Designed? - Carolyn Fischer; Asbjørn Torvanger; Manish Kumar Shrivastava; Thomas Sterner; Peter Stigson (Ambio, 2012)

Identification of TLR inducing Th1-responsive Leishmania donovani amastigote-specific antigens - Ankita Srivastava; Nisha Singh; Manish Mishra; Vinod Kumar; Jalaj K. Gour; Surabhi Bajpai; Sangram Singh; Haushila P. Pandey; Rakesh K. Singh (Molecular and Cellular Biochemistry, 2012)

Improvement in the diagnosis of Brucella abortus infections in naturally infected water buffaloes (Bubalus bubalis) using an ELISA with a Protein-G-based indicator system - Manish Kumar; Puran Chand (Tropical Animal Health and Production, 2011)

A DEM-based evaluation of potential flood risk to enhance decision support system for safe evacuation - Jinyoung Kim; Yuji Kuwahara; Manish Kumar (Natural Hazards, 2011)

Effect of Selenium on Connexin Expression, Angiogenesis, and Antioxidant Status in Diabetic Wound Healing - Surabhi Bajpai; Manish Mishra; Hemant Kumar; Kamlakar Tripathi; Santosh Kumar Singh; Haushila Prasad Pandey; Rakesh Kumar Singh (Biological Trace Element Research, 2011)

PLS regression-based pan evaporation and minimum–maximum temperature projections for an arid lake basin in India - Manish Kumar Goyal; C. S. P. Ojha (Theoretical and Applied Climatology, 2011)

Cuminum cyminum Linn. and Coriandrum sativum Linn. extracts modulate Chromium genotoxicity in Allium cepa chromosomal aberration assay - Arti Sharma; Manish Kumar; Satwinderjeet Kaur (The Nucleus, 2011)

Estimation of Scour Downstream of a Ski-Jump Bucket Using Support Vector and M5 Model Tree - Manish Kumar Goyal; C. S. P. Ojha (Water Resources Management, 2011)

A time course study on prothrombotic parameters and their modulation by anti-platelet drugs in hyperlipidemic hamsters - Vishal Singh; Manish Jain; Prem Prakash; Ankita Misra; Vivek Khanna; Rajiv Lochan Tiwari; Ravi Shankar Keshari; Shivendra Singh; Madhu Dikshit; Manoj Kumar Barthwal (Journal of Physiology and Biochemistry, 2011)

Identification of aquifer-recharge zones and sources in an urban development area (Delhi, India), by correlating isotopic tracers with hydrological features - Manish Kumar; M. Someshwar Rao; Bhishm Kumar; Algappan Ramanathan (Hydrogeology Journal, 2011)

Tracing the factors responsible for arsenic enrichment in groundwater of the middle Gangetic Plain, India: a source identification perspective - Pankaj Kumar; Manish Kumar; A. L. Ramanathan; Maki Tsujimura (Environmental Geochemistry and Health, 2010)

Trace Element Studies on Tinospora cordifolia (Menispermaceae), Ocimum sanctum (Lamiaceae), Moringa oleifera (Moringaceae), and Phyllanthus niruri (Euphorbiaceae) Using PIXE - Ramadurai Gowrishankar; Manish Kumar; Vinay Menon; Sai Mangala Divi; M. Saravanan; P. Magudapathy; B. K. Panigrahi; K. G. M. Nair; K. Venkataramaniah (Biological Trace Element Research, 2010)

Co-inoculation of the endophytic fungus Piriformospora indica with the phosphate-solubilising bacterium Pseudomonas striata affects population dynamics and plant growth in chickpea - Kamlesh K. Meena; Sukumar Mesapogu; Manish Kumar; Mahesh S. Yandigeri; Geeta Singh; Anil K. Saxena (Biology and Fertility of Soils, 2010)

Effect of Novel Amino Acids and Dipeptides Substituted 3-Morpholino Arecoline Derivatives as Muscarinic Receptor 1 Agonists in Alzheimer’s Dementia Models - S. R. Ranganatha; Manish Malviya; Y. C. Sunil Kumar; K. Vinaya; D. S. Prasanna; M. N. Subhash; K. S. Rangappa (International Journal of Peptide Research and Therapeutics, 2009)

Effects of 24-epibrassinolide and 28-homobrassinolide on the growth and antioxidant enzyme activities in the seedlings of Brassica juncea L. - Geetika Sirhindi; Sandeep Kumar; Renu Bhardwaj; Manish Kumar (Physiology and Molecular Biology of Plants, 2009)

Potent antimalarial activity of newly synthesized substituted chalcone analogs in vitro - Satish K. Awasthi; Nidhi Mishra; Brajesh Kumar; Manish Sharma; Amit Bhattacharya; Lokesh C. Mishra; Virendra K. Bhasin (Medicinal Chemistry Research, 2009)

Bacopa monniera exerts antiamnesic effect on diazepam-induced anterograde amnesia in mice - Sudesh Prabhakar; Manish Kumar Saraf; Promila Pandhi; Akshay Anand (Psychopharmacology, 2008)

Urban cadastral mapping using very high resolution remote sensing data - K. N. Prudhvi Raju; Sarvajeet Kumar; Kshitij Mohan; Manish Kumar Pandey (Journal of the Indian Society of Remote Sensing, 2008)

Impact of Tropical Ecosystem on the Migrational Behavior of K-40, Cs-137, Th-232 U-238 in Perennial Plants - Ajay Kumar; R. K. Singhal; J. Preetha; K. Rupali; U. Narayanan; Sughandhi Suresh; Manish K. Mishra; A. K. Ranade (Water, Air, & Soil Pollution, 2008)

Assessment of the impact of landfill on groundwater quality: A case study of the Pirana site in western India - Umesh Kumar Singh; Manish Kumar; Rita Chauhan; Pawan Kumar Jha; AL. Ramanathan; V. Subramanian (Environmental Monitoring and Assessment, 2008)

Applying Fuzzy logic and the point count system to select landfill sites - C. S. P. Ojha; Manish Kumar Goyal; Sunil Kumar (Environmental Monitoring and Assessment, 2007)

Design and development of microemulsion drug delivery system of acyclovir for improvement of oral bioavailability - Pradip Kumar Ghosh; Rita J. Majithiya; Manish L. Umrethia; Rayasa S. R. Murthy (AAPS PharmSciTech, 2006)

Dibutyryl c-AMP as an inducer of sporidia formation: Biochemical and antigenic changes during morphological differentiation of Karnal bunt (Tilletia indica) pathogen in axenic culture - Anil Kumar; Kaushlendra Tripathi; Manish Rana; Shalini Purwar; G. K. Garg (Journal of Biosciences, 2004)

Preparation and characterization of flurbiprofen beads by melt solidification technique - Anant Paradkar; Manish Maheshwari; Amit Kumar Tyagi; Bhaskar Chauhan; S. S. Kadam (AAPS PharmSciTech, 2003)

Air Quality Assessment along Dhanbad – Jharia Road - Manish Kumar Jain; N. C. Saxena (Environmental Monitoring and Assessment, 2002)